Context-dependent NRF2 signaling in cancer: mechanisms and precision modulation - Ling-Lan Cong; Xue-Ling Dai; Xiu-Jun Liu; Ya-Xuan Sun (Molecular Biology Reports, 2026)

Structure and functional properties of Dendrobium officinale polysaccharide-hemp seed protein gels for dysphagia diets as regulated by alkali concentration and temperature - Tingting Ding; Jing Sun; Qingquan Ma; Shuqi Gao; Cong Lu; Jiameng Liu; Fengzhong Wang; Bei Fan (Food Research International, 2026)

Interfacial dual-gradient modulation of charge and free water for efficient alkaline hydrogen evolution - Qing Zhang; Cong Liu; Chao Wang; Sunyufei Wang; Mengyang Dong; Ziqi Sun; David A. Cardwell; Dingsheng Wang; Hua Kun Liu; Shi Xue Dou; Yuhai Dou; Ding Yuan (Chemical Engineering Journal, 2026)

Planarization engineering of benzodithiophene-based nanogrids for enhanced carrier mobility and emission performance - Lei Yang; Jun Yang; Shi-rui Chen; Wen-bin Xie; Cong Sun; Wang-yang Wu; Xin-zhe Peng; Manas Ranjan Dash; Xue-qin Ran; Mohamad Akbar Ali; Ling-hai Xie (Chemical Engineering Journal, 2026)

Evaluating Sacubitril/Valsartan's efficacy in reducing myocardial hypertrophy and fibrosis in feline models - Zeyao Sun; Wenjia Huang; Xinyue Chai; Changmin Hu; Cong Zhu (The Veterinary Journal, 2026)

Systemic metabolic reprogramming underlies cold stratification–induced seed dormancy release in Cercis chinensis revealed by integrated physiological and multi-omics analyses - Tao Huang; Can Wang; Liyong Sun; Yuxiao Wang; Shuaikang Cui; Cong Lei; Yue Jiang; Shuxian Li (Plant Science, 2026)

Impact of agricultural waste recycling on soil physical responses: Effects of straw incorporation rate and moisture content on electrical and thermal conductivity of loess - Cong Zhang; Qiang Sun; Xiaojing Wang; Zifan Yang; Pengda Ma; Xin Hu; Jingjing Nan; Bin Chen (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Elemental sulfur-enhanced hydrothermal stabilization of arsenic in arsenic sulfide sludges: Mechanism of sulfur-induced structure transformation and practical application - Hui Xu; Wanlan Wu; Qiujing Xu; Yong Ke; Yun Li; Cong Peng; Lin Yu; Zhumei Sun; Yunyan Wang; Xiaobo Min (Journal of Environmental Chemical Engineering, 2026)

Regeneration behavior of sulfur-modified waste-derived sorbents for Hg0 removal: enhanced performance and synergistic mechanism - Ziyao Yang; Yunyun Hu; Yipeng Wang; Peijian Sun; Cong Nie; Jizhao Guo; Xuehui Sun; Mantang Chen; Yang Xu (Fuel, 2026)

Thermodynamic compatibility and conformational adaptability enable the matrix-adaptive protection of glycated pea protein isolate-curcumin nanoparticles in frying oils - Zhi-feng Tan; Cong Sun; Shi-hui Zhao; Zhen-wen Shao; Da-yong Zhou; Liang Song (Food Chemistry, 2026)

MMP9 mediates 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD)-induced osteoarthritis cartilage damage via regulating the p38 MAPK pathway: A mechanistic study based on network toxicology and multi-omics - Jiahao Sun; Chuanjie Li; Qi Sun; Xin Li; Cong Wang; Yongkui Zhang; Wenpeng Xie (Food and Chemical Toxicology, 2026)

Biobased dynamic vitrimer network enables high intrinsic thermal conductivity, closed-loop recycling and strong adhesion - Hongmin Sun; Xu Han; Dewang Hou; Cong Guo; Ying Wang; Xiahui Jiang; Ruiguang Li; Chengjie Li (Chemical Engineering Journal, 2026)

Contrasting urban tree species exhibit site-dependent variation in drought resistance and recovery - Lu Liu; Ji Zheng; Ningxiao Sun; Wen Sun; Jingli Yan; Fuxin Cong; Bo Peng; Xinxin Wang; Shan Yin (Agricultural and Forest Meteorology, 2026)

Engineered exosomes embedded in bioactive hydrogel for remodeling bacteria-infected diabetic wounds - Jidan Cui; Jianbin Shi; Xinhao Wang; Xiao Kuang; Jin Sun; Zhonggui He; Cong Luo; Shenwu Zhang (Chemical Engineering Journal, 2026)

Corrigendum to ‘Machine Learning-Driven Recombinant Xylanase Synergized with Pediococcus pentosaceus: Directed Xylose-Lactate Conversion and Metabolic Mechanism of Lignocellulosic Waste’[Resources, Conservation & Recycling 234 (2026) Article 109058] - Jiajin Sun; Yujuan Zhang; Luyao Zhang; Chen Shen; Yitong Lin; Rong Zhao; Lei Chen; Qiang Liu; Cong Wang; Wenjie Huo; Gang Guo (Resources, Conservation and Recycling, 2026)

Targeted isolation of previously undescribed fortunefuroic acid-type triterpenoids from Keteleeria pubescens using 1H NMR/LC-PDA-MS and assessment of ACL Inhibition - Chun-Jing Chi; Ze-Yu Zhao; Yi Zang; Cong Li; Jia Li; Dong Huang; Peng Sun; Juan Xiong; Yeun-Mun Choo; Jin-Feng Hu (Phytochemistry, 2026)

Dual effects of a freely floating body on sloshing: Suppression, amplification, and coupled response under harmonic excitation - Cong Wang; Tianze Lu; Yunjia Sun; Ignacio Barranco; Deping Cao; Jinghua Wang (Ocean Engineering, 2026)

Function identification of nitrogen forms in nitrogen-doped biochar for promoting methane production in anaerobic digestion - Xiao-Yue Cao; Cong-Cong Tang; Shuo-Han Chen; Sheng-Jie Sun; Chun-Xue Yang; Ai-Juan Zhou; Zewei Liu; Zhang-Wei He (Environmental Research, 2026)

Oxygen-vacancy-driven dipole ordering and anion anchoring in BaTiO3 nanofibers for high-performance gel polymer electrolytes in high-voltage lithium metal batteries - Yaoxiang Shan; Cong Kang; Bingkun Zang; Ting Li; Bingjia Lu; Rui Sun; Huiying Qu; Xucai Yin; Yang Ren (Chemical Engineering Journal, 2026)

Lattice oxygen transport and structural evolution of oxygen carriers for chemical looping reforming: A review of mechanisms, challenges, and regulation strategies - Yile Zou; Hui Liu; Cong Wang; Ruizhi Li; Yaning Zhang; Zhao Sun (Chemical Engineering Journal, 2026)

Aggregate-specific microbial adaptive strategies to nitrogen addition regulate carbon and nitrogen use efficiencies in a meadow steppe - Zhirui Wang; Tianpeng Li; Changming Lu; Jiangping Cai; Xue Feng; Mikhail V. Semenov; Cong Wang; Xiaotao Lü; Heyong Liu; Osbert Jianxin Sun; Xingguo Han; Irina Kravchenko; et al. (CATENA, 2026)

Enhancing selective esterification of conjugated linoleic acid isomers by immobilized Candida rugosa lipase via hydrophobic acyl acceptors - Meijun Du; Jun Jin; Cong Sun; Abdelaziz Elbarbary; Wei Wei; Hui Zhang; Qingzhe Jin; Xingguo Wang; Zhe Cui (Bioresource Technology, 2026)

Effects of estrone-3-glucuronide on HSD gene expression in steroidogenesis of the sea urchin Mesocentrotus nudus - Yuhan Hu; Weihan Meng; Xiaoxiao Huang; Heng Xiang; Jingjing Cong; Yaqing Chang; Zhihui Sun (Aquaculture International, 2026)

Experimental investigation on smoke control and smoke extraction efficiency of two-point extraction system under longitudinal sloped tunnel fires - Zhuyu Shao; Mingshu Bi; Haiyong Cong; Luyang Liu; Fengnan Sun; Yubo Bi; Tianjiao Zhang (Tunnelling and Underground Space Technology, 2026)

Retraction notice to “Altitude explains insignificant autumn phenological changes across regions with large topography relief in the Tibetan Plateau” [Sci. Total Environ. 921 (2024) 171088] - Nan Cong; Zhiyong Du; Zhoutao Zheng; Guang Zhao; Dongqi Sun; Jiaxing Zu; Yangjian Zhang (Science of The Total Environment, 2026)

A tolerogenic mRNA-LNP vaccine alleviates neuroinflammation and demyelination in experimental autoimmune encephalomyelitis - Yi Song; Zhangchi Dongye; Jiaxi Yao; Xiaonan Zhao; Tao Mo; Shiyu Yang; Cong Sun; Tingting Zhao; Jian Li; Yuzhang Wu (Science Bulletin, 2026)

Machine learning-driven recombinant xylanase synergized with Pediococcus pentosaceus: directed xylose-lactate conversion and metabolic mechanism of lignocellulosic waste - Jiajin Sun; Yujuan Zhang; Luyao Zhang; Chen Shen; Yitong Lin; Rong Zhao; Lei Chen; Qiang Liu; Cong Wang; Wenjie Huo; Gang Guo (Resources, Conservation and Recycling, 2026)

Magnetic MnFe2O4 modified sludge biochar for peroxymonosulfate activation to enhance deep dewatering of excess sludge: Performance and synergistic mechanism - Jinyun Guan; Kai Cheng; Cong Zhang; Yihang Sun; Yichenyang Li; Chong Li; Jifeng Guo (Process Safety and Environmental Protection, 2026)

Three New Arnebin-type metabolites extracted from Arnebia euchroma: Structural analysis and antitumor activity evaluation - Guang-Jie Pan; Yu Sun; De-Gang Qing; Cong-Zhao Fan; Guo-Xu Ma; Zhong-Hao Sun; Lei-Ling Shi; Jing Zhang (Phytochemistry Letters, 2026)

A study on the hydrodynamic performance and wake modulation effect of a twisted pre-swirl stator in a rim-driven thruster - Yi-Ming Hu; Cong Sun; Min Liu; Chun-Yu Guo; Pei-Rui Tang; Yu Zhao; Chao Wang (Ocean Engineering, 2026)

Combined effects of microplastics and Pb on soil-tobacco systems revealed by soil microbiomics and metabolomics - Rong ZHAO; Zeyu ZUO; Ping CONG; Haibin LI; Mingwei LI; Yanna ZHAO; Fang ZUO; Jiao SUN; Yuhuan SUN; Guangjian XU; Xuebo ZHENG; Fayuan WANG (Pedosphere, 2026)

Simultaneous elimination of perfluorooctanoic acid and its degradation-derived fluoride ions: A calcium hydroxide-activated peroxymonosulfate process - Cong Gao; Xuan Liu; Xiaotong Xu; Shuang Song; Yanming Liu; Hong Chen; Ruijun Sun (Journal of Water Process Engineering, 2026)

Exogenous calcium modulates oxalic acid metabolism via repression of LcAAE3 and mediates calcium accumulation in litchi pericarp and fruit pedicel - Dong-Cheng Li; Zhi-Qun Zhong; Teng-Kai Chen; Yi-Tong Liu; Yue-Han Sun; Hui-Cong Wang; Ren-Fang Zeng; Xu-Ming Huang (Journal of Plant Physiology, 2026)

Data-Driven Co-management: synergizing soil quality and crop productivity for sustainable agriculture - Xiaowen Gu; Pengqi Liu; Kang Wang; Qingwen Shi; Yuxiao Wu; Junwei Sun; Wen-Feng Cong; Hao Ying (Journal of Cleaner Production, 2026)

Coupling microbial functional profiles with depth-resolved molecular transformation of dissolved organic matter in mangrove sediments - Luyao Huang; Bin Sun; Kunyu Zhang; Haojie Lei; Cong Wang; Qi Wang; Zhiwei Cao; Jieming Liao; Yizhou Jiang; Yunlei Zhang; Yunting Xiong; Pei Wang; et al. (Journal of Environmental Sciences, 2026)

Unveiling the dynamic electron transfer at asymmetric Fe-O-Co sites for sustained PMS activation via in-situ synchrotron spectroscopy - Xian-Chuan Chen; Fu-Sheng Sun; Cong-Qiang Liu; Guang-Hui Yu (Journal of Environmental Sciences, 2026)

Predictors, sources, and health risks of environmental antibiotic exposure in Chinese pregnant women - Lu Qian; Yi Wang; Sumiao Hong; Yuanping Wang; Haiping Lin; Yuanyuan Chen; Baochang Sun; Yu Liu; Mingxue Wang; Xinyi Zhu; Haozhe Gu; Jiaqi Liu; et al. (Environmental Pollution, 2026)

Synergistic aggregation inhibition and radical-catalyzed doping in 3D crosslinked electron transport layer for efficient and stable inverted perovskite solar cells - Daizhe Wang; Guibin Shen; Dongqing He; Cong Kang; Chaofeng Zhu; Baitong Yan; Jiadong Xue; Xueye Ren; Xiaochen Sun; Dongyan Tang; Yong Zhang; Zhipeng Kan; et al. (Chemical Engineering Journal, 2026)

Reversible anhydride-alcohol network enables highly thermal conductive phase change composites for thermal management and thermoelectric generator - Dewang Hou; Hongmin Sun; Xu Han; Cong Guo; Ying Wang; Yifan Xue; Ruiguang Li; Chengjie Li (Chemical Engineering Journal, 2026)

Niflumic acid suppresses NLRP3 inflammasome activation by limiting chloride efflux and mitochondrial ROS production - Yuanhao Li; Qianqian Xie; Tianyin Sun; Jiwei Lu; Mengmeng Li; Renan Bai; Ronghua Lv; Fei Li; Haoqi Wang; Jingjing Cong; Wenwei Yin; Jing Li; et al. (Inflammation Research, 2026)

Tumor-confined nano-activators for antigen-independent broad activation of tumor-infiltrating T cells - Yue Wang; Min Yang; Bao-Yue Zhang; Mei-Tang Peng; Yi-Qun Sun; Shi-Kun Zhou; Wei Li; Xian-Zhu Yang; Shi-Dang Xu; Zi-Dong Lu; Cong-Fei Xu; Jun Wang (Science Bulletin, 2026)

Effects of circumferential and streamwise micro-groove arrangements on the hydrodynamic and acoustic performance of a pump-jet propulsor - Chao Wang; Yu Zhao; Cong Sun; Lian-Zhou Wang; Yu-Long Feng (Ocean Engineering, 2026)

From tomato peel waste to functional magnetic biochar: Recyclable adsorbent for efficient phenol removal from wastewater - Xiulin Feng; Xuedi Zhan; Xuening Sun; Yue Zhang; Jiangfen Duan; Cong He; Haifeng Zhang; Yakun Tang; Jinhui Yang (Journal of Water Process Engineering, 2026)

Pre-homogenization heat treatment as a novel strategy to enhance oat milk stability: Unraveling the role of protein modification - Xiaojie Qian; Yang Wu; Binghua Sun; Cong Sun; Sen Ma; Xiaoxi Wang (Innovative Food Science & Emerging Technologies, 2026)

Climate change rather than grazing dominates the declined resilience of Chinese grassland - Huanhuan Liu; Yangjian Zhang; Zhoutao Zheng; Guang Zhao; Yu Zhang; Li Liu; Nan Cong; Xiaoqing Duan; Yihan Sun (Global and Planetary Change, 2026)

Facile construction of a dual pH/redox-responsive nanopesticide for precise control of Fusarium graminearum with enhanced biosafety - Li Sun; Demei Xing; Zhen Li; Yanyan Gao; Yue Peng; Jiale Zhang; Yue Gao; Ruihan Gong; Cong Zhou; Jiagao Cheng (Chemical Engineering Journal, 2026)

Multidimensional transcriptomic analysis and in vitro experiments dissect the landscape of 2′,2′,4′,4′-Tetrabromodiphenyl ether in bladder cancer progression - Minghui Sun; Dichao Hu; Tongjie Li; Zeping Chen; Bo Cong; Zhen Xi; Yongchen Wang; Rulin Guo; Jian Zhuo; Wenbo Wu; Haitao Liu (Chemico-Biological Interactions, 2026)

Engineering of a marine cyclodextrin glucosyltransferase for efficient synthesis of 2-O-α-D-glucopyranosyl-L-ascorbic acid using maltodextrin - Wei Wang; Yang Zheng; Jingjing Sun; Chengcheng Jiang; Cong Lin; Jianhua Hao (Systems Microbiology and Biomanufacturing, 2026)

Sorghum sudanense Rotation Alleviates Biochar-Induced Salinity Accumulation While Maintaining Soil Organic Carbon Stability in Intensive Vegetable Systems - Jining Zhang; Huifeng Sun; Shanliang Liu; Cong Wang; Xianxian Zhang; Zheng Jiang; Sheng Zhou (Journal of Soil Science and Plant Nutrition, 2026)

BCAT1 mediates the carcinogenic effects of environmental bisphenol exposure: mechanistic discoveries in osteosarcoma and pan-cancer analysis - Sun Jiahao; Wang Cong; Li Xin; Cui Xu; Xie Wenpeng; Zhang Yongkui (Molecular Diversity, 2026)

Histone chaperone HIRA restrains ferroptosis susceptibility through epigenetic control of iron metabolism in prostate cancer - Enlin Wang; Qilan Sun; Zhicheng Xu; Cong Huang; Yue Chen; Qingqing Wang; Siqi Liu; Xinrui Wang; Xiaohe Ren; Feng Sun; Sheng Tai; Mafei Xu (Science China Life Sciences, 2026)

Decoding Climate-Zone-Specific Nonlinear Interactions Between Urban Morphology, Vegetated Coverage, and Land Surface Temperature for the United States - Cong Guo; Xinyuan Sun; Wenqing Wan; Renlu Qiao; Zhiqiang Wu (Sustainable Cities and Society, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Revealing the roles of biochar in anaerobic digestion of waste activated sludge with the overloading accumulation of humic acids - Wen-Tao Li; Fei Wang; Qing-Bin Meng; Sheng-Jie Sun; Cong-Cong Tang; Lei Yang; Jun Lan; Ai-Juan Zhou; Wenzong Liu; Yong-Xiang Ren; Zhang-Wei He (Journal of Water Process Engineering, 2026)

Nontarget screening of halogenated nucleotide analogs in water by chemical derivatization coupled with FT-ICR MS - Guangrong Sun; Dongquan Li; Feiyang Huang; Haibing Cong (Journal of Environmental Chemical Engineering, 2026)

A flow-through E-peroxone reactor for simultaneous in situ disinfection and purification of simulated swimming pool water - Cong Geng; Ruilan Liu; Jianqiu Chen; Dan Li; Weichun Gao; Zicheng Sun; Jiyan Liang (Journal of Environmental Chemical Engineering, 2026)

Elucidating the synergistic mechanism of dextran and polyphenols in modulating thermal aggregation behavior and gel properties of myofibrillar protein induced by high temperature - Xiaoming Zhang; Jingyi Sun; Yujuan Xu; Cong Li; Hui Zhou; Baocai Xu (Food Hydrocolloids, 2026)

A potent human neutralizing antibody targeting the receptor-binding site in the glycoprotein gp350 of Epstein-Barr virus - Qingtai Liang; Qian-Ying Zhu; Xin-Yan Fang; Jing Wei; Yi-En Xu; Yanan Zuo; Guo-Long Bu; Chu Xie; Sisi Shan; Cong Sun; Zheng Liu; Linqi Zhang; et al. (Science China Life Sciences, 2026)

Lactiplantibacillus Plantarum O126 Postbiotics Boost growth, Antioxidant levels, Disease resistance, and Gut Health in Sea Cucumber (Apostichopus japonicus) - Feng-Li Chen; Hui-Ting Zhao; Wei Gu; Zong-Xiu Wu; Jing-Wen Xiang; Qing Yang; Yu-Lin Yang; Lei Tan; Meng-Xia Sun; Wei Cong; Shu Li; Bin-Tong Yang; et al. (Probiotics and Antimicrobial Proteins, 2026)

Collaborative planning methodology for observation and data transmission missions of the lunar far side and polar landing regions - Xiaohan Mei; Wenkai Zheng; Yiqin Cong; Shengxin Sun; Cheng Wei (Advances in Space Research, 2026)

Numerical investigation of cavitation and vortex evolution characteristics in a hull-propeller-rudder coupled system - Chao Wang; Yi-Ming Hu; Cong Sun; Yu Zhao; Yang Han; Lian-Zhou Wang; Jia-Xiu Cao (Ocean Engineering, 2026)

Calcium silicate hydrate-mediated in-situ phosphorus immobilization facilitates subsequent eutrophic sediment dewatering through structure reorganization - Cong Zhao; Yuxiao Sun; Zheng Wu; Jiarun Lv; Daoping Peng; Chunxiao Meng (Chemical Engineering Journal, 2026)

Multifunctional carboxymethyl cellulose/polydopamine dual-network conductive hydrogels for motion detection and photothermal therapy - Yiying Wei; Bo Cong; Xiaopu Ji; Dangyang Wang; Jinghui Hu; Zonglei Mou; Haiqing Song; Yue Zhi; Yushu Liu; Guofeng Zhang; Wan Ru Sun; Pingyu Wang; et al. (Carbohydrate Polymers, 2026)

Genetic mapping and identification of a major quantitative trait locus associated with the high fiber strength introgressed from Gossypium barbadense - Kai Wang; Haohong Tang; Cong Sun; Xiaohu Ma; Shen Ren; Jie Li; Xinyu Zhang; Shuaishuai Cheng; Xianpeng Xiong; Jie Sun (Plant Cell Reports, 2026)

Multi-omics analysis provides genetic evidence for the involvement of cell adhesion pathway in the pathogenesis of biliary atresia - Rui Dong; Jinhang Zhu; Chunjing Ye; Fenglong Sun; Cong Huai; Wei Zhou; Jiajie Zhu; Xiaoqi Feng; Qiange Xiao; Deqian Chen; Yifan Yang; Ran Yang; et al. (Science China Life Sciences, 2026)

From copper transport to cuproptosis: emerging therapeutic targets in cardiovascular disease - Xiaobing Zhang; Jiawen Liu; Cong He; Yu Wang; Qianyue Ni; Yabin Zhou; Jing Sun (Molecular and Cellular Biochemistry, 2026)

Development of a carbon-sequestering binder using carbonated ground granulated blast-furnace slag/carbide slag blends and desulfurization gypsum for silty clay stabilization - Cong Wang; Yifeng Ling; Lei Ran; Yanbing Sun; Sudong Hua; Xuhao Wang (Sustainable Chemistry and Pharmacy, 2026)

Nanoimprinted topological laser in the visible - Qiang Zhang; Rui Duan; Yutian Ao; Lin Wang; Xuehong Zhou; Xuyong Yang; Qing Zhang; Xiao-Cong Yuan; Baile Zhang; Handong Sun (Science Bulletin, 2026)

Unraveling the roles of reactive nitrogen species in the UV/nitrate degradation of naproxen - Cong Liu; Dihao Bai; Yuting Peng; Huiyu Dong; Lingfei Li; Lei Sun; Xiangjuan Yuan (Journal of Environmental Chemical Engineering, 2026)

Non-negligible risk of nitrogenous disinfection byproducts arising from the chlorination of ammonia-containing source water - Guangrong Sun; Dongquan Li; Feiyang Huang; Han Yeong Kaw; Hainan Wu; Haibing Cong (Journal of Environmental Chemical Engineering, 2026)

Land use and carbon stock changes in China: spatiotemporal evolution and forecasting analysis - Zhaoxu Zhang; Xutong Li; Sijia Du; Cong Shi; Zhenwei Shi; Yuanheng Sun (Gondwana Research, 2026)

The interactive effects of roasting degree and lipid content on the gas retention capacity in fermented oat dough - Fan Yang; Wenhua Ma; Ruige Yu; Binghua Sun; Xiaojie Qian; Cong Sun; Chong Liu; Sen Ma; Xiaoxi Wang (Food Research International, 2026)

Bioactive carbon dots as antibacterial neural interface for neuron recording - Wanyu Tang; Yang Wang; Huan Wang; Zhaoliang Ni; Xinyu Sun; Liu Cong; Xiaoyi Zuo; Ziying Meng; Shaofang Zhang; Hao Wang; Jinsong Ren; Shuangjie Liu; et al. (Chemical Engineering Journal, 2026)

Isolation and Identification of Lactic Acid Bacteria from Traditional Fermented Shredded Potato and Research on Their Prebiotic, Antioxidant, and Fermentative Properties - Nan Hu; Jie Ji; Hongji Zhao; Jingyi Sun; Shanzi Cong (Probiotics and Antimicrobial Proteins, 2026)

Risk assessment and source apportionment of heavy metals in soil-highland barley system of farmland in Yarlung Zangpo River basin, Tibet - Yufan Zhu; Xuandi Zhang; Mingkun Sun; Gulipiyan Balajiang; Yumeng Zhang; Yuhui Dang; Xueyan Gu; Cong Yuan; Shiwei Ai (Environmental Geochemistry and Health, 2026)

Mantle dunites archive multistage melt metasomatism under a fossil slow-ultraslow spreading center: an example from the Tibetan Xigaze ophiolite - Li Wang; Qing Xiong; Hong-Kun Dai; Xiang Zhou; Hong-Da Zheng; Hao-Qin Sun; Yi-Cong Li; Long-Fei Xue; Alessio Sanfilippo; Valentin Basch; Jian-Ping Zheng (Contributions to Mineralogy and Petrology, 2026)

Microbial metabolism decline in degraded grasslands depends on soil organism size - Yang Hu; Mengfei Cong; Tianle Kou; Han Yan; Xinya Sun; Haolin Zhang; Yakov Kuzyakov; Yang Yang; Yimei Huang; Yanxing Dou; Zhaolong Zhu; Baorong Wang; et al. (Agriculture, Ecosystems & Environment, 2026)

Depth Conversion of Underwater Static Electric Fields for Submersibles in High-Latitude Low-Temperature Sea Areas - Yuhong Li; Cong Chen; Hongsen Zhao; Yiqun Liu; Yunfu Hou; Jiaqing Sun; Wentie Yang (Journal of Marine Science and Engineering, 2026)
Depth conversion of underwater static electric fields refers to a mathematical approach that indirectly determines the distribution of planar electric fields at larger depths using measured planar electric field data obtained from a shallower region with finite depth and limited area. The complicated environment of high-latitude low-temperature sea areas further increases the difficulty of performing practical large-depth measurements of underwater electric fields. Therefore, depth conversion becomes an important technical strategy for overcoming the constraints of field measurements and for comprehensively understanding the distribution of underwater static electric fields of the target. This study begins with the mathematical formulation of the depth conversion problem, solves the related boundary value problem, and develops the corresponding depth conversion method. Subsequently, based on COMSOL simulation data of the underwater static electric field generated by a scaled-down submersible model, numerical analyses are conducted to investigate the effects of factors such as grid discretization, measurement plane dimensions, conversion depth, and data noise on the conversion accuracy. Finally, the reliability of the conversion method is validated in a laboratory environment by simulating a naturally frozen sea area and employing measured underwater static electric field data from the scaled-down submersible model. The results demonstrate that the developed conversion method can effectively achieve extrapolation of the underwater static electric field of the submersible from shallow regions to deeper water. Even when the noise amplitude is nearly twice that of the effective signal and the conversion depth reaches 8 times the outer diameter of the submersible, the relative root mean square error (RRMSE) of the conversion results can still be maintained below 0.10. These findings provide useful references for the advancement of technologies related to underwater electric field characteristic recognition and electric field stealth performance evaluation in high-latitude low-temperature sea areas.

Computing transient responses of floating structure arrays in the frequency domain - Chongyang Sun; Jinwei Sun; Shuai Cong; Meng Shao; Linqiang Zhang (Ocean Engineering, 2026)

Corrigendum to “Research on early warning and control measures for arable land resource security” [Land Use Policy 128 (2023), 106601] - Xueqing Sun; Pengcheng Xiang; Kexin Cong (Land Use Policy, 2026)

How does urban-rural integration synergize food security and agricultural carbon efficiency? The moderating role of artificial intelligence and heterogeneous pathways - Cong Sun; Enjun Xia; Jieping Huang; Haotian Tong; Fengtian Zhu; Kuan Yan (Journal of Rural Studies, 2026)

Unraveling the nonlinear effects of urban blue-green spaces on residents’ health in the United States (2000–2019) - Cong Guo; Xinyuan Sun; Wenqing Wan; Wei Wang; Peng Yuan (Journal of Environmental Management, 2026)

Lithogenic control on zinc stable isotopes in riverine systems: The importance of carbonate dissolution - Qinyuan Qu; Zhongwei Wang; Benjamin Chetelat; Zhengrong Wang; Qingchuan Liu; Mei Sun; Wei Yuan; Hongming Cai; Jianfeng Liu; Pengxue Gai; Yi Liu; Wang Zheng; et al. (Geochimica et Cosmochimica Acta, 2026)

Molecular mechanisms of ion hydration and gas–water diffusion joint controlled the CO2 hydrate growth - Hu Wenfeng; Sun Xiyue; Cheng Chuanxiao; Wu Xuehong; Zhang Xueling; Wang Fan; Zhu Shiquan; Qi Tian; Xiao Yanqiu; Chen Cong (Fuel, 2026)

Corrigendum to “Synergistic Apoptosis-Ferroptosis: Oxaliplatin loaded amorphous iron oxide nanoparticles for High-efficiency therapy of orthotopic pancreatic cancer and CA19-9 levels decrease” [Chem. Eng. J. 464 (2023) 142690] - Yilong Li; Xinlong Wang; Binbin Ding; Cong He; Can Zhang; Jiating Li; Haonian Wang; Zhibo Li; Gang Wang; Yongwei Wang; Hua Chen; Ping’an Ma; et al. (Chemical Engineering Journal, 2026)

In-situ cultivation and process dynamics of algal-bacterial granular sludge in a continuous-flow self-circulation reactor - Wei-Kang Qi; Yu-Ge Sun; Ming-Ming Zhang; Rui Hu; Yong-Zhen Peng; Cong Wang (Bioresource Technology, 2026)

The Effects of Poplar-Cyperus Esculentus Agroforestry System on Soil Nutrients and Microbial Communities in Northeast China - Wenxu Zhu; Weixi Zhang; Weiwei Gu; Xinyao Cong; Siqi Wu; Zhongyi Pang; Yanhui Peng; Jian Qiu; Zhuo sun; Changjun Ding (Journal of Soil Science and Plant Nutrition, 2026)

Autumnicola aciditolerans sp. nov., a novel member of the genus Autumnicola isolated from tidal flat in Zhoushan - Yang Li; Dong-Yan He; Jia-Wei Gao; Ke Cao; Yun-Fei Cao; Xing-Cheng Wang; Lin Xu; Yan Bai; Can Chen; Cong Sun (Antonie van Leeuwenhoek, 2026)

PEDV nonstructural protein 14 inhibits RIPK3 and RIPK1-mediated PANoptosis - Xingyi Xie; Dengkun Wang; Xueke Sun; Xuechen Li; Mengru Luo; Jiahao Cong; Wenju Yuan; Huihui Huang; Zhaojiang Chen; Yuhang Zhang; Zhengjie Kong; Bo Wan (Veterinary Microbiology, 2026)

High-speed vertical water entry of semi-sealed cylindrical shell with large slenderness ratio - Shengsheng Xia; Yingjie Wei; Cong Wang; Tiezhi Sun; Liu Yang; Yang Xu; Shilei Wu; Baoxiang Wang; Tiantang Duan (Ocean Engineering, 2026)

The carbon footprint of the farming of edible brown alga Sargassum naozhouense - Liwei Sun; Jiali Xie; Cong Xu; Enyi Xie; Chuangye Yang; Hui Zhao (Marine Environmental Research, 2026)

Ultra-high SERS-active nanowires-PTFE composite substrate for trace detection of Aflatoxin B1 in aquaculture water - Liu Wang; Jie Han; Liangyan Sun; Jinru Feng; Xiaohan Lin; Daoliang Li; Cong Wang (Journal of Hazardous Materials, 2026)

Integrated multi-omics profiling of wooden breast reveals energy metabolism dysfunction and RHOA/ROCK pathway activation - Cong Ding; Meijuan Ren; Zhixuan Li; Shiqi Liu; Haoming Sun; Sijia Yu; Yiwei Chen; Xingyu Li; Qiang Niu; Bing Li; Li Li; Xiaojun Yang; et al. (Food Chemistry, 2026)

Network toxicology and multi-omics analyses identify diagnostic genes and elucidate underlying mechanisms of 6PPDQ-induced hepatocellular carcinoma - Xulei Zuo; Xiaoyu Hou; Shiyi Tan; Cong Zhang; Yuxi Zhang; Rongli Sun; Yuepu Pu; Juan Zhang (Environmental Pollution, 2026)

Catalytic hairpin assembly-assisted dual-enhanced SERS satellite nanocomplex for ultrasensitive detection of lipopolysaccharides in injection samples - Chan Huang; Xiuying Li; Xuan Zeng; Lingzhi Chen; Huabin Zhang; Xinjie Guo; Yiqun Chang; Wenshi Huang; Yichu Nie; Tianen Zhou; Jiaqi Yu; Jun Xu; et al. (Chemical Engineering Journal, 2026)

Room-temperature fabricated boron nitride ceramics with superior thermal conductivity - Jin Cheng; Li Li; Naichao Chen; Hongye Wang; Xinwei Xu; Zhan Zeng; Jiufeng Dong; Liang Sun; Yani Lu; Cong Liu; Fei Jin; Hong Wang (Chemical Engineering Journal, 2026)

From bioprocess to market: Optimizing medium-chain carboxylate extraction for application readiness - Yiran Zhang; Aijie Wang; Yilu Sun; Xuening Zhang; Jianfeng Liu; Wen Wang; Cong Huang; Shaoping Fu; Honggang Deng; Yongping Shan; Jiadong Yu; Xufeng Yuan; et al. (Bioresource Technology, 2026)

Nanoparticle-free dualmodal lateral flow immunoassay for sensitive detection of aflatoxin B1 based on “four-in-one” multifunctional nanobody - Tingting Gong; Weili Shen; Kaiyuan Chen; Meng Bi; Cong Liu; Hao Zheng; Wenjia Niu; Yulin Mao; Changli Shao; Longlong Luo; Tieqiang Sun (Analytica Chimica Acta, 2026)

Estimation of surface seawater pH in Hangzhou Bay based on machine learning - Qi Chen; Yuqian Wu; Cong Liu; Shuangyan He; Pei Sun Loh; Yanzhen Gu; Peiliang Li (Acta Oceanologica Sinica, 2026)

A Novel NIR Fluorescent Probe with Large Stokes Shift for the Detection of Hg2+ and its Imaging in Living Cells and Zebrafish - Huan Zhang; Limeng Cong; Cong Sun; Jinwei Zhang; Shuai Guo; Songhua Zhu; Baoze Guo; Junqing Zhou; Youlai Zhang (Journal of Fluorescence, 2026)

3D magnetotelluric imaging of lithospheric magmatic systems in the Yitong Volcanic Area, Northeast China: Implications for fault-zone segmentation and seismic rupture dynamics along the Yilan-Yitong Fault - Cong Cao; Lingqiang Zhao; Yan Zhan; Yanfu Qi; Xiangyu Sun; Xiong Yang; Hongbin Lv; Qingliang Wang; Bowen Hou; Wenwen Qi (Tectonophysics, 2026)

Enhancing carbon fixation in carbide slag-based materials through a dual-process carbon fixation method - Fengge Zhou; Lulu Sun; Shoulei Duan; Quanlin Shi; Guansheng Qi; Cong Zhang (Process Safety and Environmental Protection, 2026)

Linking ENSO diversity to runoff predictability in China using nonhomogeneous hidden Markov model - Jian Sun; Lei Yan; Jinxia Sha; Dan Xu; Fan Lu; Qinghua Luan; Yuan Liu; Boyuan Lu; Cong Jiang; Lihua Xiong (Journal of Hydrology, 2026)

Modulation of reservoir surface wettability by CO2 injection: A molecular simulation perspective - Jingyue Sun; Xi Wang; Zherui Chen; Yue Zhang; Weizhong Li; Cong Chen; Zhehui Jin; Wenfeng Hu; Yongchen Song (Journal of Cleaner Production, 2026)

Decadal soil carbon sequestration under straw management: Relative roles of stable carbon inputs and microbial carbon pump efficacy - Zheng Jiang; Huifeng Sun; Jining Zhang; Liuming Hai; Cong Wang; Xianxian Zhang; Sheng Zhou (Journal of Environmental Management, 2026)

Occurrence of beryllium and its microscale interactions with coexisting phases in beryllium-containing sludge - Xiaobo Min; Lin Yu; Yong Ke; Yunyan Wang; Wenming Zeng; Hui Xu; Yun Li; Cong Peng; Zhumei Sun (Journal of Environmental Sciences, 2026)

Nondestructive assessment of refrigerated quality attributes of kiwifruit via hyperspectral imaging coupled with a point-to-interval prediction model - Sunli Cong; Jun Sun; Lei Shi; Chunxia Dai; Xiaohong Wu; Bing Zhang; Kunshan Yao; Xiao Ge (Food Chemistry, 2026)

Differential associations of PFAS in follicular fluid and serum with reproductive hormones: Insights from a Chinese IVF cohort GIVES - Kun Zhao; Chu Chu; Michael S. Bloom; Jian-Ping Cong; Marjut Roponen; Pasi Jalava; Mo Yang; Wan-Ting He; Yun-Ting Zhang; Ming-Kun Sun; Jing-Wen Huang; Li-Xia Liang; et al. (Environmental Research, 2026)

Smart, tumor-targeted, and responsive intracellular delivery engineering (STRIDE) nanoplatform: co-delivery of siGLI1 and cisplatin prodrug to overcome lung adenocarcinoma chemoresistance - Ge Chen; Mengyang Liu; Yanan Sun; Shifei Zhang; Qingyi Liu; Yuxiang Liang; Kexin Cong; Meng Yan; Zhigan Zhang; Jinjiang Deng; Zongyu Wang; Ziqiang Li; et al. (Chemical Engineering Journal, 2026)

Hydrangea-like NiTi layered double hydroxide-derived balsawood@Ti3C2Tx-based disposable electrode for convenient residue analysis of carbendazim pesticide - Kanru Fu; Zhengri Cong; Xinghao Wang; Haocheng Sun; Yong Zhang (Chemical Engineering Journal, 2026)

CuO2-loaded quaternized chitosan-based composite nanofiber membranes: Immediate contact antibacterial for high-risk public surface engineering - Caiyun Chen; Yufei Tang; Cong Wu; Yani Sun; Bo Zhang; Kang Zhao; Zixiang Wu (Chemical Engineering Journal, 2026)

Joint analysis of GWAS and TILLING reveals the negative role of GLABRA2 in controlling seed oil content in Brassica napus - Zetao Bai; Haibo Sun; Weidong Shi; Cong Zhou; Ming Hu; Meili Xie; Feng Gao; Chaobo Tong; Yueying Liu; Guohua Chai; Shengyi Liu (Theoretical and Applied Genetics, 2026)

Positive and negative responses of AMF community and diazotrophic community to peanut genetic diversity - Yanyan Yu; Miaomiao Li; Cong Wang; Zhongjie Sun; Xiongde Dong; Shijie Han; Junqiang Zheng (Applied Soil Ecology, 2026)

Differential life cycle toxic effects and molecular mechanisms of Di(2-ethylhexyl) phthalate (DEHP) exposure on the female reproductive system - Kangshuai Zhang; Yuxuan Lin; Xiance Sun; Cong Zhang; Haoyuan Deng; Xiaofeng Yao; Ningning Wang; Guang Yang (Toxicology, 2025)

Soil phosphorus availability modulates root exudation under long-term nitrogen fertilization - Zheng Jiang; Cong Wang; Huifeng Sun; Xianxian Zhang; Jining Zhang; Liuming Hai; Sheng Zhou (Soil and Tillage Research, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Hyperspectral imaging combined with a universal hybrid deep network for identifying early chilling injury in kiwifruit across varieties - Sunli Cong; Jun Sun; Lei Shi; Chunxia Dai; Xiaohong Wu; Bing Zhang; Kunshan Yao (Postharvest Biology and Technology, 2025)

Structure-based molecular design of fungicidal β-ketonitrile derivatives with biphenyl moiety as novel succinate dehydrogenase inhibitors - Cong Zhou; Ziye Cao; Li Sun; Na Zhai; Liangliang Cheng; Zheyi Feng; Zhong Li; Xuhong Qian; Jiagao Cheng (Pesticide Biochemistry and Physiology, 2025)

Contact-induced high energy-dissipation array column for vibration suppression of deep sea mining tower - Shubin ji; Li Zou; Zhe Sun; Xueyu Wang; Maoyue Lin; Cong Wang; Yingjie Wei (Ocean Engineering, 2025)

Defective modulation of bio-base metal-organic frameworks for enhanced CO2 adsorption and catalytic conversion - Yiling Xu; Cong Liu; Leyu Nie; Xinru Liu; Kai Xia; Zhaojun Chen; Deshuai Sun (Journal of Environmental Chemical Engineering, 2025)

Ureolysis-driven sulfidogenic precipitation and pH enhancement for robust bioremediation of zinc-laden acid mine drainage - Cong Peng; Zhenyu Zhang; Zhendong Yang; Li Zeng; Huijun Xi; Zhenghua Liu; Huaqun Yin; Delong Meng; Yonghong Liu; I.A. Ibrahim; Hongjuan Sun; Ke Zhang; et al. (Journal of Environmental Chemical Engineering, 2025)

Investigation of hydrate formation and flow characteristics within multiphase transmission pipelines employing a constant pressure visualization loop system - Xi Wang; Kaibang Liu; Shouyi Ma; Linan Guan; Zherui Chen; Yan Qin; Jingyue Sun; Cong Chen (Gas Science and Engineering, 2025)

Separation, characterization, AI screening, and bioactivities of marine bioactive peptides: A review - Yi Cui; Xiaorui Li; Yiran Sun; Yinyin Liu; Weiye Zhang; Yifan Jiang; Yunxiang Zhou; Jinshan Liu; Bangyu Gong; Yuzhen Wu; Shengfu Li; Linwu Zhuang; et al. (Food Chemistry, 2025)

Single-cell transcriptomic profiling of goat milk somatic cells highlights immune heterogeneity and epithelial cell-related networks - Ren Tao; Cong He; Liu Yaolong; Liu Chengli; Ruan Pengcheng; Wang Zixuan; Long Hao-yuan; Simone Ceccobelli; Hu Pengfei; Zeng Yan; Han Yanguo; Sun Yawang; et al. (Food Bioscience, 2025)

Effect of solvent recrystallization on the purification of crude phytosterols derived from corn oil deodorizer distillate - Zhili Shen; Shaohua Liang; Cong Sun; Pengcheng Meng; Ruinan Yang (Food and Bioproducts Processing, 2025)

Atomic-scale regulation of Bi2Te3 nanopores via in-situ electron beam irradiation for nanofabrication - Yuting Shen; Yu Tao; Tao Xu; Yuwei Xiong; Kuibo Yin; Yilong Zhou; Shan Cong; Litao Sun (Chemical Engineering Journal, 2025)

Ultra-stable Pd/NaInY catalyst with atom-dispersed indium modification of NaY zeolite for CO direct esterification to dimethyl carbonate - Yi-Jing Feng; Xiao-Yuan Tan; Jian Lin; Wen-Qiang Zou; Jing Sun; Zhong-Ning Xu; Guo-Cong Guo (Chemical Engineering Journal, 2025)

Enhanced Carrier Collection by Controlling Element Distribution in Kesterite Solar Cells through Se&SnS2 Co-annealing process - Yali Sun; Zihang Liu; Jiahui Ma; Xiao Liu; Ridong Cong; Qing Zhou; Wanlei Dai; Xiaoyun Teng; Chao Gao; Wei Yu; Dongliang Ding (Chemical Engineering Journal, 2025)

Rationally engineered metal-organic framework membrane structure for effective Mg2+/Li+ separation - Yijing Zhang; Si Sun; Ming Wang; Xuan Luo; Zhehua Jia; Jiaoyu Peng; Shenzhen Cong; Tao He; Huan Pang (Chemical Engineering Journal, 2025)

Identification of a missing Pictet–Spenglerase in the Gloriosa superba L. colchicine biosynthesis pathway - Jingyi Sun; Huapeng Sun; Zhiqiang Xiong; Xuefei Jiang; Xiaona Fu; Hanqing Cong; Fei Qiao (Molecular Biology Reports, 2025)

Proto-oncogene DEK binds to pre-mRNAs and regulates the alternative splicing of Hippo signaling genes in HeLa cells - Dongbo Liu; Wei Sun; Jing Han; Cong Wang; Dong Chen; Yunfei Wu; Yongjie Chang; Bin Yang (Molecular Genetics and Genomics, 2025)

Comprehensive profiling of Bcl-2-associated athanogene (BAG) genes and their genetic potential role under cold stress in Cotton - Aamir Ali Abro; Cong Sun; Mubashir Abbas; Qiankun Liu; Zheng Jie; Yanchao Xu; Yuqing Hou; Zhongli Zhou; Rashid Iqbal; Fang Liu; Xiaoyan Cai (Functional & Integrative Genomics, 2025)

Decreased nematode energy flow triggers soil microbial necromass loss in degraded grasslands - Yang Hu; Mengfei Cong; Tianle Kou; Han Yan; Yuanbin Jia; Xinya Sun; Haolin Zhang; Bicheng Zhang; Yubin Wang; Hongtao Jia; Shaoshan An (Applied Soil Ecology, 2025)

Complete genome sequence and molecular characterization of a novel potyvirus (sweet potato virus H) infecting sweet potato - Wei Tang; Jukui Ma; Yanping Tian; Xiao Yin; Jingwei Chen; Dongjing Yang; Fangyuan Gao; Zhao Liang; Cong Tong; Chengling Zhang; Houjun Sun (Archives of Virology, 2025)

Seasonal water level fluctuations regulate the source, distribution, and risk of antibiotics in the largest floodplain-lake in China - Xiaolong Huang; Cong Wang; Yiting Chen; Meng Zhang; Muhammad Zaffar Hashmi; Tingting Sun; Borui Zou; Yuanyan Zhang; Jingjing Lin; Zhi Wang (Water Research, 2025)

Bisphenol A exposure promotes proliferation and invasion capabilities of bladder cancer cells: Insights from gene expression and pathway analysis - Bo Cong; He Liu; Minghui Sun; Dichao Hu; Tongjie Li; Wenbo Wu; Haitao Liu (Toxicology Letters, 2025)

Theoretical and experimental study on the performance of the hydraulic power unit employed on full ocean depth manned submersible - Zhida Chen; Tianhao Li; Linglong Li; Jincang Liao; Cong Ye; Defa Wu; Shuai Liu; Yinshui Liu; Yunxiang Ma; Lang Gu; Gang Sun (Ocean Engineering, 2025)

Glass bead-supported Eu3+/Bi2WO6 packed-bed reactor for efficient photocatalytic removal of tetracycline - Huadong Liu; Jingliang Cheng; Xiaoyu Sun; Zhonghao Zhao; Cong Zhang (Journal of Water Process Engineering, 2025)

Rapid formation of acetaldehyde and its influence on ozone formation in a petrochemical industrialized region - Can Cui; Yujiao Zhu; Xiaoyu Yan; Xin Zhang; Min Zhao; Jiangshan Mu; Xuelian Zhong; Jinghao Tang; Yanqiu Nie; Cong An; Wanghui Chu; Yue Sun; et al. (Journal of Environmental Sciences, 2025)

A novel angiotensin-converting enzyme (ACE) inhibitory peptide from Alaska pollock (Gadus chalcogrammus) Skin: Preparation, screening, in vitro activity evaluation, and network pharmacology analysis - Linwu Zhuang; Yifan Jiang; Shuai Li; Yi Cui; Weiye Zhang; Dingfei Yan; Yiran Sun; Yunxiang Zhou; Jinshan Liu; Shengfu Li; Cong Wei; Junjie Zhang (Food Bioscience, 2025)

Lattice-matching formed covalent heterointerfaces based on epitaxial growth of ZnIn2S4 nanosheet on Cu2S nanobox to accelerate charge separation for effective antibiotic degradation cooperated with hexavalent chromium reduction - Sainan Sun; Jiahong Pan; Jialu Pan; Xinyi Shen; Jiahui Liu; Ziyi Guo; Chenyi Wang; Yanqing Cong; Shi-Wen Lv (Environmental Research, 2025)

Distribution patterns and source contributions of emerging contaminants in urban wastewater systems: from pumping stations to wastewater treatment plants - Yujin Yuan; Qiaoting Zeng; Meixian Cao; Wanqiang Cai; Cong Ma; Anyi Hu; Qian Sun (Environmental Pollution, 2025)

Volatilization behavior of thallium and valuable metals (lead, zinc and cadmium) in thallium-containing waste during thermal treatment - Wanlan Wu; Yong Ke; Yunyan Wang; Xikai Wang; Xiaolin Quan; Cong Peng; Yun Li; Zhumei Sun; Qi Liao; Xiaobo Min (Chemical Engineering Journal, 2025)

Supramolecular carboxylic acid complex elastomer for CsPbI3-xBrx-based perovskite solar cells with high efficiency and excellent stability - Cong Shen; Peixia Yang; Lijie Sun; Guanying Chen (Chemical Engineering Journal, 2025)

Preparation, characterization, fermentation properties of pectin with specific structures, and the analysis of microbial enzymes and genes involved in their degradation - Weichao Cao; Yaxian Liu; Nuo Chen; Yuhang Wang; Yiasmin Mst Nushrat; Shouzheng Qiao; Lisha Tang; Zhen Sun; Rongrong Lu; Cong Liu; Xiao Hua (Carbohydrate Polymers, 2025)

Alkali-induced Dendrobium officinale polysaccharide-hemp seed protein gels: Insight into structure, molecular interaction mechanisms, and potential as dysphagia food - Tingting Ding; Bei Fan; Xin Xu; Caiyue Chen; Cong Lu; Jiameng Liu; Fengzhong Wang; Jing Sun (Carbohydrate Polymers, 2025)

A deep learning-based hybrid model for improved SST prediction in the tropical Pacific Ocean - Yuanzhe Ma; Bowen Xie; Zhongkun Feng; Guimin Sun; Cong Zhang; Shuguo Yang (Journal of Oceanology and Limnology, 2025)

Disulfide bond-driven nanoassembly of lipophilic epirubicin prodrugs for breast cancer therapy - Haimeng Yuan; Yao Chen; Yuting Hu; Yanxin Li; Hongyuan Zhang; Shenwu Zhang; Qin Chen; Wenhu Zhou; Jin Sun; Zhonggui He; Yuequan Wang; Cong Luo (Journal of Pharmaceutical Investigation, 2025)

Sensitive colorimetric assay for the detection of aflatoxin B1 via target-induced generation of multivalent DNA nanowires accelerates the catalytic hairpin assembly reaction - Shihong Zhang; Yingying Sun; Xingyu Liu; Cong Chen; Yuhan Ma; Dian Yu; Wenjie Liu; Jianna Yu; Guoxing Jing; Wen Liu; Wenshan Li (Analytica Chimica Acta, 2025)

Transcriptome analysis provides insights into the regulatory role of phytohormone in second flowering of pear - Dongrui Liu; Cong Shi; Xinkang Wan; Jie Ding; Xuepeng Sun; Meisong Dai; Kai Xu; Xiaolong Li (Plant Science, 2025)

Catalytic selective production of mono-aromatics from low-density polyethylene via HNO3-induced surface oxidation of activated carbon - Xiaona Lin; Xiaojie Zhuansun; Zhen Sun; Hongtao Li; Hongbin Cong (Journal of Environmental Chemical Engineering, 2025)

Research on the synthesis and application of photo controlled intelligent porphyrin-based covalent organic frameworks linked by azobenzene - Nazhen Zhang; Songyang Sun; Yue Zhong; Mingzhong Li; Yongjie Lin; Yanwei Li; Cong Liu; Yanhui Li (Journal of Environmental Chemical Engineering, 2025)

Enhanced moisture tolerance and toluene oxidation activity of δ-MnO2 catalysts by Sn doping: Phase transition and surface protection - Yiming Li; Mengxia Xu; Rui Liu; Shuibo Wang; Taotao Sun; Zijun Yan; Cong Wan; Hongbo Yu; Haocheng Li; Haotian Li; Xudong Zhao; Kaijie Li; et al. (Fuel, 2025)

A small amount of Pd promotes CO2 adsorption and reduces carbon deposition to double the stability of NiFePd/MgAlO catalyst for plasma-assisted dry reforming reaction - Lian-He Zhao; Shu-Juan Lin; Jian-Feng Diao; Ming-Sheng Wang; Jing Sun; Zhong-Ning Xu; Guo-Cong Guo (Chemical Engineering Journal, 2025)

Hydrogen plasma-induced uniform grain boundary engineering in Cu(In, Ga)Se2 thin films for high efficiency large area solar panels - Zeran Gao; Jiaxin Guo; Zihan Guo; Shanshan Tian; Wanlei Dai; Ridong Cong; Yali Sun; Chao Gao; Xinzhan Wang; Wei Yu (Chemical Engineering Journal, 2025)

Branched ligand-functionalized immuno-evasive PEGylation (BLIP) platform: Breaking through accelerated blood clearance and chemoresistance barriers with dual-targeting RNAi-chemotherapy synergy - Mengyang Liu; Ruijuan Xing; Ge Chen; Yuxiang Liang; Lu Huang; Yumeng Xi; Yue Li; Shifei Zhang; Yanan Sun; Yupin Song; Jintao Hao; Kexin Cong; et al. (Chemical Engineering Journal, 2025)

An experimental study on the montmorillonite illitization process in Na-Gaomiaozi bentonite for Chinese EBS - Cong Liu; Yong-Gui Chen; Zhao Sun (Bulletin of Engineering Geology and the Environment, 2025)

Genetic Structure in a Trans‐Oceanic Hot Vent Mussel Reveals Four Metapopulations With Implications for Conservation - Qin Mao; Chong Chen; Jin Sun; Jin Liang; Yanan Sun; Yejian Wang; Cong Zeng; Mingting Li; Shuaicheng Xin; Dongsheng Zhang; Yadong Zhou (Journal of Biogeography, 2025)
Aim Genetic diversity and connectivity are crucial to informing the conservation strategy for deep‐sea organisms, especially those threatened by deep‐sea mining. The vent mussel Bathymodiolus septemdierum has an extraordinary trans‐oceanic distribution range across the Indo‐West Pacific including numerous sites eyed for exploitation. Here, we aimed to assess the connectivity of B. septemdierum across its entire range, for the first time. Location Hydrothermal vent fields on the Carlsberg Ridge (CR), Central Indian Ridge (CIR), Southwest Indian Ridge (SWIR), as well as those in the Mariana Trough and the Southwest Pacific. Taxon Bathymodiolus septemdierum Methods Combining new and published data, we studied the genetic structure, historical demography and gene flow of B. septemdierum using three mitochondrial and two nuclear genes from a total of 444 individuals across 16 vent fields. Results Bathymodiolus septemdierum populations are structured with four regional metapopulations including (1) the whole Western Pacific, (2) CR in the northern Indian Ocean, (3) vents on the SWIR and southern CIR (CIR + SWIR) and (4) Onnuri field on the northern CIR. IMa3 analysis shows divergence first occurred between WP and the Indian Ocean, and then between CR and CIR + SWIR metapopulations. The gene flow towards CR from both CIR + SWIR and WP is higher than the reverse directions, while Onnuri received exceptionally high migrations from both CIR + SWIR and CR metapopulations. Main Conclusions Our findings support a large‐scale dispersal scenario where larvae are carried westwards from the Pacific Ocean into the western Indian Ocean through Indonesia, and then separated into northern and southern Indian Ocean clades. The CR acts as an isolated gene pool for this species among others, and the Onnuri field serves as a key transition zone in the Indian Ocean, and we urge for the prioritised protection of these vents currently targeted by deep‐sea mining.

Autonomous Inspection Strategies and Simulation for Large Aquaculture Net Cages Based on Deep Visual Perception - Keru Cai; Cong Li; Qian Sun; Yijun Liu; Hongyi Ye; Yuwang Xu (Journal of Marine Science and Engineering, 2025)
In China, a single large deep-sea net cage can raise nearly one million fish. If the fish net is damaged and the fish escape, it can lead to significant economic losses and ecological damage. Therefore, the inspection and maintenance of deep-sea aquaculture net cages are very important. Currently, the inspection of fish nets relies primarily on manual remote control, and underwater positioning often uses ultra-short baseline systems, which depend on specialized personnel and have high costs. This paper proposes an autonomous inspection strategy for large aquaculture net cages based on deep visual perception. It utilizes stereo cameras to identify the relative distance and attitude angles between the robot and the sides of fish net as well as the fish net ahead. A PID method is employed to control the underwater autonomous net patrol robot to conduct operations with fixed depth, fixed distance, and attitude holding around the net. By integrating the Gazebo physical simulation platform with the ROS (Robot Operating System), a simulation environment for the underwater autonomous net patrol robot was constructed. The study investigated the inspection performance of the robot under different speed conditions, both in still water and considering current conditions. By comparing the actual operating trajectory with the expected trajectory, the proposed autonomous inspection strategy was validated. Moreover, the study examined the operation state under sudden disturbance forces, where the robot deviated six meters from the net cage and rotated 70 degrees. The simulation results indicate that under this control strategy, the robot can quickly recover its desired pose and continue executing the inspection task.

Characterization of thermal runaway properties and gas production characteristics of aging batteries - Yuyang Shao; Beihua Cong; Jianghong Liu; Sumiao Yin; Mingming Qiu; Boyu Sun (Process Safety and Environmental Protection, 2025)

S-domain receptor-like protein kinase OsGRSK1 participates in regulating plant height and grain size via gibberellin pathway in rice - Cong Chen; Xin Hu; Haitao Du; Quanshi Dong; Yihan Fu; Ying Li; Fanqing Duanmu; Hongzheng Sun; Junzhou Li; Changqing Du (Plant Science, 2025)

Ni-doped CdO/CdSe in-situ heterojunctions: Tunable composition engineering for low-concentration formaldehyde detection - Yunjiang Zhang; Yan Zhang; Junjun Sun; Jianliang Cao; Cong Qin; Yan Wang (Journal of Hazardous Materials, 2025)

Effect of pulsation frequencies on the fracture characteristics of CO2 foam fractured coal: An experimental study - Yangfeng Zheng; Cheng Zhai; Aikun Chen; Hexiang Xu; Xinyu Zhu; Shuxun Sang; Meng Wang; Shiqi Liu; Xu Yu; Jizhao Xu; Yong Sun; Yuzhou Cong; et al. (Gas Science and Engineering, 2025)

Multimetallic intra-nanogap nanozyme-mediated lateral flow immunoassay for ultrasensitive and multimode detection of K. pneumonia in clinical samples - Weixia Zhi; Xinjie Guo; Yichu Nie; Lu Nie; Tingting He; Li Dai; Jing Xu; Xiangxin Zong; Jun Xu; Huaihong Cai; Yong Tang; Yanguang Cong; et al. (Chemical Engineering Journal, 2025)

Aurantibrevibacter litoralis gen. nov. sp. nov. a Novel Member in the Family Flavobacteriaceae Isolated from Sediment of Tidal Flat Located in Ningbo, China - Yun-Fei Cao; Dong-Yan He; Yu-Ruo Wang; Ke Cao; Yang Li; Jia-Wei Gao; Xing-Cheng Wang; Lin Xu; Cong Sun; Xiao-Yun Yu (Current Microbiology, 2025)

Novel Application of Ultrashort Pulses for Underwater Positioning in Marine Engineering - Kebang Lu; Minglei Guan; Zheng Cong; Dejin Zhang; Jialong Sun; Haigang Zhang; Keqing Yang (Journal of Marine Science and Engineering, 2025)
Noise interference and multipath effects in complex marine environments seriously constrain the performance of hydroacoustic positioning systems. Traditional millisecond-level signal application and processing methods are widely used in existing research; however, it is difficult to meet the requirements of centimeter-level positioning accuracy in marine engineering. To address this problem, this study proposes a hydroacoustic positioning method based on a short baseline system for the cooperative reception of multi-channel signals. The method adopts ultra-short pulse signals with microsecond pulse width, and significantly improves the system signal-to-noise ratio and anti-interference capability through multi-channel signal alignment and coherent superposition techniques; meanwhile, a joint energy gradient-phase detection algorithm is designed, which solves the instability problem of the traditional cross-correlation algorithm in the detection of ultra-short pulse signals through the identification of signal stability intervals and accurate phase estimation. Simulation verification shows that the 8-hydrophone × 4-channel configuration can achieve 36.06% signal-to-noise gain under harsh environmental conditions (−10 dB), and the performance of the joint energy gradient-phase detection algorithm is improved by about 19.1% compared with the traditional method in an integrated manner. Marine tests further validate the engineering practicability of the method, with an average SNR gain of 2.27 dB achieved for multi-channel signal reception, and the TDOA estimation stability of the new algorithm is up to 32.0% higher than that of the conventional method, which highlights the significant advantages of the proposed method in complex marine environments. The results show that the proposed method can effectively mitigate the noise interference and multipath effects in complex marine environments, significantly improve the accuracy and stability of hydroacoustic positioning, and provide reliable technical support for centimeter-level accuracy applications in marine engineering.

Paeoniflorin protected UVA-exposed skin fibroblasts from caspase-3/GSDME mediated pyroptosis - Dongxin Shi; Haitao Chu; Yijun Sun; Hailun He; Wenyue Huang; Hua Pan; Cong Ma; Shulan Yao; Meihui Shi; Hexiao Wang; Yan Wu (Journal of Photochemistry and Photobiology B: Biology, 2025)

Impacts of sex and gestation on bioaccumulation and transfer of per-and polyfluoroalkyl substances in loaches - Cong Wang; Yonglong Lu; Bin Sun; Ruoyu Mao; Meng Zhang; Shuai Song; Mingzhao Yu; Jixin Zhao (Environmental Research, 2025)

Structural engineering and 3D printing of highly stretchable strain sensors for smart wearable systems - Meng Sun; Tianyi Lu; Yuxuan Zhou; Yuxian Chen; Weilong Tu; Cong Zhang; Zhonghua Ni; Xiao Li; Tao Hu (Chemical Engineering Journal, 2025)

Drought Stress Alleviation in Paeoniae Radix Rubra with Three Bacillus Strains and Associated Metabolic Changes - Aowei Xu; Shixin Guan; Shilong Wang; Ayimukezi Maimaitizunong; Fuxin Cong; Dairu Jiang; Yanxin Gu; Lijie Xu; Xiaomei Sun (Journal of Plant Growth Regulation, 2025)

Subchannel analysis of post-dryout flow and heat transfer in a tight-lattice fuel assembly - Shuo Chen; Junsen Fu; Quanyi Gao; Yubo Sun; Yao Xiao; Tenglong Cong; Hanyang Gu (Annals of Nuclear Energy, 2025)

Turning point of direct N2O emissions in China’s croplands dominated by reduced fertilizer usage since 2015 - Zimeng Li; Songbai Hong; Ziyuan Sun; Nan Cong; Yanzi Yan; Fa Li; Yuanyi Gao; Yan Sun; Yilin Chen; Yue Chen; Xuhui Wang; Shilong Piao (Agriculture, Ecosystems & Environment, 2025)

Knowledge-driven inverse diffusion prediction algorithm for flexible job shop scheduling problem considering transportation resources and multiple breakdowns - Cong Wang; Lixin Wei; Hao Sun; Ziyu Hu (Swarm and Evolutionary Computation, 2025)

Diquat exposure causes brainstem demyelination by upregulating the mitochondrial calcium uniporter - Jie Zhou; Yingli Yang; Jiacheng Tian; Cong Liu; Jiafei Chen; Mei Yang; Mengran Zhang; Yu Duan; Tian Zhang; Yapei Sun; Qin Yu; Zhiqin Xia; et al. (Journal of Hazardous Materials, 2025)

Fluorescence hyperspectral imaging for detection of selenium content in lettuce leaves under cadmium-free and cadmium environments - Lei Shi; Jun Sun; Sunli Cong; Xingyu Ji; KunShan Yao; Bing Zhang; Xin Zhou (Food Chemistry, 2025)

Nondestructive detection of cadmium content in oilseed rape leaves under different silicon environments using deep transfer learning and Vis-NIR hyperspectral imaging - Xin Zhou; Yang Liu; Chunjiang Zhao; Jun Sun; Lei Shi; Sunli Cong (Food Chemistry, 2025)

Corrigendum to “Sunlight-driven peroxydisulfate activation by floating Ca/Fe-TiO2@polystyrene spheres for efficient moxifloxacin degradation in circulated water: Critical roles of Ca/Fe bimetallic ions crosslinking on the stability of catalyst structure and electron transfer of system” [Chem. Eng. J. 513 (2025) 162750, https://doi.org/10.1016/j.cej.2025.162750. /CEJ-D-25-03061] - Zisong Xu; Hanbing Zhang; Jingyi Zhou; Ting Huang; Jing Sun; Cong Chang; Zheng Chen; Kun Liu; Zhangfa Tong (Chemical Engineering Journal, 2025)

Contriving molecular configuration to realize a bidirectionally stable quasi-solid polymer electrolyte for high-voltage Li metal batteries - Silin Chen; Shunchao Ma; Yu Zhang; Yanan Li; Yutong Yang; Shuainan Wang; Jianli Cao; Siqi Fan; Liqun Sun; Yulong Liu; Lina Cong; Haiming Xie (Chemical Engineering Journal, 2025)

Characterization and function analysis of a glucose-regulated protein 78 gene in Neocaridina denticulata sinensis - Dandan Feng; Yujie Liu; Cong Wang; Xiao Li; Huimin Li; Yuying Sun; Jiquan Zhang (Journal of Oceanology and Limnology, 2025)

Reaction performance of Non-Thermal plasma induced CO2 reforming of CH4 for landfill gas treatment - Yiping Sun; Kai Zhang; Nana Qi; Cong Chao; Xianchun Li; Dongke Zhang (Waste Management, 2025)

Aqueous production of sulfur-containing aerosols from nitroaromatic compounds and SO2 in wintertime urban haze - Ning Yang; Junfeng Wang; Daniel J. Jacob; Jianhuai Ye; Ming Sheng; Mutong Niu; Yiming Qin; Xinlei Ge; Yele Sun; Zifa Wang; Yuhang Wang; Fengchang Wu; et al. (Science Bulletin, 2025)

Metabolomic analysis reveals contrasting effects of PFOS and PFAS on cyanobacterial bloom and metabolic pathways in eutrophic water - Jieming Liao; Luyao Huang; Yinyue Liu; Bin Sun; Kunyu Zhang; Cong Wang; Haojie Lei; Zhiwei Cao; Yonglong Lu (Environmental Pollution, 2025)

Sunlight-driven peroxydisulfate activation by floating Ca/Fe-TiO2@polystyrene spheres for efficient moxifloxacin degradation in circulated water: Critical roles of Ca/Fe bimetallic ions crosslinking on the stability of catalyst structure and electron transfer of system - Zisong Xu; Hanbing Zhang; Jingyi Zhou; Ting Huang; Jing Sun; Cong Chang; Zheng Chen; Kun Liu; Zhangfa Tong (Chemical Engineering Journal, 2025)

Corrigendum to “A chitosan derivative-crosslinked hydrogel with controllable release of polydeoxyribonucleotides for wound treatment” [Carbohydrate Polymers 300 (2023) 120298] - Yanzhen Sun; Xiaodong Jing; Yang Liu; Bing Yu; Hao Hu; Hailin Cong; Youqing Shen (Carbohydrate Polymers, 2025)

MTMR7 attenuates the proliferation and migration of pulmonary arterial smooth muscle cells in pulmonary hypertension by suppressing ERK/STAT3 signaling - Jia Wang; Bing Xuan; Baomei Song; Ting Wang; Cong Lan; Wei Guo; Yongjian Yang; Xiongshan Sun (Molecular and Cellular Biochemistry, 2025)

Enhanced hydrological disturbance and atmospheric pollution on an ombrotrophic peatland (Greater Khingan Mountains, Northeast China) since 1950s inferred from diatom records - Dongxue Han; Yang Sun; Jinxin Cong; Guoping Wang; Chuanyu Gao (Anthropocene, 2025)

Mass deposition of microbes from wildfire smoke to the sea surface microlayer - Siyao Yue; Yafang Cheng; Lishan Zheng; Senchao Lai; Shan Wang; Tianli Song; Linjie Li; Ping Li; Jialei Zhu; Meng Li; Lianfang Wei; Chaoqun Ma; et al. (Limnology and Oceanography, 2025)
Microbes in the sea surface microlayer (SML) are key to connecting the ocean and the atmosphere, affecting the exchange of matter, momentum, and heat at the interface. However, their sources have never been quantified systematically. Seawater has long been deemed their major source, whereas atmospheric deposition is regarded as trivial or merely providing additional nutrients. Here, combining atmospheric observations and quantitative budget analyses, we show that during the Indonesian peatland wildfire events the smoke can directly deposit abundant microbes into the SML, which can be comparable to the estimated supply from seawater and potentially diversify the microbial community of the SML. This land–air–ocean interaction is relevant for global climate, as it may induce previously unknown effects on the air–sea interactions, especially in an increasingly warming future with more intensifying wildfires.

CYP321F3 mediates metabolic resistance to methoxyfenozide in rice stem borer, Chilo suppressalis - Fang-Rui Guo; Shu-Chao Wang; Yan Liu; Shuai Wang; Jing-Mei Huang; Hao Sun; Lin-Feng He; Yuan Xie; Song-Tao Qiao; Feng-Xia Yang; Chris Bass; Cong-Fen Gao; et al. (Pesticide Biochemistry and Physiology, 2025)

Elucidation and de novo reconstitution of glyceollin biosynthesis - Yunlong Sun; Cong Chen; Chao Lin; Hao Zhang; Jiazhang Lian; Benke Hong (Molecular Plant, 2025)

Exergoeconomic analysis and machine learning-based optimization for a near-zero CO2 emission multi-generation system with freshwater production - Wenxing Liang; Yanxia Sun; Cong Han; Jinwen Yang; Fanhua Rong; Jitian Han (Desalination, 2025)

Hollow-whisker modified calcium phosphate loaded with deferoxamine to promote osteoporotic bone regeneration by acting HIF-1α signaling pathway - Linyun Tan; Wacili Da; Cong Feng; Yitian Wang; Xin Hu; Guifeng Du; Hao Wang; Minghao Sun; Yuanrui Luo; Jingyang Li; Xiangfeng Li; Li Min; et al. (Chemical Engineering Journal, 2025)

Low-severity fire promote carbon emissions in permafrost peatlands of the Great Khingan Mountains, Northeast China - Guangxin Li; Long Sun; Shengzhen Ji; Xiao Li; Jinxin Cong; Dongxue Han; Guoping Wang; Chuanyu Gao (CATENA, 2025)

Impact of irrigation strategies on methane emission and absorption characteristics at different interfaces in rice field systems - Cong Wang; Lei Liu; Huifeng Sun; Xianxian Zhang; Jining Zhang; Zheng Jiang; Sheng Zhou (Journal of Soils and Sediments, 2025)

Nutritional quality of interspecific backcross between hybrids of Crassostrea gigas×C. angulata and their two parental species - Chenchen Wei; Luping Wang; Xinfeng Sun; Wei Wang; Guofan Zhang; Li Li; Rihao Cong (Journal of Oceanology and Limnology, 2025)

Comprehensive analysis of non-coding RNAs in the ovaries of high and low egg production hens - Jintang Luo; Tiantian Sun; Siyi Jiang; Zhuliang Yang; Cong Xiao; Jixian Deng; Biyan Zhou; Xiurong Yang (Animal Reproduction Science, 2025)

Anti-ferroptosis effects of undescribed abietane diterpenoids from Prunella vulgaris subsp . hispida (Benth.) Hultén - Heng-Li Yan; Xiao-Qiao Yang; Han-Fei Liu; Fen-Cong Pan; Jin-Yu Li; Wei-Dong Pan; Ni Zhang; Hua-Yong Lou; Chao Sun (Natural Product Research, 2025)

Dynamics of proximate composition, fatty acid profile and transcriptome response to low-temperature stress in muscle tissues of spotted sea bass (Lateolabrax maculatus) - Cong Liu; Yuan Zheng; Haishen Wen; Chong Zhang; Yonghang Zhang; Lingyu Wang; Donglei Sun; Kaiqiang Zhang; Xin Qi; Yun Xia; Yun Li (Aquaculture, 2025)

TCDD inhibits the proliferation of C17.2 cells through the activation of the c-Cbl/β-catenin signaling pathway - Yewen Cong; Yue Wu; Yue Liu; Yongjun Ai; Xiping Wang; Chunxi Wei; Haoyu Ding; Guangfei Xu; Wenxing Sun (Toxicology in Vitro, 2025)

Numerical study of relationships between flows and structural characteristics of the rotor in a rim-driven hubless thruster using a strongly-coupling FSI algorithm - Chun Yang; Hua-Dong Yao; Cong Sun; Chao Wang; Chunyu Guo; Jianfeng Lin (Ocean Engineering, 2025)

Metal covalent organic frameworks-based laccase-like nanozyme for oxidative degradation and identification of phenolic pollutants - Jin Liu; Cong Hu; Xiaoyan Meng; Ying Sun; Bo Zhao; Zian Lin (Journal of Hazardous Materials, 2025)

Lipidomic characterization of polar and non-polar lipids in egg yolk and their anti-inflammatory and analgesic activities in zebrafish - Li Wang; Cong Yin; Juanjuan Sun; Wei Li; Xiaoyan Zou; Miaojuan Zheng; Xiangheng Zeng; Haishan Zhao; Weihuan Huang; Haiyan Tian (Food Chemistry, 2025)

A self-encapsulation hollow structure design for high-capacity and fast-charging sodium-ion batteries at high-temperature - Yifan Zheng; Zhi Zhang; Cong Liu; Huanyi Liao; Zhongxi Li; Yumeng Jiang; Yixin Hou; Li Sun; Yihua Gao (Chemical Engineering Journal, 2025)

Monolithic and effective kinetic promoter formed by immobilizing MWCNTs on cellulose for efficient hydrate-based gas storage - Shuai Wang; Huilian Sun; Zhen Li; Changrui Shi; Lunxiang Zhang; Mingjun Yang; Yanghui Li; Cong Chen; Yongchen Song; Zheng Ling (Chemical Engineering Journal, 2025)

Regulating the growth mechanism of kesterite thin films with single-target selenium-free annealing by introducing a suitable buried buffer layer at the bottom - Qing Zhou; Yijia Cong; Tingchun Wu; Hao Li; Junhui Hei; Xinzhan Wang; Xiaobing Yan; Yali Sun; Chao Gao; Wei Yu (Chemical Engineering Journal, 2025)

Effects of conservation tillage practices on rice yields and greenhouse gas emissions: Results from a 10-year in situ experiment - Cong Wang; Huifeng Sun; Xianxian Zhang; Jining Zhang; Zheng Jiang; Sheng Zhou (Agriculture, Ecosystems & Environment, 2025)

Autonomous collaborative observation method for time-sensitive moving target tracking by satellite swarms - Yiqin Cong; Xiaohan Mei; Shengxin Sun; Tianxi Liu; Gongshun Guan; Cheng Wei (Advances in Space Research, 2025)

Characterization of CYP3A genes and the impact of letrozole on gonadal development in Apostichopus japonicus - Lingnan Kong; Abudula Abulizi; Jingjing Cong; Weihan Meng; Yaqing Chang; Zhihui Sun (Aquaculture International, 2025)

Proteomic Profiling and Therapeutic Targeting of Oxidative Stress in Autoimmune Encephalitis - Fan Zhang; Cong Zhang; Wei Sun; Shuhua Xie; Pengcheng Wu; Guoyong Zeng; Xianghong Liu (Journal of Molecular Neuroscience, 2025)

Polysaccharide metabolic pattern of Cytophagales and Flavobacteriales: a comprehensive genomics approach - Kuo-Jian Ma; Yong-Lian Ye; Yu-Kang Li; Ge-Yi Fu; Yue-Hong Wu; Cong Sun; Xue-Wei Xu (Frontiers in Marine Science, 2025)
The complete metabolism of carbohydrates, as the most abundant and structurally diverse organic matter on earth, requires the involvement of different carbohydrate-active enzymes (CAZymes). Flavobacteriales and Cytophagales are two groups whose members specialize in polysaccharide metabolism, but research on their polysaccharide metabolic patterns based on the overall CAZymes is scarce. In this study, we analyzed 702 filtered genomes of Flavobacteriales and Cytophagales and obtained 100,445 CAZymes. According to their taxonomic status and living environment, we explored the impact of taxonomic status, isolation source, and environmental condition on their potential polysaccharide metabolic patterns. The results indicated significant differences in the CAZyme composition among different taxonomic statuses or environments. Compared with the Flavobacteriales genomes, the genomes of Cytophagales possess more abundant and diverse CAZymes, but have fewer unique CAZyme families. Genomes from different families vary greatly in terms of CAZyme family diversity and composition, but relatively small divergences were found from families in the same order. Furthermore, our findings indicated that genomes from the marine and tidal flat environments share more similarities in CAZyme family composition and diversity compared with the terrestrial genomes. Extreme environments greatly constrain the types of CAZyme families present, and certain CAZyme families are significantly lower than those in normal environments. Although significant differences were found among genomes from both different taxonomic statuses and environments, the dimensionality reduction and the clustering analysis based on CAZyme composition indicated that evolutionary status is the main factor influencing the polysaccharide metabolic patterns of these strains. The correlations among CAZyme families indicated that the majority of these families are synergistically involved in polysaccharide metabolism. This study provides a comprehensive profile of the CAZymes in Flavobacteriales and Cytophagales, highlighting the role of evolutionary status in shaping the polysaccharide metabolic patterns and the prevalence of synergism among CAZyme families. These findings have implications for understanding microbial carbohydrate metabolism in different environments.

Deciphering the genetic basis and genomic prediction of heat tolerance trait from whole-genome resequencing in spotted sea bass (Lateolabrax maculatus) - Cong Liu; Haishen Wen; Chong Zhang; Yonghang Zhang; Lingyu Wang; Donglei Sun; Mengqun Liu; Yani Dong; Pengyu Li; Hao Li; Kaiqiang Zhang; Xin Qi; et al. (Aquaculture, 2025)

Future projections of the rainfall intensity-duration-frequency curves in Beijing-Tianjin-Hebei urban agglomeration based on NEX-GDDP CMIP6 simulations - Lidong Song; Lei Yan; Fuxin Chai; Fan Lu; Jiaqi Zhai; Qinghua Luan; Qiumei Ma; Cong Jiang; Mengjie Zhang; Jian Sun (Sustainable Cities and Society, 2025)

Nonlinear dynamic analysis of a 3D land-fixed oscillating water column wave energy converter - Dezhi Ning; Yawei Sun; Rongquan Wang; Peiwen Cong (Ocean Engineering, 2025)

Mussel-inspired stable and magnetically recyclable Fenton-like catalyst: Preventing iron leaching and accelerating contaminant enrichment via polydopamine modification - Guihua Wang; Bin Peng; Xianhu Long; Xuehui Sun; Yipeng Wang; Ziqi Shi; Cong Nie; Rongfu Huang; Bin Yan (Journal of Water Process Engineering, 2025)

In-situ bond conversion strategy to construct Pt/1T-MoS2 heterojunctions by MOF-confinement for hydrogen evolution reaction in wide-pH-value water and seawater - Haoyuan Hao; Yukun Lu; Na Liu; Wenjing Bao; Fengyue Sun; Cong Zhang; Dengwei Yan; Changle Yue (Fuel, 2025)

Engineered hydrogel platform for diabetic wound healing - Jidan Cui; Jianbin Shi; Yanjun Liu; Xianbao Shi; Jin Sun; Zhonggui He; Cong Luo; Shenwu Zhang (Chemical Engineering Journal, 2025)

Meteorological–hydrological coupling flood forecast and error propagation characteristics based on radar data assimilation in small- to medium sized River Basin: a case study of Zhanghe River Basin in China - Yufang Gao; Linyi Cong; Tao Peng; Xin Sun; Tong Nie; Yingchun Hu (Natural Hazards, 2025)

Production and Subsequent Application of Different Biochar-based Organic Fertilizers to Enhance Vegetable Quality and Soil Carbon Stability - Jining Zhang; Li-ao Ge; Yuxiang Yang; Xianxian Zhang; Cong Wang; Huifeng Sun; Honghui Chen; Jian Huang; Sheng Zhou (Journal of Soil Science and Plant Nutrition, 2025)

Assessing predictions on fitness effects of missense variants in HMBS in CAGI6 - Jing Zhang; Lisa Kinch; Panagiotis Katsonis; Olivier Lichtarge; Milind Jagota; Yun S. Song; Yuanfei Sun; Yang Shen; Nurdan Kuru; Onur Dereli; Ogun Adebali; Muttaqi Ahmad Alladin; et al. (Human Genetics, 2025)

How heatwaves impact microalgae in the presence of environmentally relevant PFAS concentration: Metabolic shifts and challenges posed - Jieming Liao; Yonglong Lu; Yinyue Liu; Bin Sun; Kunyu Zhang; Cong Wang; Haojie Lei; Zhiwei Cao (Journal of Hazardous Materials, 2025)

Origin and evolution of slope-confined canyons and their relationship with gas hydrate accumulation in the northwestern Qiongdongnan Basin, South China Sea - Zigui Chen; Tao Jiang; Wenzhao Sun; Yue Chen; Cong Cheng; Ru Yin (Geomorphology, 2025)

Synergistic enhancement of catalytic hydrodeoxygenation performance by oxygen vacancies and frustrated Lewis pairs - Qing-Qing Sun; Cong Liu; Guo-Qiang Zhang; Zhong-Qiu Liu; Mei-Ying Wang; Ai-Min Wang; Yujing Liu; Runpu Shen; Anguo Ying (Fuel, 2025)

Oxidation mechanism of methane fuel blended with dimethyl ether/hydrogen/ammonia via ReaxFF molecular dynamics simulation - Liang Song; Chun-Chen Xu; Jing Ye; Yong Zhang; Fang-Chao Hou; Bo-Cong Chen; Hao-Long Su; Jing Sun (Fuel, 2025)

Improved mercury removal performance and leaching stability of Fe/Br co-doped biochars synthesized through one-step pyrolysis - Xuehui Sun; Yunyun Hu; Mantang Chen; Weihui Liao; Cong Nie; Yipeng Wang; Yang Xu (Fuel, 2025)

The responses of root exudates and microbiome in the rhizosphere of main plant and aromatic intercrops to soil Cr stress - Rui Li; Zhenglin Li; Kui Zhang; Cong Zhang; Yue Sun; Jie Zhang; Yi Zheng; Yuncong Yao; Xiaoxiao Qin (Environmental Pollution, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Rice Wall-Associated Protein Kinase OsWAK12 Modulates Primary Root and Root Hair Via Involving in Auxin Pathway - Changqing Du; Xin Hu; Zheng Hu; Cong Chen; Fanqing Duanmu; Yihan Fu; Lili Wang; Quanshi Dong; Hongzheng Sun; Junzhou Li; Quanzhi Zhao (Journal of Plant Growth Regulation, 2025)

A deep learning method for bias correction of wind field in the South China Sea - Cong Pang; Tao Song; Handan Sun; Xin Li; Danya Xu (Frontiers in Marine Science, 2025)
To address the systematic bias in the Global Forecast System (GFS) wind field forecasts, we utilize deep learning techniques. The developed MU - Diffusion framework, based on a diffusion model and MultiUnet (a multitasking Unet model), establishes a nonlinear relationship between GFS and the fifth-generation EC atmospheric reanalysis (ERA5) data. Focusing on the South China Sea region, this method corrects both wind speed and direction simultaneously. Using 2022 GFS data, we achieved average enhancements of 42% in wind speed and 38.3% in wind direction compared to the initial GFS data. Tests in typhoon conditions also confirm the excellent performance of this architecture.

Insights to the roles of nitrogen-doped biochar in anaerobic digestion - Zhang-Wei He; Sheng-Jie Sun; Ai-Hua Li; Cong-Cong Tang; Ai-Juan Zhou; Yong-Xiang Ren; Zhi-Hua Li; Ai-Jie Wang; Wen-Zong Liu (Process Safety and Environmental Protection, 2025)

Comprehensive investigation of pollutant removal and microbial community in University of Cape Town membrane bioreactors by aluminum sulfate addition - Guangrong Sun; Haibing Cong; Chuanyi Zhang (Journal of Water Process Engineering, 2025)

Molybdenum isotopic evidence for linked changes in North Pacific Intermediate Water and subtropical Northwest Pacific redox conditions over the last 200 k.y - Yanguang Dou; Chenghui Sun; Shouye Yang; Xuefa Shi; Yonghua Wu; Jingyi Cong; Yong Zhang; Fengmei Wang; Feng Cai; Peter D. Clift (Global and Planetary Change, 2025)

Evaluation of physicochemical quality, specific aromatic characteristic, and volatile organic compound profile of fresh-cut coriander leaves under different super-atmospheric oxygen modified atmosphere packaging conditions - Chun-yu Ni; Xing-lu Sun; Hui-na Dong; Cong-cong Xu (Food Packaging and Shelf Life, 2025)

Ternary organic solar cells containing fused-benzotriazole polymer as donor and two types of benzotriazole molecules as guest component - Ning Sun; Leyi Tang; Lei Yang; Mengzhen Du; Zongtao Wang; Qing Guo; Peiqing Cong; Yanfang Geng; Jimin Du; Erjun Zhou (Chemical Engineering Journal, 2025)

Highly active and CO-resistant PdRuMo/C with a wide potential-stable window toward alkaline hydrogen oxidation reaction - Chunxiao Chai; Haoliang Huang; Hao Yang; Jiaqi Qin; Chongyun Sun; Yongpeng Li; Zhaoqi Wang; Xinwei Zhao; Zhongyu Qiu; Tiantian Li; Jiahuan Li; Rui Gao; et al. (Chemical Engineering Journal, 2025)

Effects of Vibratory Stress Relief on Microstructure and Mechanical Properties of Marine Welded Structures - Liqiang Gao; Qinan Yao; Yuchen Yang; Dejian Sun; Guanhua Xu; Bangping Gu; Cong Yang; Shuaizhen Li (Journal of Marine Science and Engineering, 2024)
Dissimilar steel welded structures are commonly used in the marine engineering field. Owing to the scarcity of in-depth investigation into the intricate pattern of residual stress distribution in welding within 316L/Q345 dissimilar steel welded joints and methods for reducing this stress, a platform-based vibratory stress relief (VSR) experimental system was established to comprehensively study the effects of VSR on the mechanical properties and microstructure of 316L/Q345 welded structures. Scanning electron microscopy (SEM) was used to examine the fracture morphology and explore the intrinsic mechanisms by which VSR enhances the mechanical properties of welded joints. The findings suggest that VSR is capable of significantly homogenizing and diminishing the welding residual stress within the heat-affected area of 316L/Q345 mismatched steel welded specimens. The significant reduction in residual stress after VSR can primarily be attributed to the combination of alternating stress applied by the VSR platform and the welding residual stress, which exceeded the yield limit of the metal materials. Furthermore, the significant reduction in residual stress, refinement of second-phase particles, and changes in fracture mechanisms are the main reasons for the increased strength observed after VSR. This study has significant engineering application value, providing a theoretical basis for the use of VSR treatment to enhance the reliability of the safe operation of marine engineering equipment.

DEHP regulates ferritinophagy to promote testicular ferroptosis via suppressing SIRT1/PGC-1α pathway - Qi Zhu; Jianan Zhai; Zhengguo Chen; Zhifang Guo; Xiance Sun; Jing Li; Ningning Wang; Xiaofeng Yao; Cong Zhang; Haoyuan Deng; Shaopeng Wang; Guang Yang (Science of The Total Environment, 2024)

Enhancing immune defense against COVID-19: Alveolar delivery of mucosal vaccines - Pei-Huang Wu; Dong-Chun Hong; Chu Xie; Mu-Sheng Zeng; Cong Sun (Science Bulletin, 2024)

Influence of energy-saving devices on the hydrodynamic characteristics of a waterjet-propelled ship: Experimental and numerical investigation - Kewei Song; Pei Xu; Jie Gong; Cong Sun; Shenwei Ge (Ocean Engineering, 2024)

Long-term exposure to third-hand smoke could accelerate biological aging via mitochondrial dysfunction: Evidence from population and animal studies - Wenbo Jiang; Xin Liu; Qianqian Lei; Mengjie Xiao; Mengyao Li; Yifan Ma; Cong Hu; Xinmiao Kong; Leyao Qi; Huanyu Wu; Changhao Sun (Journal of Hazardous Materials, 2024)

Biogeochemical process governing cadmium availability in sediments of typical coastal wetlands driven by drying-wetting alternation - Cheng-Cheng Jiang; Guang-Hui Yu; Xiao-Jie Zhou; Fu-Sheng Sun; Cong-Qiang Liu (Journal of Hazardous Materials, 2024)

OR-LIM: Observability-aware robust LiDAR-inertial-mapping under high dynamic sensor motion - Yangzi Cong; Chi Chen; Bisheng Yang; Ruofei Zhong; Shangzhe Sun; Yuhang Xu; Zhengfei Yan; Xianghong Zou; Zhigang Tu (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

The influence of soil salinization, induced by the backwater effect of the Yellow River, on microbial community dynamics and ecosystem functioning in arid regions - Mengyuan He; Cong Shen; Shuang Peng; Yuanduo Wang; Jianbin Sun; Junhua Zhang; Yiming Wang (Environmental Research, 2024)

Shift from legacy to emerging per- and polyfluoroalkyl substances for watershed management along the coast of China - Haojie Lei; Yonglong Lu; Pei Wang; Xingwei Xie; Jialong Li; Xupeng An; Zian Liang; Bin Sun; Cong Wang (Environmental Pollution, 2024)

Enhancing CO2 electroreduction to formate on bismuth catalyst via sulfur doping - Xiaoxu Duan; Junli Xu; Yuan Cong; Haofei Geng; Kai Chen; Teng Xu; Yuxiang Zhang; Fuhai Zhang; Jianqiu Zhu; Linjuan Zhang; Wei Zhao; Yifei Sun; et al. (Chemical Engineering Journal, 2024)

Accuracy assessment on eight public PM2.5 concentration datasets across China - Yangchen Di; Xizhang Gao; Haijiang Liu; Baolin Li; Cong Sun; Yecheng Yuan; Yong Ni (Atmospheric Environment, 2024)

Effects of Vegetation Distribution and Morphology of Tidal Channels on Hydrological Connectivity of Tidal Flats Under Different Formation Processes in the Liaohe Delta Wetland - Kexin Chen; Shuxiu Liang; Pifu Cong; Zhaochen Sun; Jiaqing Sun (Wetlands, 2024)

Transcriptomic Analysis Reveals Dynamics of Gene Expression in Liver Tissue of Spotted Sea Bass Under Acute Thermal Stress - Pengyu Li; Yalong Sun; Haishen Wen; Xin Qi; Yonghang Zhang; Donglei Sun; Cong Liu; Yun Li (Marine Biotechnology, 2024)

Comparing the intra-annual radial growth of three temperate species as related to leaf phenology - Nipeng Qian; Zhenzhao Xu; Chaojie Song; Chunchao Dong; Zhen Sun; Ying Liu; Zhenyong Deng; Mingzhu Cong; Qijing Liu (European Journal of Forest Research, 2024)

Biogenic silica dynamics in coastal wetland sediments: A key driver of silicon and carbon biogeochemical cycling - Xiangwei Zhao; Zhaoliang Song; Yuntao Wu; Lukas Van Zwieten; Laodong Guo; Changxun Yu; Zimin Li; Lele Wu; Xiaomin Yang; Xiangbin Ran; Jun Sun; Yuqiu Wei; et al. (Limnology and Oceanography, 2024)
Biogenic silica (biogenic Si) is a bioactive component crucial for the biogeochemical cycling of Si in terrestrial and aquatic ecosystems. Its formation and dissolution dynamics are intricately linked to carbon (C) cycling. However, knowledge about the source, composition, and factors controlling the distribution of biogenic Si in coastal wetland sedimentary environments is still limited. To address this lack of knowledge, we introduced a suite of geometric models for biogenic Si biovolume calculation and investigated biogenic Si assemblages, along with biogenic Si and biogenic Si‐occluded C contents, in sediments from representative coastal wetlands along the west coast of Bohai Bay. Our analysis showed that sedimentary biogenic Si predominantly derived from phytoliths (78.1% ± 5.8%), diatoms (18.2% ± 4.8%), and sponge spicules (3.7% ± 2.9%). Notably, phytolith assemblages were primarily composed of forms derived from the Poaceae family. The biogenic Si‐occluded C content (0.035–1.870 g kg −1 ) within these wetland sediments was consistent across both sites, accounting for 0.97–5.71% of the total organic C pool. Structural equation modeling indicated that total organic C, pH, and amorphous aluminum oxides either directly or indirectly influenced the biogenic Si content in coastal wetlands sediments. These results demonstrate the critical role that biogenic Si plays in the Si biogeochemical cycle and provide valuable information that advances our understanding of the biogeochemical interactions between Si and C in coastal wetland ecosystems.

Antibiotic intermediates and antibiotics synergistically promote the development of multiple antibiotic resistance in antibiotic production wastewater - Sun Miao; Yanyan Zhang; Baochan Li; Xin Yuan; Cong men; Jiane Zuo (Journal of Hazardous Materials, 2024)

Coupling and coordination of food security and agricultural carbon emission efficiency: Changing trends, influencing factors, and different government priority scenarios - Cong Sun; Enjun Xia; Jieping Huang; Haotian Tong (Journal of Environmental Management, 2024)

Near-zero-waste processing of jarosite waste to achieve sustainability: A state-of-the-art review - Mingfei Zhu; Yunyan Wang; Chujing Zheng; Yongjian Luo; Yun Li; Shuaixia Tan; Zhumei Sun; Yong Ke; Cong Peng; Xiaobo Min (Journal of Environmental Management, 2024)

Numerical investigation on dynamic flow characteristics of methane condensation in microchannels - Yuwei Sun; Cong Zhao; Haocheng Wang; Yinan Qiu; Maoqiong Gong; Yanxing Zhao (International Journal of Refrigeration, 2024)

Thermal decomposition behaviors of adamantane and 1-methyladamantane in oxygen atmosphere: ReaxFF molecular dynamics simulation - Liang Song; Tian-Cheng Zhang; Yong Zhang; Bo-Cong Chen; Jing Ye; Fang-Chao Hou; Jing Sun; Su-Qin Zhou (Fuel, 2024)

The yeast Dothiora sorbi IOJ-3 naturally produced various filamentous sectors with distinct abilities by undergoing DNA demethylation - Yong Sun; Yijia Zhang; Suwan Pan; Hao Cong; Jihong Jiang (Fungal Biology, 2024)

Methylmercury chloride inhibits meiotic maturation of mouse oocytes in vitro by disrupting the cytoskeleton - Zhiming Ding; Yan Sun; Caiyun Wu; Cong Ma; Hongzhen Ruan; Yingying Zhang; Yan Xu; Ping Zhou; Yunxia Cao; Zuying Xu; Huifen Xiang (Food and Chemical Toxicology, 2024)

Associations of multiple blood metals with cardiac structure and function: A cross-sectional study in a CAD population - Yapei Sun; Qi Mao; Denglu Zhou; Jiacheng Tian; Hang Du; Qin Yu; Jianhua Zhao; Weixia Duan; Cong Liu; Yu Duan; Jie Zhou; Tian Zhang; et al. (Environmental Pollution, 2024)

Heterostructured GCN Nanosheets/ZnO nanoflowers for enhanced TMO loading: From high-performance three electrode systems to printed flexible asymmetric supercapacitors - Xuhao Wang; Fenglin Sun; Fuhao Jiang; Binxuan Diao; Rong Wang; Hongjiang Li; Sang Woo Joo; Rong Li; Se Hyun Kim; Chenhao Cong; Xinlin Li (Chemical Engineering Journal, 2024)

Printed flexible supercapacitors utilizing composites of MWCNT/MOF ultrathin nanosheets: Exploring 1D/2D structural adjustment - Binxuan Diao; Chenhao Cong; Fenglin Sun; Hongjiang Li; Haoran Zhang; Xuhao Wang; Mingliang Jin; Sooman Lim; Xinlin Li; Se Hyun Kim (Chemical Engineering Journal, 2024)

Online in-situ modification of biochar for the efficient removal of elemental mercury and co-benefit of SO2/NO removal - Qiqi Yao; Ziyao Yang; Cong Nie; Mantang Chen; Xuehui Sun; Jiaxin Zhu; Yang Xu (Chemical Engineering Journal, 2024)

Icariin-loaded selenium-gold multi-shell nanocomposites with NIR-II response release to relieve post-damaged bone microenvironment for osteoporosis synergy therapy - Yuqing Li; Xiaotong Feng; Yuwei Li; Qile Song; Naling Long; Xiaoting Fu; Yifan Wang; Yingjiao He; Huiying Yan; Cong Li; Lina Feng; Cundong Fan; et al. (Chemical Engineering Journal, 2024)

Salts-activated synthesis of Cu/Co co-doped biochar for efficient removal of elemental mercury from coal combustion flue gas - Lina Liu; Xuehui Sun; Cong Nie; Mantang Chen; Yipeng Wang; Qingzhu Zhang; Yang Xu (Chemical Engineering Journal, 2024)

Coupled coordination and pathway analysis of food security and carbon emission efficiency under climate-smart agriculture orientation - Cong Sun; Enjun Xia; Jieping Huang; Haotian Tong (Science of The Total Environment, 2024)

Study on the influence of water saturation on radon exhalation rates of rocks - Pengfei Li; Qiang Sun; Lin Cong (Science of The Total Environment, 2024)

Injection of micro jets to improve hydrodynamic performance of a ducted propeller - Chun Yang; Hua-Dong Yao; Cong Sun; Chunyu Guo; Chao Wang; Wanlong Ren (Ocean Engineering, 2024)

Whole-genome sequencing of Ganzi horse reveals the genetic diversity and provides unique insights into its plateau adaptation - Jiale Han; Meixuan Lu; Cong Li; Minhao Sun; Qiaoyan Hu; Yidan Li; Halima Jafari; Zhaofei Wang; Pengcheng Zhao; Ruihua Dang (Livestock Science, 2024)

Improved microbial-plant soil bioremediation of PAHs and heavy metal through in silico methods - Lei Zhao; Peixuan Sun; Jiaxuan Gao; Yunxiang Li; Qikun Pu; Cong Lyu; Wenjin Zhao (Journal of Hazardous Materials, 2024)

Preparation, characterization, and mechanism of swelling and Cu2+ adsorption by alginate-based beads enhanced with Huangshui polysaccharides - Ziyan Wu; Jian Su; Xiangyun Cong; Dong Zhao; Jihong Wu; Hanling Zhou; Mingquan Huang; Jia Zheng; Dongrui Zhao; Baoguo Sun (Journal of Cleaner Production, 2024)

Pyrolysis and oxidation mechanisms of ethylene and ethanol blended fuel based on ReaxFF molecular dynamics simulation - Liang Song; Chun-Chen Xu; Jing Ye; Yong Zhang; Biao Chen; Fang-Chao Hou; Bo-Cong Chen; Hao-Long Su; Jing Sun (Fuel, 2024)

Regulating fat globule structure of infant formula based on MFGM to promote lipid uptake by improving lipolysis - Yue Sun; Bin Zhu; Pingyao Cong; Xiaodong Li; Lu Liu; Chanchan Guo; Kuangyu Zhao; Jiaxin Qiu; Haowen Ji; Xiaojun Zhu; Kouadio Jean Eric-Parfait Kouame (Food Hydrocolloids, 2024)

Biochar alleviates inhibition effects of humic acid on anaerobic digestion: Insights to performances and mechanisms - Sheng-Jie Sun; Fei Wang; Zhang-Wei He; Cong-Cong Tang; Ai-Juan Zhou; Yong-Xiang Ren; Zhihua Li; Wenzong Liu (Environmental Research, 2024)

Amine/vermiculite composite aerogels fabricated by polyethyleneimine-induced vermiculite nanosheet gelation for efficient direct air capture - Shuai Wang; Huilian Sun; Jie Wang; Cong Chen; Lanlan Jiang; Yi Zhang; Yu Liu; Yongchen Song; Zheng Ling (Chemical Engineering Journal, 2024)

Intensified O2 activation and lattice O supply at inverse oxide-metal interface for catalytic oxidation reactions: A case study in alcohol oxidation - Kun Liu; Yongbin Sun; Jiaqi Si; Cong Fu; Yushui Bi; Xiaomin Zhao; Guofeng Zhao (Chemical Engineering Journal, 2024)

Efficient window layer modification enabling the remarkable FF and efficiency improvement of kesterite solar cell - Dongliang Ding; Yali Sun; Wenbo Li; Yuzhou Sun; Ridong Cong; Zhongrong Wang; Chao Gao; Wei Yu (Chemical Engineering Journal, 2024)

Silicon promotes biomass accumulation in Phragmites australis under waterlogged conditions in coastal wetland - Yuntao Wu; Xiaodong Zhang; Jiayang Lin; Xia Wang; Shaobo Sun; Qian Hao; Lele Wu; Jingyun Zhou; Shaopan Xia; Xiangbing Ran; Yidong Wang; Jiahuan Tang; et al. (Plant and Soil, 2024)

In vivo assembly in tobacco cells to elucidate and engineer the biosynthesis of 4-hydroxydihydrocinnamaldehyde from Gloriosa superba - Zhiqiang Xiong; Zhuoying Ding; Jingyi Sun; Xuefei Jiang; Hanqing Cong; Huapeng Sun; Fei Qiao (Plant Cell Reports, 2024)

Spatial heterogeneity and driving mechanism of urban climbing and its impact on regional environment in varied landform types in the middle reaches of the Yellow River - Congjian Sun; Jiamin Cong; Wei Chen (Journal of Mountain Science, 2024)

Long term comparison of GHG emissions and crop yields in response to direct straw or biochar incorporation in rice-wheat rotation systems: A 10-year field observation - Huifeng Sun; Xianxian Zhang; Jining Zhang; Cong Wang; Sheng Zhou (Agriculture, Ecosystems & Environment, 2024)

Association of prenatal multiple metal exposures with child neurodevelopment at 3 years of age: A prospective birth cohort study - Yun Qiu; Yuxin Liu; Ming Gan; Weiting Wang; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; Xin Xu; et al. (Science of The Total Environment, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Experimental/numerical investigation on the hydrodynamic and noise characteristics of pump-jet propulsion - Kaiqiang Weng; Cong Sun; Kang Han; Chao Wang; Shuai Sun; Peng Li; Jian Hu (Ocean Engineering, 2024)

Construction and comprehensive evaluation of an index system for climate-smart agricultural development in China - Haotian Tong; Enjun Xia; Cong Sun; Kuan Yan; Jun Li; Jieping Huang (Journal of Cleaner Production, 2024)

Molecularly engineering a lipid nanoregulator destroying the last defense of ferroptosis in breast cancer therapy - Jiaping Wu; Xuan Zhang; Dongqi Sun; Xianbao Shi; Jin Sun; Cong Luo; Zhonggui He; Shenwu Zhang (Chemical Engineering Journal, 2024)

Analysis of Fracture Network Formation Mechanisms and Main Controlling Factors of Methane Explosion Fracturing in Deep Shale Reservoir - Yu Wang; Cheng Zhai; Ting Liu; Xu Yu; Jizhao Xu; Yong Sun; Yuzhou Cong; Wei Tang; Yangfeng Zheng; Ning Luo (Rock Mechanics and Rock Engineering, 2024)

Curcumin inhibits PAT-induced renal ferroptosis via the p62/Keap1/Nrf2 signalling pathway - Jianan Zhai; Zhengguo Chen; Qi zhu; Zhifang Guo; Xiance Sun; Liping Jiang; Jing Li; Ningning Wang; Xiaofeng Yao; Cong Zhang; Haoyuan Deng; Shaopeng Wang; et al. (Toxicology, 2024)

ε-Polylysine treatment maintains sensory quality, texture, flavor, and inhibits aerobic bacteria growth in vacuum-packed fresh-cut lettuce - Liu Qianqian; Zhang Xin; Han Cong; Chen Qingmin; Sun Fei; Fu Maorun; Zhao Handong; Xiao Zhijian; Tang Zheng (Postharvest Biology and Technology, 2024)

Application of copper for sufficient metal extraction from zinc leaching residue: Process optimization and copper reuse - Limin Zhang; Yunyan Wang; Yun Li; Zhumei Sun; Yong Ke; Cong Peng; Mingfei Zhu; Yongjian Luo; Xiaobo Min (Minerals Engineering, 2024)

Modeling and forecasting of coal price based on influencing factors and time series - Cong Wang; Gang Xu; Changliang Sun; Jun Xu; Kai Xu; Long Jiang; Yi Wang; Sheng Su; Song Hu; Jun Xiang (Journal of Cleaner Production, 2024)

Construction of ultrafine and highly dispersed RuSe2 on WOx by “atom-to-cluster” strategy for efficient hydrogen evolution reaction - Fengyue Sun; Wenjing Bao; Chao Feng; Jiahui Bi; Changle Yue; Cong Zhang; Na Liu; Haoyuan Hao; Yukun Lu (Fuel, 2024)

Characterization of two virulent Salmonella phages and transient application in egg, meat and lettuce safety - XiaoWen Sun; Fan Xue; Cong Cong; Bilal Murtaza; LiLi Wang; XiaoYu Li; ShuYing Li; YongPing Xu (Food Research International, 2024)

Genome-wide atlas of rust resistance loci in wheat - Jingyang Tong; Cong Zhao; Dan Liu; Dilani T. Jambuthenne; Mengjing Sun; Eric Dinglasan; Sambasivam K. Periyannan; Lee T. Hickey; Ben J. Hayes (Theoretical and Applied Genetics, 2024)
Rust diseases, including leaf rust, stripe/yellow rust, and stem rust, significantly impact wheat ( Triticum aestivum L.) yields, causing substantial economic losses every year. Breeding and deployment of cultivars with genetic resistance is the most effective and sustainable approach to control these diseases. The genetic toolkit for wheat breeders to select for rust resistance has rapidly expanded with a multitude of genetic loci identified using the latest advances in genomics, mapping and cloning strategies. The goal of this review was to establish a wheat genome atlas that provides a comprehensive summary of reported loci associated with rust resistance. Our atlas provides a summary of mapped quantitative trait loci (QTL) and characterised genes for the three rusts from 170 publications over the past two decades. A total of 920 QTL or resistance genes were positioned across the 21 chromosomes of wheat based on the latest wheat reference genome (IWGSC RefSeq v2.1). Interestingly, 26 genomic regions contained multiple rust loci suggesting they could have pleiotropic effects on two or more rust diseases. We discuss a range of strategies to exploit this wealth of genetic information to efficiently utilise sources of resistance, including genomic information to stack desirable and multiple QTL to develop wheat cultivars with enhanced resistance to rust disease.

Highly sensitive and selective electrochemical biosensor using odorant-binding protein to detect aldehydes - Cong Peng; Yutong Sui; Chaohua Fang; Hongxu Sun; Wenxin Liu; Xinying Li; Chen Qu; Wenhui Li; Jiemin Liu; Chuandong Wu (Analytica Chimica Acta, 2024)

NR2F1 overexpression alleviates trophoblast cell dysfunction by inhibiting GDF15/MAPK axis in preeclampsia - Ke Zhang; Hailing Zhang; Bing Wang; Shanshan Gao; Caiping Sun; Cong Jia; Jinquan Cui (Human Cell, 2024)

Artificial intelligence in ovarian cancer drug resistance advanced 3PM approach: subtype classification and prognostic modeling - Cong Zhang; Jinxiang Yang; Siyu Chen; Lichang Sun; Kangjie Li; Guichuan Lai; Bin Peng; Xiaoni Zhong; Biao Xie (EPMA Journal, 2024)

Experimental investigation on compressive dwell fatigue behavior of titanium alloy pressure hull for deep-sea manned submersibles - Lei Wang; Cong Ye; Chengqi Sun; Shichao Feng; Xiaozhong Xie; Yuan Gao; Kun Zhao; Yanqing Li; Zhengquan Wan (Ocean Engineering, 2024)

Membraneless organelles assembled by AuNPs-enzyme integration in non-photosynthetic bacteria: Achieving high specificity and selectivity for solar hydrogen production - Hui Li; Xiaoxuan Yu; Yaqi Wu; Cong Li; Zhengwei Xu; Wang Liu; Shuheng Chen; Hongcheng Sun; Yan Ge; Zhenhui Qi; Junqiu Liu (Chemical Engineering Journal, 2024)

Multiscale rooftop greening and its socioeconomic implications in Hong Kong - Jing Ling; Ka Hei Anson Yip; Shan Wei; Ka Ying Sit; Liqun Sun; Qingyan Meng; Na Cong; Jian Lin; Hongsheng Zhang (Building and Environment, 2024)

Multiple Applications of a Novel Fluorescence Probe with Large Stokes Shift and Sensitivity for Rapid H2S Detection - Lai-Xin Hong; Le Sun; Cong Li; Rong-Lan Zhang; Jian-She Zhao (Journal of Fluorescence, 2024)

Pilot-scale field studies on activated microbial remediation of petroleum-contaminated soil - Wu-Juan Sun; Qian Li; Bo-Yun Luo; Rui Sun; Cong-Yu Ke; Si-Chang Wang; Qun-Zheng Zhang; Xun-Li Zhang (Environmental Geochemistry and Health, 2024)

Bicyclol mitigates lipopolysaccharide-induced acute lung injury through myeloid differentiation factor 88 inhibition - Lili Fu; Linting Cheng; Junliang Lu; Qianru Ye; Cong Shu; Chuchu Sun; Zhiguo Liu; Guang Liang; Weixin Zhao (Toxicology and Applied Pharmacology, 2024)

The G932C mutation of chitin synthase 1 gene (CHS1) mediates buprofezin resistance as confirmed by CRISPR/Cas9-mediated knock-in approach in the brown planthopper, Nilaparvata lugens - Fan Zhang; Yan-Chao Zhang; Zhi-Tao Yu; Bing Zeng; Hao Sun; Yu-Qiu Xie; Kun Yan Zhu; Cong-Fen Gao (Pesticide Biochemistry and Physiology, 2024)

First record of the latest Devonian ostracods from Xainza region, Tibet, China: implications on palaeoenvironment and palaeobiogeography - Jun-Jun Song; Wen Guo; Yu-Cong Sun; Juan Ma; Jia-Yuan Huang; Yi-Chun Zhang; Wen-Kun Qie (Palaeoworld, 2024)

Flow boiling heat transfer characteristics and correlation development of R290/R600a mixtures in an internally threaded tube - Cong Zhao; Yuwei Sun; Hao Guo; Yanxing Zhao; Maoqiong Gong; Zhiqiang Yang (International Journal of Refrigeration, 2024)

One step cleanup of 160 pesticides and veterinary drugs in aquatic products using melamine-based automatic pressure filtration purification method combined with HPLC-MS/MS - Ruidong Zhou; Cong Kong; Yupeng Wen; Guangxin Yang; Wendi Huo; Chaoying Zhang; Huiwu Sun; Huan Liu; Dongmei Huang; Jincheng Li (Food Chemistry, 2024)

Enteral nutrition in the management of acute pancreatitis: Modulates gut microbiome and alleviates inflammation - Fang-Yuan Yang; Yi-Jing Cai; Xiao-Ying Niu; Shun-Fu Wang; Yu-Qi Wang; Sabola Eluby Esmie; Rui-Cong Chen; Sheng-Jie Dai; Hong-Ru Kong; Hong-Wei Sun; Ke-Qing Shi (Food Bioscience, 2024)

A green and low-cost preparation of polyacrylonitrile fibers with imine dioxime and amidoxime groups for efficient and selective gold recovery - Wenqi Zhang; Cong Liu; Xiangrui Meng; Jie Sun; Huayu Tian (Chemical Engineering Journal, 2024)

A neural m6A pathway regulates behavioral aggregation in migratory locusts - Xianliang Huang; Qing Li; Yanan Xu; Ang Li; Shanzheng Wang; Yusheng Chen; Chunrui Zhang; Xia Zhang; Hailin Wang; Cong Lv; Baofa Sun; Shaoqin Li; et al. (Science China Life Sciences, 2024)

Low Rather Than High Level Nitrogen Additions Accelerate Carbon Release Process and Inhibit Recalcitrant Carbon Allocation via Stirring Soil Enzymatic Activities in Plateau Meadows - Mei Lu; Mingliu Wang; Yujia Sun; Guanfa Sun; Dingrong Zhao; Shengyang San; Cong Li; Guoqing Liu; Chuniao Guo; Xuyan Zhao; Zhimin Chen (Journal of Soil Science and Plant Nutrition, 2024)

Marinobacter albus sp. nov., Isolated from Sand Sediment in a Coastal Intertidal Zone - Tai-Hang Deng; Yu Zhang; Wen-Wu Zhang; Yue Su; Jia-Wei Gao; Jun-Jie Ying; Lin Xu; Xiao-Ming Xia; Cong Sun (Current Microbiology, 2024)

Panax quinquefolius saponins and panax notoginseng saponins attenuate myocardial hypoxia-reoxygenation injury by reducing excessive mitophagy - Junyan Xia; Cong Chen; Yanan Sun; Sinai Li; Yuxuan Li; Bai-Ru Cheng; Yanting Pang; Yan Li; Dong Li; Qian Lin (Cell Biochemistry and Biophysics, 2024)

Fate of contaminants of emerging concern in two wastewater treatment plants after retrofitting tertiary treatment for reduction of nitrogen discharge - Tianyuan Chen; Qiaoting Zeng; Meixian Cao; Lanping Zhang; Bob Adyari; Cong Ma; Kai Wang; Deti Gao; Anyi Hu; Qian Sun; Chang-Ping Yu (Environmental Research, 2024)

Comparative evaluation of acid-resistant nanofiltration membranes for heavy metal removal in acidic wastewater - Chun Cui; Cong Luo; Tian Tian; Ru Feng; An-Kang Li; Shi-Peng Sun; Xue-Li Cao (Desalination, 2024)

Synergistic therapy for melanoma via bioactive compounds derived metal-phenolic networks - Zhenghao Zhou; Cong Li; Shuai Cui; Shian Sun; Shaowei Zhu; Qing Yu; Ning Ding; Hao Hong; Dongzhi Yang (Chemical Engineering Journal, 2024)

Unveiling the dual tunability of dimension and pore structure in MAX-derived carbon via molten salt electrolysis - Sheng Pang; Jijun Lu; Liangwei Cong; Youpeng Xu; Yiwei Sun; Zhenqian Zhang; Jianwei Guo; Dong Wang; Xiao Yang; Guoyu Qian; Zhi Wang (Chemical Engineering Journal, 2024)

Waste cigarette butts-templated synthesis of in-situ graphitic carbon-doped ZnO fibers boosting dual-selectivity NO2/butanone at different temperatures - Zhao-Qi Cui; Ze Wei; Cong Chen; Yuan-Yuan Sun; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2024)

RETRACTED: Altitude explains insignificant autumn phenological changes across regions with large topography relief in the Tibetan Plateau - Nan Cong; Zhiyong Du; Zhoutao Zheng; Guang Zhao; Dongqi Sun; Jiaxing Zu; Yangjian Zhang (Science of The Total Environment, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Metabolomics revealed more deleterious toxicity induced by the combined exposure of ammonia and nitrite on Ruditapes philippinarum compared to single exposure - Ming Cong; Zhaoshun Li; Yu Che; Yuanmei Li; Wenwen Tian; Jiasen Lv; Xiyan Sun (Marine Environmental Research, 2024)

Pilot–scale vertical continuous–flow reactors applied to treat rural domestic wastewater at low temperature via aerobic granular sludge - Shibo Cong; Ge Yu; Shuai Xia; Haiyang Yu; Yang Sun; Yu Gao; Yuzhi Liu; Donglei Zou (Journal of Water Process Engineering, 2024)

La-Ce-MOF nanocomposite coated quartz crystal microbalance gas sensor for the detection of amine gases and formaldehyde - Shihao Chen; Xiaoyi Duan; Cong Liu; Suqi Liu; Pei Li; Dianbin Su; Xia Sun; Yemin Guo; Wei Chen; Zhenhe Wang (Journal of Hazardous Materials, 2024)

Sulfate radical-assisted photocatalytic degradation of quinoline with WO3/CuFe2O4/Cu Z-scheme system: Comparison of persulfate and sulfite activation - Bihan Sun; Houfen Li; Rong Han; Cong Gao; Rui Li; Aijuan Zhou; Xiuping Yue (Journal of Environmental Chemical Engineering, 2024)

A combined evaluation of the characteristics and antibiotic resistance induction potential of antibiotic wastewater during the treatment process - Sun Miao; Yanyan Zhang; Cong Men; Yiou Mao; Jiane Zuo (Journal of Environmental Sciences, 2024)

Crystal mush rejuvenation in the formation of Triassic dacites in Mengku, SE Tibetan Plateau - Feng Cong; Fu-Yuan Wu; Wen-Chang Li; Zai-Bo Sun; Xiao-Chi Liu; De-Feng He; Wei-Qiang Ji; Fang-Yang Hu; Shao-Hua Zhang; Xiao-Ming Huang (Journal of Asian Earth Sciences, 2024)

Highly selective production of high purity methyl oleate biodiesel by silver-based deep eutectic solvent extraction - Xianli Fu; Yuxin Liu; Cong Sun; Wei Liu (Fuel, 2024)

Design of probiotic delivery systems for targeted release - Cong Xu; Munkh-Amgalan Gantumur; Jialu Sun; Jiahui Guo; Jiage Ma; Zhanmei Jiang; Wan Wang; Jing Zhang; Yue Ma; Juncai Hou; David Julian McClements (Food Hydrocolloids, 2024)

Application of vertically ordered polyaniline nanofibers in enhancing the ORR activity of Pt catalysis - Shujie Xue; Rongzhong Yang; Cong Lei; Jianan Zhao; Shanshan Sun; Minglin Zhao; Zhaogen Wang; Qinghong Huang; Yuping Wu (Chemical Engineering Journal, 2024)

Grazing exclusion jeopardizes plant biodiversity effect but enhances dryness effect on multifunctionality in arid grasslands - Lingfei Yu; Wenjuan Sun; Haiyang Zhang; Nan Cong; Yuan Chen; Jinjiao Hu; Xin Jing (Agriculture, Ecosystems & Environment, 2024)

Degradation and mechanism of PFOA by peroxymonosulfate activated by nitrogen-doped carbon foam-anchored nZVI in aqueous solutions - Changyu Li; Cong Shen; Bin Gao; Wenxu Liang; Yifan Zhu; Weijie Shi; Shiyun Ai; Hongxia Xu; Jichun Wu; Yuanyuan Sun (Chemosphere, 2024)

Sex differences in the growth of sea cucumber (Apostichopus japonicus) - Jingjing Cong; Lingnan Kong; Weihan Meng; Zengdong Wang; Zhihui Sun; Yaqing Chang (Aquaculture, 2024)

Damaging effects of earth fissures on high-speed railway bridges: Insights from physical experiments and numerical simulations - Cong Liu; Zhaoyue Yu; Jiewei Zhan; Ming Wu; Yuemin Sun; Jianbing Peng (Transportation Geotechnics, 2024)

Mechanisms of LPS–induced epithelial mesenchymal transition in bEECs - Mingkun Sun; Pengjie Song; Yu Zhao; Bowen Li; Ping Wang; Zhipeng Cong; Song Hua (Theriogenology, 2024)

Comparative peptidomics analysis of preeclamptic placenta and the identification of a novel bioactive SERPINA1 C-terminal peptide - Lingling Jiang; Yuanyuan Zhu; Liuxin Wu; Cong Wang; Nana Yang; Yetao Xu; Lizhou Sun (Reproductive Biology, 2024)

Plastic food? Energy compensation of zebrafish (Danio rerio) after long-term exposure to polylactic acid biomicroplastics - Zhenghua Duan; Yizhuo Chen; Yuhang Dou; Huiyu Fan; Jing Wang; Jiaoyue Cong; Hongwen Sun; Lei Wang (Journal of Hazardous Materials, 2024)

Reduction strategies of polycyclic aromatic hydrocarbons in farmland soils: Microbial degradation, plant transport inhibition, and their mechanistic analysis - Lei Zhao; Tianfu Yao; Yuanyuan Zhao; Shuhai Sun; Cong Lyu; Wenjin Zhao (Journal of Hazardous Materials, 2024)

Efficient carbamazepine degradation by modified copper tailings and PMS system: Performance evaluation and mechanism - Cong Pan; Yan Sun; Yiqie Dong; Haobo Hou; Ming-Feng Kai; Jirong Lan (Journal of Hazardous Materials, 2024)

The organic–inorganic dual anchoring strategy based on organic chelators and lacunary polyoxometalates for the preparation of efficient CoWS hydrodesulfurization catalysts - Wenjing Bao; Cong Zhang; Dengwei Yan; Fengyue Sun; Changle Yue; Chongze Wang; Yukun Lu (Fuel, 2024)

Synergistic binding mechanisms of co-contaminants in soil profiles: Influence of iron-bearing minerals and microbial communities - Fu-Sheng Sun; Miao-Miao Wang; Xiang-Yang Zhao; Qiao-Yun Huang; Cong-Qiang Liu; Guang-Hui Yu (Environmental Pollution, 2024)

Associations between fine particulate air pollution with small-airway inflammation: A nationwide analysis in 122 Chinese cities - Jian Lei; Cong Liu; Xia Meng; Yiqing Sun; Suijie Huang; Yixiang Zhu; Ya Gao; Su Shi; Lu Zhou; Huihuan Luo; Haidong Kan; Renjie Chen (Environmental Pollution, 2024)

Redox-regulating nanotherapeutics potentiating ferroptosis-driven cancer treatment - Xiaohong Yang; Xinxin Sun; Jin Lei; Xianbao Shi; Shenwu Zhang; Cong Luo (Chemical Engineering Journal, 2024)

In-situ construction of Z-scheme silver phosphotungstate/polyimide photocatalysts and enhanced visible-light photocatalytic degradation of aflatoxin B1 in vegetable oil - Pengcheng Meng; Jiao Li; Panpan Wang; Guolong Yang; Wei Liu; Shaohua Liang; Ruinan Yang; Cong Sun (Chemical Engineering Journal, 2024)

Natural variation of Grain size 3 allele differentially functions in regulating grain length in xian/indica and geng/japonica rice - Yong-Bin Peng; Chen-Yang Du; Ya-Nan He; Chong-Ke Zheng; Wei Sun; Jin-Jun Zhou; Li-Xia Xie; Cong-Hui Jiang; Jian-Di Xu; Fang Wang; Xian-Zhi Xie (Euphytica, 2024)

Crosstalk between methanogens and methanotrophs determines methane emissions in a rice paddy under different watering regimes - Xianxian Zhang; Zuopeng Lv; Huifeng Sun; Junguo Bi; Jining Zhang; Cong Wang; Sheng Zhou (Applied Soil Ecology, 2024)

Association of multiple blood metals and systemic atherosclerosis: A cross-sectional study in the CAD population - Yapei Sun; Qi Mao; Denglu Zhou; Jiacheng Tian; Hang Du; Qin Yu; Jianhua Zhao; Weixia Duan; Cong Liu; Yu Duan; Jie Zhou; Tian Zhang; et al. (Chemosphere, 2024)

Short-term exposure to ozone may trigger the onset of Kawasaki disease: An individual-level, case-crossover study in East China - Yixiang Zhu; Renjie Chen; Cong Liu; Yue Niu; Xia Meng; Su Shi; Kexin Yu; Guoying Huang; Liping Xie; Siyuan Lin; Min Huang; Meirong Huang; et al. (Chemosphere, 2024)

Ecological risk assessment for typical organophosphorus pesticides in surface water of China based on a species sensitivity distribution model - Jing Wang; Zhirong Wang; Yuhang Dou; Jiaoyue Cong; Hongwen Sun; Lei Wang; Zhenghua Duan (Science of The Total Environment, 2024)

Silicon fractionations in coastal wetland sediments: Implications for biogeochemical silicon cycling - Xiangwei Zhao; Zhaoliang Song; Lukas Van Zwieten; Yidong Wang; Xiangbin Ran; Qian Hao; Juqin Zhang; Zimin Li; Jun Sun; Yuqiu Wei; Lele Wu; Shuyan Liu; et al. (Science of The Total Environment, 2024)

Hysteretic nonlinear SMA-TMD for wind-wave-induced vibration mitigation of monopile offshore wind turbines considering stiffness degradation - Shuo Yao; Cong Liu; Xin Chen; Baijian Tang; Yong Sun; Zhiqiang Zhang (Ocean Engineering, 2024)

Vertical baffled reactor promoting aerobic sludge concentration for effective remediating unstable–load domestic wastewater: Performance, microbial properties and mechanism - Shibo Cong; Yang Sun; Yanhong Dong; Guangxu Xiao; Donglei Zou; Yu Yan (Journal of Water Process Engineering, 2024)

Surface implantation of ionically conductive polyhydroxyethylaniline on cation exchange membrane for efficient heavy metal ions separation - Wei-Tao Ding; Hui-Qian Huo; Dan Sun; Yan-Li Ji; Cong-Jie Gao (Journal of Environmental Chemical Engineering, 2024)

Induced synthesis of SO2-promoting and H2O-tolerant sorbents for elemental mercury removal from flue gas - Ziyao Yang; Yang Xu; Xuehui Sun; Cong Nie; Mantang Chen; Qingzhu Zhang; Guangqian Luo (Fuel, 2024)

High phase purity of stable 1T-phase Co-doped WS2 for full pH hydrogen evolution reaction in water and seawater - Changle Yue; Fengyue Sun; Na Liu; Yang Liu; Wenjing Bao; Xiaowei Zhang; Cong Zhang; Shuyan Ma; Yan Zhou; Chao Feng; Yukun Lu (Fuel, 2024)

Molecular insights into the wettability of antifreeze protein-adsorbed hydrate surface: Application to hydrate anti-agglomeration - Yue Zhang; Zherui Chen; Chengyang Yuan; Jingyue Sun; Cong Chen; Xiaodong Liang; Nicolas von Solms; Yongchen Song (Chemical Engineering Journal, 2024)

The accumulation and carbon sequestration potential of biogenic silica in coastal salt marshes: Implications for relative sea-level rise - Xiangwei Zhao; Xiaodong Zhang; Zhaoliang Song; Lukas Van Zwieten; Xiangbin Ran; Yulin Pu; Jun Sun; Qiang Li; Lele Wu; Xiaomin Yang; Yuqiu Wei; Zimin Li; et al. (CATENA, 2024)

Engineering photo-methylotrophic Methylobacterium for enhanced 3-hydroxypropionic acid production during non-growth stage fermentation - Zeng-Xin Ma; Chen-Xi Feng; Ya-Zhen Song; Jing Sun; Yi Shao; Shu-Zhen Song; Bin Wan; Cong Zhang; Huan Fan; Kai Bao; Song Yang (Bioresource Technology, 2024)

Development and experimental validation of a machine learning-based disulfidptosis-related ferroptosis score for hepatocellular carcinoma - Cong Zhang; Tiantian Xu; Kun Ji; Shoujin Cao; Jing Ai; Junhan Pan; Yunbo Cao; Yuning Yang; Li Jing; Jun-Hui Sun (Apoptosis, 2024)

Isolation and Cultivation of Carotenoid-Producing Strains from Tidal Flat Sediment and Proposal of Croceibacterium aestuarii sp. nov., a Novel Carotenoid-Producing Species in the Family Erythrobacteraceae - Xiao-Yan Sun; Han Dong; Yu Zhang; Jia-Wei Gao; Peng Zhou; Cong Sun; Lin Xu (Journal of Marine Science and Engineering, 2024)
Carotenoids are extensively used in drugs, cosmetics, nutrients, and foods, owing to their antioxidant and anti-inflammatory characteristics. Diverse marine heterotrophic prokaryotes can accumulate carotenoids and become promising alternatives for the advancement of carotenoids production. In this research, 55 strains were isolated and cultivated from tidal flat sediment in Zhoushan and classified into the phyla Pseudomonadota (n = 24), Bacillota (n = 18), Bacteroidota (n = 9), and Actinomycetota (n = 4). Nine of them accumulated carotenoids, and most of them belonged to the families Flavobacteriaceae (n = 4) and Erythrobacteraceae (n = 4). Among those carotenoid-producing strains, one strain, designated as D39T, was proposed as one novel species belonging to the genus Croceibacterium through polyphasic taxonomy approaches. Genomic annotations and carotenoid compound determinations revealed that strain D39T encoded crtEBIYZG genes and mainly accumulated zeaxanthin as major carotenoids. Furthermore, carotenoid biosynthesis pathway in the majority of Croceibacterium strains were identical with that in the strain D39T, implying that Croceibacterium members can be sources of producing zeaxanthin. This study enhances knowledge of microbial biodiversity in tidal flats, proposes a novel carotenoid-producing Croceibacterium species, and elucidates carotenoid biosynthesis pathway in the genus Croceibacterium, which contribute to enriching marine carotenoid-producing strains and promoting a comprehensive insight into genomic contents of them.

Mass-immigration shapes the antibiotic resistome of wastewater treatment plants - Lanping Zhang; Bob Adyari; Liyuan Hou; Xiaoyong Yang; Mahmoud Gad; Yuwen Wang; Cong Ma; Qian Sun; Qiang Tang; Yifeng Zhang; Chang-Ping Yu; Anyi Hu (Science of The Total Environment, 2024)

Nanoplastics increase the adverse impacts of lead on the growth, morphological structure and photosynthesis of marine microalga Platymonas helgolandica - Minhao Liu; Xiukai Song; Cong Liu; Xumeng Cui; Wei Sun; Zhengmao Li; Jun Wang (Marine Environmental Research, 2024)

Changes in Accessibility of Chinese Coastal Ports to Arctic Ports under Melting Ice - Ran Zhang; Yi Zuo; Zhuo Sun; Shuang Cong (Journal of Marine Science and Engineering, 2023)
Global warming has accelerated the melting of Arctic sea ice, providing favorable conditions for Arctic shipping. Arctic ports are gaining prominence in shipping networks and international trade. Accessibility is a key indicator of port facilitation, and identifying trends in Arctic port accessibility holds significance for Arctic route planning and port development. To achieve this, this paper develops a modeling framework for assessing the accessibility of Arctic ports. First, we utilize the Coupled Model Intercomparison Project (CMIP6) model to predict sea ice conditions and quantify the navigation risk for open water (OW) vessels and Arc4 ice-class (Arc4) vessels during the summer months of 2030–2050. The A-star (A*) algorithm is then used to plan the vessel’s shortest route while avoiding high-risk waters. Finally, changes in the accessibility of Arctic ports are calculated by using an improved gravity model. The framework is applied for the quantitative analysis of the accessibility of Chinese coastal ports to Arctic ports. The results indicate that accessibility to Arctic ports will gradually increase for all Chinese ports in the future, with the port of Shanghai continuing to maintain its prominence under the trend of melting sea ice.

Preparation of chitosan/citral forward osmosis membrane via Schiff base reaction with enhanced anti-bacterial properties - Lei Wu; Xiaolu Gong; Cong Ma; Lan Xu; Ming Li; Chen Lyu; Nan Sun (Chemosphere, 2023)

m6A modification associated with YTHDF1 is involved in Japanese encephalitis virus infection - Xiao-han Li; Jing Chen; Yu-da Ou; Xiang Zhong; Jia-huan Hu; Rui-cong Sun; Ying-jun Lv; Jian-chao Wei; Yun Young Go; Bin Zhou (Veterinary Microbiology, 2023)

Nanoplastics induce neuroexcitatory symptoms in zebrafish (Danio rerio) larvae through a manner contrary to Parkinsonian's way in proteomics - Yudi Wang; Jing Wang; Jiaoyue Cong; Haihong Zhang; Zhiyuan Gong; Hongwen Sun; Lei Wang; Zhenghua Duan (Science of The Total Environment, 2023)

Exploring spatial-temporal driving factors for changes in multiple ecosystem services and their relationships in West Liao River Basin, China - Wei Jiang; Bojie Fu; Guangyao Gao; Yihe Lv; Cong Wang; Siqi Sun; Kai Wang; Stefan Schüler; Zhongguo Shu (Science of The Total Environment, 2023)

Characterising personal, household, and community PM2.5 exposure in one urban and two rural communities in China - Ka Hung Chan; Xi Xia; Cong Liu; Haidong Kan; Aiden Doherty; Steve Hung Lam Yim; Neil Wright; Christiana Kartsonaki; Xiaoming Yang; Rebecca Stevens; Xiaoyu Chang; Dianjianyi Sun; et al. (Science of The Total Environment, 2023)

Complete genome sequence of carotenoid-producing Aestuariibaculum lutulentum L182T isolated from the tidal sediment - Wen-Jia Liu; Jia-Wei Gao; Yu Zhang; Cong Sun; Lin Xu (Marine Genomics, 2023)

Coupling UV-radiation with immobilized bacteria for the removal of 17β-estradiol and 17 α-ethynylestradiol - Dan Qin; Claude Kiki; Cong Ma; Qian Sun; Chang-Ping Yu (Journal of Water Process Engineering, 2023)

Levels of iron and iron-related proteins in Alzheimer’s disease: A systematic review and meta-analysis - Lin Gong; Jiahui Sun; Shuyan Cong (Journal of Trace Elements in Medicine and Biology, 2023)

Boron isotope behavior during metamorphic dehydration and partial melting of continental crust: Constraints from tourmaline in metapelites and leucocratic dikes, Himalayan orogen - Min Ji; Xiao-Ying Gao; Yi-Xiang Chen; Cong Tu; Guo-Chao Sun; Bing Gong; Xiang-Ping Zha; Yong-Fei Zheng (Geochimica et Cosmochimica Acta, 2023)

Engineering of 0D/1D architectures in 3D networks over CDs/PPy-CPP biomass foam with high efficiency on seawater evaporation - Lei Sun; Xiang Zhang; Hao Yuan; Hongmin Cong; Yuxing Shi; Jialin Lu; Weilong Shi; Feng Guo (Chemical Engineering Journal, 2023)

Tunable biocomposite films fabricated using cellulose nanocrystals and additives for food packaging - Cong Chen; Wenjing Sun; Jinwu Wang; Douglas J. Gardner (Carbohydrate Polymers, 2023)

Elucidation of the neutralizing antibody evasion of emergent SARS-CoV-2 Omicron sub-lineages using structural analysis - Cong Sun; Yuan-Tao Liu; Yin-Feng Kang; Chu Xie; Shu-Xin Li; Yu-Tong Lu; Mu-Sheng Zeng (Science China Life Sciences, 2023)

Parerythrobacter aestuarii sp. nov., Isolated from Seawater in the Tidal Region of Taizhou - Han Dong; Ren-Zhuang Han; Yu Zhang; Maripat Xamxidin; Peng Zhou; Cong Sun; Wu Qu; Lin Xu (Current Microbiology, 2023)

A Pair of New Spirocyclic Alkaloid Enantiomers with TrxR Inhibitory Activities Were Isolated from Marine-Derived Aspergillus ruber TX-M4-1 - Cong Wang; Yufei Wang; Jian Sun; Shiyi Wang; Weisheng Du; Liman Zhou; Fandong Kong (Journal of Ocean University of China, 2023)

Toxicity of leachate from smoked cigarette butts to terrestrial animals: A case study on the earthworm Eisenia fetida - Yu Xi; Leiyu Diao; Ziyi Wang; Zi Jin; Yilin Wang; Wenhua Liu; Dongsheng Wen; Hongxin Li; Cong Sun; Jiqi Lu (Science of The Total Environment, 2023)

Ship energy-saving device: Influence of the scale effect and hull roughness on the resistance reduction effect of an interceptor - Kewei Song; Jie Gong; Shenwei Ge; Cong Sun; Haiyan Yang; Weiping Zhang (Ocean Engineering, 2023)

The effects of domain division types on the performance prediction of a rim-driven thruster - Peng Li; Cong Sun; Hua-Dong Yao; Zeping Wang; Chao Wang; Kaiqiang Weng (Ocean Engineering, 2023)

Suppressing trap density and energy loss via skeleton asymmetry strategy enables highly efficient all-small-molecule organic solar cells - Xufan Zheng; Xunchang Wang; Fengbo Sun; Ming Wan; Zhiya Li; Cong Xiao; Tingting Cong; Tianyu Hu; Yuchen Liao; Renqiang Yang (Chemical Engineering Journal, 2023)

Novel supramolecular deep eutectic solvent pretreatment for obtaining fluorescent lignin and promoting biomass pyrolytic saccharification - Zhiwen Jia; Shiyang Wang; Haipeng Yu; Wanyu Li; Jiamin Ye; Yihao Hu; Cong Liu; Zijian Ye; Yan Sun; Xiwei Xu (Bioresource Technology, 2023)

NCBP1 Improves Cognitive Function in Mice by Reducing Oxidative Stress, Neuronal Loss, and Glial Activation After Status Epilepticus - Xiaoying Gao; Zhipeng You; Cong Huang; Zhixiong Liu; Zixiao Tan; Jiran Li; Yang Liu; Xingan Liu; Fan Wei; Zhijie Fan; Sihua Qi; Jiahang Sun (Molecular Neurobiology, 2023)

Characterization of Maribacter polysaccharolyticus sp. nov., Maribacter huludaoensis sp. nov., and Maribacter zhoushanensis sp. nov. and illumination of the distinct adaptative strategies of the genus Maribacter - Jia-Wei Gao; Jun-Jie Ying; Han Dong; Wen-Jia Liu; Dong-Yan He; Lin Xu; Cong Sun (Frontiers in Marine Science, 2023)
Polysaccharides are complex carbohydrates and are abundant in the marine environment. Microbes degrade and utilize them using Carbohydrate-active enzymes (CAZymes), which mediate polysaccharides into the marine carbon cycle. With the continued supply of polysaccharides from the marine environment, tidal flats are also abundant in polysaccharides, resulting in an abundance of marine polysaccharide degrading strains. In this study, three novel strains, designated as D37 T , M208 T , and SA7 T , were isolated from the intertidal sediment samples located in Zhoushan, Zhejiang and Huludao, Liaoning, PR China. The phylogenetic trees using the 16S rRNA gene and genome sequences showed that the three novel strains belonged to the genus Maribacter . The highest 16S rRNA gene sequence similarities between the three novel strains and other strains of the genus Maribacter were 98.7%, 99.2%, and 98.8%, respectively, while the ANI, AAI, and dDDH values between the three strains and the other strains of the genus Maribacter were 70-86%, 67-91%, and 17-30%, respectively, supporting their affiliation as novel species. Combined with other phenotypic and genotypic characterization in this study, three novel species are proposed as Maribacter polysaccharolyticus sp. nov., Maribacter huludaoensis sp. nov., and Maribacter zhoushanensis sp. nov., respectively, for the three strains. Furthermore, we compared all available genomes of Maribacter representatives and found that Maribacter strains could be divided into two groups (A and B). The two groups are different in genome size and G + C content and gene densities of CAZyme, peptidase, and sulfatase. Group A possesses more CAZymes which are related to degrading laminarin, fucoidan, mannan, xylose, and xylan. This result suggests that the two groups may have different niche adaptation strategies. Our study contributes to a better understanding of the role of marine flavobacteria in biogeochemical cycles and niche specialization.

Taxonomic Diversity of Fish Species in the Lower Reaches of the Yellow River - Lufeng Sun; Xiuqi Li; Guancang Dong; Xuri Cong (Fishes, 2023)
In order to study the community of fishery resources, five sampling sections were set up in the lower Yellow River from 2019 to 2022 to investigate the diversity of fishery resources. A total of 54 fish species were identified in the survey, belonging to 9 orders, 19 families, and 48 genera. The number of species reached its highest level since the Integrated Water Regulation of the Lower Yellow River in 1999. The original rare and endangered fish species in the lower reaches of the Yellow River, such as Coilia nasus, Rhinogobio nasutus, and Pseudobagrus ussuriensis, have reappeared in the lower reaches. The population and abundance of main economic fish and common small-sized fish in the lower reaches of the Yellow River have increased. These signs all indicate that, and the fishery resources are recovering slowly in the lower Yellow River. By comparing the fish resources of various investigation sections, it was found that there are differences in fish diversity: the closer to the estuarine waters, the higher the variety of fish in the Yellow River at the upper level of the taxonomic category. However, that section of the lower Yellow River where species evenness, species diversity, and community structure of fishery resources were most stable was the confluence of Dongping Lake into the Yellow River, which has the most significant number of fish species, the smallest Λ+ value, and the most extensive G-F index. The above results indicate that Dongping Lake, as the only lake connected to the lower reaches of the Yellow River, plays an essential role in replenishing fish resources in the lower reaches of the Yellow River.

Naturally aged polylactic acid microplastics stunted pakchoi (Brassica rapa subsp. chinensis) growth with cadmium in soil - Zhenwen Xie; Cong Men; Xin Yuan; Sun Miao; Quanyi Sun; Jiamin Hu; Yanyan Zhang; Yuxin Liu; Jiane Zuo (Journal of Hazardous Materials, 2023)

L-type lectin receptor-like kinase OsCORK1 as an important negative regulator confers copper stress tolerance in rice - Ke Wang; Shen Li; Zhaoyan Yang; Cong Chen; Yihan Fu; Haitao Du; Hongzheng Sun; Junzhou Li; Quanzhi Zhao; Changqing Du (Journal of Hazardous Materials, 2023)

Quantitative characterization of water transport and wetting patterns in coal using LF-NMR and FTIR techniques - Yuliang Cai; Cheng Zhai; Xu Yu; Yong Sun; Jizhao Xu; Yangfeng Zheng; Yuzhou Cong; Yujie Li; Aikun Chen; Hexiang Xu; Shuai Wang; Xizhuo Wu (Fuel, 2023)

A novel ligand protection strategy based on lacunary polyoxometalate to precisely construct CoMoS active sites for hydrodesulfurization - Cong Zhang; Wenjing Bao; Shuyan Ma; Chongze Wang; Yunqi Liu; Chenguang Liu; Daofeng Sun; Yukun Lu (Chemical Engineering Journal, 2023)

Promotion of nitrogen removal in a denitrification process elevated by zero-valent iron under low carbon-to-nitrogen ratio - Ze-Tong Feng; Xin Ma; Ying-Jun Sun; Jia-Min Zhou; Zu-Gang Liao; Zhi-Cong He; Fei Ding; Qian-Qian Zhang (Bioresource Technology, 2023)

A comprehensive analysis of the Bencao (herbal) small RNA Atlas reveals novel RNA therapeutics for treating human diseases - Yinghao Cao; Yexuan Lin; Na Sun; Xinyi Du; Yixin Dong; Song Mei; Xingyu Deng; Xiaobei Li; Shaoting Guo; Kegong Tang; Jiaqi Liu; Xiangyu Qiao; et al. (Science China Life Sciences, 2023)

Exploring the therapeutic mechanism of Banxia Xiexin Decoction in mild cognitive impairment and diabetes mellitus: a network pharmacology approach - Cong Li; Wei Yang; Yubo Meng; Lina Feng; Linlin Sun; Zhenghong Li; Xingfang Liu; Mingquan Li (Metabolic Brain Disease, 2023)

Optimizing fertilizer management mitigated net greenhouse gas emissions in a paddy rice-upland wheat rotation system: A ten-year in situ observation of the Yangtze River Delta, China - Xianxian Zhang; Huifeng Sun; Cong Wang; Jining Zhang; Sheng Zhou (Agriculture, Ecosystems & Environment, 2023)

A tradeoff between denitrification and nitrate leaching into the subsoil in nitrate-rich vegetable soils treated by reductive soil disinfestation - Hui-Min Zhang; Yu Liu; Ying-Hua Zhang; Yong Li; Zhao-Xiong Chen; Xin Sun; Hang Jing; Jing Wang; Ahmed S. Elrys; Mao-Heng Zhang; Zu-Cong Cai; Yi Cheng (Agriculture, Ecosystems & Environment, 2023)

The heterogeneity of microbial diversity and its drivers in two types of sediments from tidal flats in Beibu Gulf, China - Yong-Lian Ye; Kuo-Jian Ma; Yun-Han Fu; Zhi-Cheng Wu; Ge-Yi Fu; Cong Sun; Xue-Wei Xu (Frontiers in Marine Science, 2023)
Mudflats and sandflats are two common types of coastal tidal flats, the structure and function differences of microbial communities between them are still underappreciated. Beibu Gulf is a diurnal tidal regime located in China, the differences between the two type of tidal flats could be more distinct. In this study, we collected a total of 6 samples from Beibu Gulf, consisting of 3 sandflats samples and 3 mudflats samples, classified based on clay and silt content. Generally, the mudflats samples exhibited higher levels of NH 4 + _N and TOC, but lower in ORP and pH. The microbial diversity of the two types of tidal flats was investigated, revealing great differences existed and sandflats had higher microbial richness and diversity than mudflats. Furthermore, we analyzed the association between microbial communities and environmental factors, finding NH 4 + _N to have the highest contribution to the total variation in microbial community structure, and microbial groups such as Desulfobacterota, Campilobacterota, Chloroflexota, Calditrichota, Spirochaetota, Zixibacteria, Latescibacterota and Sva0485 group in mudflats were positively associated with NH 4 + _N. The functions of microbial community were predicted using metagenomic sequences and metagenome assembled genome (MAG). Mudflats contained more genes for carbon fixation. Nitrate and nitrite reduction were widely existed in mudflats and sandflats, but nitrogen fixation was only existed in mudflats, and Campilobacterota , Desulfobacterota and Gammaproteobacteria MAGs were mainly responsible for it. Sandflats composed more genes for ammonium oxidation, but no MAG was found whether in sandflats or mudflats. Microbes in mudflats exhibited a greater abundance of genes related to sulfur cycling, especially in reduction process, unique MAGs in mudflats such as Calditrichota, Chloroflexota, Desulfobacterota and Zixibacteria MAGs are responsible for sulfate and sulfite reduction. Finally, we predicted functions of ammonium related microbes in mudflats based on MAGs and found Campilobacterota and Desulfobacterota MAGs were important for high accumulation of ammonium in mudflats. This study illuminated the structural and functional differences of microbial communities in mudflats and sandflats, providing new insights into the relationship of microbial communities and environment in the tidal flat.

The interaction of different chlorine-based additives with swine manure during pyrolysis: Effects on biochar properties and heavy metal volatilization - Yonggang Xu; Fangjie Qi; Yubo Yan; Weimin Sun; Tianxia Bai; Nan Lu; Hong Luo; Cong Liu; Biao Yuan; Zhenhuan Sheng; Tingwu Liu (Waste Management, 2023)

Global prevalence and factors affecting the level of Cryptosporidium contamination in soil: A systematic review, meta-analysis, and meta-regression - Mu-Ran Zuo; Xiao-Ting Li; Rui-Zhe Xu; Wen-Chao Sun; Hany M. Elsheikha; Wei Cong (Science of The Total Environment, 2023)

Parallel paired electrolysis-enabled asymmetric catalysis: simultaneous synthesis of aldehydes/aryl bromides and chiral alcohols - Bing Sun; Zhen-Hua Wang; Yun-Zhao Wang; Yu-Cheng Gu; Cong Ma; Tian-Sheng Mei (Science Bulletin, 2023)

Diatom evidence for late Holocene environmental change in a permafrost peatland in the northern Greater Khingan Mountains, Northeast China - Dongxue Han; Yang Sun; Zicheng Yu; Ming Jiang; Jinxin Cong; Chuanyu Gao; Guoping Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Elevated temperature decreases cardiovascular toxicity of nanoplastics but adds to their lethality: A case study during zebrafish (Danio rerio) development - Zhenghua Duan; Jing Wang; Haihong Zhang; Yudi Wang; Yizhuo Chen; Jiaoyue Cong; Zhiyuan Gong; Hongwen Sun; Lei Wang (Journal of Hazardous Materials, 2023)

Designing functionalized graphene-stitched-SiC/fluoropolymer novel composite coating with excellent corrosion resistance and hydrogen diffusion barrier properties - Sicheng Yuan; Kun Li; Yue Sun; Chang Cong; Yaran Liu; Dan Lin; Luchao Pei; Yanji Zhu; Huaiyuan Wang (Chemical Engineering Journal, 2023)

Identifying changes in the hydrological connectivity and their drivers in the Liaohe Delta wetland - Kexin Chen; Pifu Cong; Limei Qu; Shuxiu Liang; Zhaochen Sun; Jianbo Han (Ocean & Coastal Management, 2023)

Organic carbon preservation in wetlands: Iron oxide protection vs. thermodynamic limitation - Fu-Sheng Sun; Chao Ma; Guang-Hui Yu; Yakov Kuzyakov; Yun-Chao Lang; Ping-Qing Fu; Li-Jun Guo; Hui Henry Teng; Cong-Qiang Liu (Water Research, 2023)

The effects and mechanism of LncRNA NORAD on doxorubicin-induced cardiotoxicity - Xiaoran Guan; Yong Wang; Wuquan Li; Xiangyong Liu; Jing Jiang; Weihua Bian; Cong Xu; Yeying Sun; Chunxiang Zhang (Toxicology, 2023)

Source analysis of metals in the tea plant using linear correlation analysis combined with a lead-strontium isotope tracer - Yan Cong; Rui-lian Yu; Yu Yan; Bo-sen Weng; Gong-ren Hu; Jing-wei Sun; Jian-yong Cui; YanYan; Yao-yi Huang (CATENA, 2023)

Pore Structure and Damage Evaluation of Hot Dry Rocks in Enhanced Geothermal System by Combining Electrical Resistivity, Ultrasonic Waves and Nuclear Magnetic Resonance - Yong Sun; Cheng Zhai; Xu Yu; Jizhao Xu; Yuzhou Cong; Yangfeng Zheng; Wei Tang; Yujie Li (Natural Resources Research, 2023)

Memristive competitive hopfield neural network for image segmentation application - Cong Xu; Meiling Liao; Chunhua Wang; Jingru Sun; Hairong Lin (Cognitive Neurodynamics, 2023)

Diverse early diagenetic processes of ferromanganese nodules from the eastern Pacific Ocean: evidence from mineralogy and in-situ geochemistry - Rong Su; Fengyue Sun; Xiaohu Li; Fengyou Chu; Guosheng Sun; Jie Li; Hao Wang; Zhenggang Li; Cong Zhang; Weiyan Zhang; Xiaohan Gong; Yanhui Dong (International Geology Review, 2023)

Genomic and phylotypic properties of three novel marine Bacteroidota from bare tidal flats reveal insights into their potential of polysaccharide metabolism - Kuo-Jian Ma; Yong-Lian Ye; Yun-Han Fu; Ge-Yi Fu; Cong Sun; Xue-Wei Xu (Frontiers in Marine Science, 2023)
Special geographical location and abundant organic matter profiles in tidal flats have resulted in great microbial diversity, in which Bacteroidota strains are considered as one of the primary degraders of polysaccharides, playing a crucial role in the carbon cycle. In this study, we collected sediment or sand samples from 34 bare tidal flats in China and investigated the profile of culturable bacteria, selected three Bacteroidota for polyphasic taxonomic analysis and revealed their polysaccharide metabolic potential. Totally, we isolated 352 pure cultured bacteria and they mainly distributed in Bacteroidota , Pseudomonadota , Bacillota , and Actinomycetota . It is shown that the bare tidal flats contained a large number of potential novel species, mainly distributed in Flavobacteriales and Cytophagales within Bacteroidota . Three Bacteroidota strains, M17 T , M82 T , and M415 T , isolated from mudflat were selected for polyphasic taxonomic analysis. The 16S rRNA gene sequence similarity between strain M17 T and Mangrovivirga cuniculi KCTC 72349 T was 99.28%, and less than 90.09% with other species; strain M82 T shared the highest 16S rRNA gene sequence similarity of 97.85% with Pontibacter litorisediminis KCTC 52252 T , and less than 97.43% with other species; strain M415T had higher 16S rRNA gene sequence similarities with type species of genera Eudoraea (92.62-93.68%), Zeaxanthinibacter (92.02-92.91%), and Muriicola (92.21-92.83%). Phylogenetic analysis based on 16S rRNA gene sequences and single-copy orthologous clusters showed that strains M17 T and M82 T represent novel species within the genus Mangrovivirga and Pontibacter , respectively, and strain M415 T represents a novel species of a novel genus within the family Flavobacteriaceae . The potential in polysaccharide metabolism of all these three strains was analyzed by genomes. The analysis revealed that glycoside hydrolases and glycosyltransferases account for more than 70% of the total CAZymes. Additionally, the numbers of polysaccharide utilization loci (PULs) and annotated CAZymes in Cytophagales spp. M17 T and M82 T were found to be higher than those in Flavobacteriales sp. M415 T . Highly specialized saccharolytic systems and the presence of numerous diversified CAZymes for obtaining energy through polysaccharide metabolism were speculated to help the three novel strains adapt to the utilization of both terrestrial and marine polysaccharides.

A new method for long-term in situ monitoring of seabed interface evolution: A self-potential probe - Zhihan Fan; Xianming Zhu; Haibo Xu; Zhiwen Sun; Hong Zhang; Xianbin Bi; Cong Hu; Dequan Lu; Zhongqiang Sun; Kai Li; Yongzheng Quan; Yonggang Jia (Ocean Engineering, 2023)

Upregulation of mitochondrial calcium uniporter contributes to paraquat-induced neuropathology linked to Parkinson’s disease via imbalanced OPA1 processing - Weixia Duan; Cong Liu; Jie Zhou; Qin Yu; Yu Duan; Tian Zhang; Yuanyuan Li; Guanyan Fu; Yapei Sun; Jiacheng Tian; Zhiqin Xia; Yingli Yang; et al. (Journal of Hazardous Materials, 2023)

Enrichment strategies of heavy metals in the O/H/O process composed of biological fluidized bed for wastewater treatment: A case study of Cu and Zn - Cong Wei; Xiaoqian Cheng; Wei Sun; Xia Tang; Tuo Wei; Zijun Pang; Xiong Ke; Zhi Qin; Jiamin Pan; Gengrui Wei; Guanglei Qiu; Chunhua Feng; et al. (Journal of Cleaner Production, 2023)

In situ self-assembled nanomedicines for cancer treatment - Xinxin Sun; Xiaohong Yang; Yao Chen; Jin Sun; Zhonggui He; Shenwu Zhang; Cong Luo (Chemical Engineering Journal, 2023)

Coaxial electrospun nanofibrous substrates with tunable wettability for constructing cucurbit[n]uril-embedded organic solvent nanofiltration membranes - Qian Wang; Qin-Yuan He; Liu-Lin Zhao; Yue Wang; Rong Fang; Cong Luo; Wei-Tong Lu; Hong-Ya Jiang; Shi-Peng Sun; Xue-Li Cao (Chemical Engineering Journal, 2023)

Quantifying the Impact of Hydrological Connectivity on Salt Marsh Vegetation in the Liao River Delta Wetland - Kexin Chen; Limei Qu; Pifu Cong; Shuxiu Liang; Zhaochen Sun; Jianbo Han (Wetlands, 2023)

Microstructure Evolution of Bituminous Coal Modified by High-Pressure CO2 Foam Fracturing Fluid with Different Treatment Times - Yangfeng Zheng; Cheng Zhai; Aikun Chen; Yong Sun; Yuzhou Cong; Wei Tang; Jizhao Xu; Xu Yu; Xinyu Zhu; Yujie Li (Natural Resources Research, 2023)

Portable smartphone-assisted ratiometric fluorescence sensor for visual detection of glucose - Xiaohui Zhang; Bo Sun; Yunyi Zhang; Qingfeng Zhang; Mahmood Hassan Akhtar; Ming Li; Yuwei Gu; Cong Yu (Analytica Chimica Acta, 2023)

Investigating food web structure and system function of an artificial reef ecosystem based on carbon and nitrogen stable isotope analysis: implications for reef management - Jie Feng; Xiaolong Zhao; Fan Bi; Wei Zhao; Liang Zhao; Hao Song; Meijie Yang; Zhi Hu; Cong Zhou; Pu Shi; Pengpeng Hu; Peizhen Ma; et al. (Frontiers in Marine Science, 2023)
Introduction Food web is an important basis for identifying trophodynamic processes, and evaluating the structural and functional characteristics of ecosystems. The trophodynamics and system function of artificial reef (AR) ecosystems have rarely been examined. Methods Stable isotope analysis was used to investigate the food web structure and functions of an artificial reef (AR) ecosystem in this study. Results and Discussion The δ13C and δ15N values of particulate organic matter (POM) in AR showed noticeable seasonal changes, and the δ13C value of POM in autumn was significantly higher than that in other seasons (p<0.05). There were no significant seasonal variations in the δ13C values of solid organic matter (SOM), and no significant difference between SOM and POM was observed except in autumn. Moreover, macroalgae did not significantly affect the δ13C values of SOM. Phytoplankton may be the primary nutrient source in the AR ecosystem. The δ13C values of most crustaceans in the AR were approximately between (-17.03 ± 0.22) ‰ – (-17.74 ± 0.07) ‰, higher than those of most fish, indicating that they may have different basal nutrient sources. The trophic level (TL) of invertebrates was between 2.00 and 3.09, and that of fish was between 2.98 and 3.66. The distribution of δ13C and TLs of crustaceans and fish showed that, except for crustaceans, bivalve shellfish and zooplankton might also be important food sources for fish in the AR ecosystem. Conclusion The δ13C and δ15N values of most species in the AR showed good continuity, indicating that they may be mainly produced from the AR ecosystem. Migratory species such as Lateolabrax japonicus and Sepiella maindroni showed higher δ13C values, indicating that they may have migrated from other sea areas. To maintain the stability of the ecosystem structure and function of the AR ecosystem, fishing activities should be carried out following the maximum sustainable yield theory. Future research needs to identify the nutritional relationship between AR and its adjacent sea areas, to depict the food web structure of the AR with higher accuracy.

Porcine Mx proteins inhibit pseudorabies virus replication through interfering with early gene synthesis - Jing Chen; Jia-huan Hu; Rui-cong Sun; Xiao-han Li; Jing Zhou; Bin Zhou (Veterinary Microbiology, 2023)

Dysregulation of the microbiota-brain axis during long-term exposure to polystyrene nanoplastics in rats and the protective role of dihydrocaffeic acid - Wenbo Jiang; Cong Hu; Yunyan Chen; Yue Li; Xinyi Sun; Huanyu Wu; Ruiming Yang; Yiwei Tang; Fengru Niu; Wei Wei; Changhao Sun; Tianshu Han (Science of The Total Environment, 2023)

Research on early warning and control measures for arable land resource security - Xueqing Sun; Pengcheng Xiang; Kexin Cong (Land Use Policy, 2023)

Accelerated methane emission from permafrost regions since the 20th century - Guo-zhi Xie; Li-peng Zhang; Cong-ying Li; Wei-dong Sun (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Synergistic Apoptosis-Ferroptosis: Oxaliplatin loaded amorphous iron oxide nanoparticles for High-efficiency therapy of orthotopic pancreatic cancer and CA19-9 levels decrease - Yilong Li; Xinlong Wang; Binbin Ding; Cong He; Can Zhang; Jiating Li; Haonian Wang; Zhibo Li; Gang Wang; Yongwei Wang; Hua Chen; Ping'an Ma; et al. (Chemical Engineering Journal, 2023)

Current and future potential soil organic carbon stocks of vegetated coastal ecosystems and their controls in the Bohai Rim Region, China - Shaobo Sun; Zhaoliang Song; Baozhang Chen; Yidong Wang; Xiangbin Ran; Yunying Fang; Lukas Van Zwieten; Iain P. Hartley; Yafei Wang; Qiang Li; Lele Wu; Cong-Qiang Liu; et al. (CATENA, 2023)

A20 ameliorates disc degeneration by suppressing mTOR/BNIP3 axis-mediated mitophagy - Xin Peng; Cong Zhang; Jia-Wei Gao; Feng Wang; Jun-Ping Bao; Zhi-Min Zhou; Rui Sun; Hang-Yu Ji; Cabral VLF; Xiao-Tao Wu (Genes & Genomics, 2023)

Aestuariibaculum lutulentum sp. nov., a marine bacterium isolated from coastal sediment in Beihai - Jia-Wei Gao; Dong-Yan He; Wen-Wu Zhang; Yu-Ruo Wang; Yue Su; Jun-Jie Ying; Zhi-Cheng Wu; Wu Qu; Lin Xu; Cong Sun (Archives of Microbiology, 2023)

Seasonal variation of the shape and location of the Luzon cold eddy - Ruili Sun; Peiliang Li; Yanzhen Gu; Chaojie Zhou; Cong Liu; Lin Zhang (Acta Oceanologica Sinica, 2023)

Calcium isotopic geochemistry of geothermal systems in the tectonically active southeastern Tibetan Plateau - Bei-Bei Chen; Si-Liang Li; Philip A.E. Pogge von Strandmann; Jun Zhong; Ting-Ting Ma; Jian Sun; Wen-Yan He; Cong-Qiang Liu (Science of The Total Environment, 2023)

Dry response and acclimated characteristics of people ascending the Tibetan Plateau - Dengjia Wang; Xin Sun; Cong Song; Yingying Wang; Guannan Duan; Jiale Hu (Journal of Thermal Biology, 2023)

Glycation of whey protein isolate and stachyose modulates their in vitro digestibility: Promising prebiotics as functional ingredients - Guang-yao Zhang; Cong Sun; Jing-ru Song; Wei-yi Jin; Yue Tang; Da-yong Zhou; Liang Song (Food Bioscience, 2023)

Oral vaccination with recombinant Lactobacillus casei with surface displayed OmpK fused to CTB as an adjuvant against Vibrio mimicus infection in Carassius auratus - Hong-Jin Li; Bin-Tong Yang; Yu-Feng Sun; Tong Zhao; Zhi-Peng Hao; Wei Gu; Meng-Xia Sun; Wei Cong; Yuan-Huan Kang (Fish & Shellfish Immunology, 2023)

A human antibody potently neutralizes RSV by targeting the conserved hydrophobic region of prefusion F - Chunyan Yi; Caixia Su; Xiaoyu Sun; Xiao Lu; Chuanya Si; Caixuan Liu; Zhuo Yang; Hong Yuan; Yuying Huang; Jing Wen; Yonghui He; Yaguang Zhang; et al. (Science China Life Sciences, 2023)

A Hybrid Multi-Criteria Decision-Making Framework for Ship-Equipment Suitability Evaluation Using Improved ISM, AHP, and Fuzzy TOPSIS Methods - Cheng Chen; Xiangrui Zhang; Guo Wang; Feng Feng; Cong Sun; Qin He (Journal of Marine Science and Engineering, 2023)
The inherent complexity of large ships makes it challenging to evaluate ship designs systematically and scientifically. Knowledge-based expert systems can be reasonable solutions. However, this problem needs more rationality and better operability, especially in complicated ship-equipment suitability evaluation problems with numerous indicators and complex structures. This paper presents a hybrid multi-criteria decision-making (MCDM) framework to extend the ship-equipment suitability evaluation to group decision-making settings, where individual consistency and group consensus are thoroughly investigated to improve rationality and operability. As a result, an improved Interpretive Structural Modeling (ISM) method is developed to construct the evaluation index systems. Furthermore, based on an applicability analysis of the selected MCDM methods, an improved Analytical Hierarchy Process (AHP) method is proposed to distribute the index weights, and an applicable Fuzzy Technique for Order Preference by Similarity to Ideal Solution (Fuzzy TOPSIS) method is utilized to evaluate and select appropriate ship designs. Finally, a ship-equipment environmental suitability evaluation case is examined. The results indicate that the proposed framework improves the rationality and operability of the decision-making process and provides practical support to decision-makers for the systematic and scientific evaluation of ship designs. Therefore, it can also be applied to other ship design evaluation and selection problems.

The mechanism of rh-endostatin-induced cardiotoxicity and its protection by dihydromyricetin[in vivo/in vitro, C57BL/6 mice, AC16 and hiPSC-CMs] - Xiaoran Guan; Wuquan Li; Yong Wang; Qun Zhao; Xinru Yu; Jing Jiang; Weihua Bian; Cong Xu; Yeying Sun; Chunxiang Zhang (Toxicology Letters, 2023)

Cyclodextrin as a green anti-agglomerant agent in oil–water emulsion containing asphalt - Zherui Chen; Jingyue Sun; Peng Wu; Weiguo Liu; Cong Chen; Chen Lang; Sining Dai; Wenning Zhou (Fuel, 2023)

Biochar as a multifunctional material facilitate the organohalide remediation: A state-of-the-art review - Xueqi Chen; Bin Wu; Wenxin Yang; Guanshu Zhao; Jinglong Han; Cong Huang; Bo Sun; Aijie Wang; Zhiling Li (Chemical Engineering Journal, 2023)

Vitamin D receptor (VDR) mediates the quiescence of activated hepatic stellate cells (aHSCs) by regulating M2 macrophage exosomal smooth muscle cell-associated protein 5 (SMAP-5) - Xuwentai Liu; Yue Wu; Yanyi Li; Kaiming Li; Siyuan Hou; Ming Ding; Jingmin Tan; Zijing Zhu; Yingqi Tang; Yuming Liu; Qianhui Sun; Cong Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2023)

A systematic review, meta-analysis and meta-regression of the global prevalence of foodborne Vibrio spp. infection in fishes: A persistent public health concern - Jun-Yang Ma; Xin-Kun Zhu; Ren-Ge Hu; Ze-Zheng Qi; Wen-Chao Sun; Zhi-Peng Hao; Wei Cong; Yuan-Huan Kang (Marine Pollution Bulletin, 2023)

Distribution of legacy and novel per- and polyfluoroalkyl substances in surface and groundwater affected by irrigation in an arid region - Ruoyu Mao; Yonglong Lu; Meng Zhang; Cong Wang; Bin Sun; Yajuan Shi; Shuai Song; Pei Wang; Jingjing Yuan; Jixin Zhao (Science of The Total Environment, 2023)

Zero-valent iron loaded on N-doped biochar fabricated by one-step pyrolysis of K2FeO4 and coffee grounds as a persulfate activator for Bisphenol A degradation - Bo Jiang; Yunshu Zhang; Cong Li; Jiaqi Guo; Chunmeng Sun (Process Safety and Environmental Protection, 2023)

Behaviour of Sr, Ca, and Mg isotopes under variable hydrological conditions in high-relief large river systems - Bei-Bei Chen; Si-Liang Li; Philip A.E. Pogge von Strandmann; David J. Wilson; Jun Zhong; Ting-Ting Ma; Jian Sun; Cong-Qiang Liu (Geochimica et Cosmochimica Acta, 2023)

Preparation of shell-core fiber-encapsulated Lactobacillus rhamnosus 1.0320 using coaxial electrospinning - Cong Xu; Jiage Ma; Zhijing Liu; Wan Wang; Xin Liu; Shanshan Qian; Lijun Chen; Liya Gu; Chuanqiang Sun; Juncai Hou; Zhanmei Jiang (Food Chemistry, 2023)

Acute responses of bio-denitrification to short-term clopyralid exposure: Kinetic analysis and biological mechanisms - Suyun Sun; Ya-Nan Hou; Cong Huang; Hafiz M. Adeel Sharif; Jianbo Guo; Nanqi Ren; Ai-Jie Wang (Chemical Engineering Journal, 2023)

Superhydrophilic molybdenum phosphide quantum dots on porous carbon matrix for boosting hydrogen evolution reaction - Yang Liu; Changle Yue; Fengyue Sun; Wenjing Bao; Lulu Chen; Zonish Zeb; Chongze Wang; Shuyan Ma; Cong Zhang; Daofeng Sun; Yuan Pan; Yichao Huang; et al. (Chemical Engineering Journal, 2023)

Microbial functional communities and the antibiotic resistome profile in a high-selenium ecosystem - Yanmei Sun; Jia Guo; Fu Wei; Xiaohui Chen; Meng Li; Chao Li; Size Xia; Guangming Zhang; Wencai You; Xin Cong; Tian Yu; Shiwei Wang (Chemosphere, 2023)

Knockout of the odorant receptor co-receptor, orco, impairs feeding, mating and egg-laying behavior in the fall armyworm Spodoptera frugiperda - Hao Sun; Ling-Ao Bu; Shao-Cong Su; Di Guo; Cong-Fen Gao; Shun-Fan Wu (Insect Biochemistry and Molecular Biology, 2023)

Ecological and human health risks of antibiotics in marine species through mass transfer from sea to land in a coastal area: A case study in Qinzhou Bay, the South China sea - Cong Wang; Yonglong Lu; Bin Sun; Meng Zhang; Chenchen Wang; Cuo Xiu; Andrew C. Johnson; Pei Wang (Environmental Pollution, 2023)

Durable antibacterial and temperature regulated core-spun yarns for textile health and comfort applications - Wei Fan; Yao Zhang; Yanli Sun; Shujuan Wang; Cong Zhang; Xichen Yu; Weiting Wang; Kai Dong (Chemical Engineering Journal, 2023)

Self-engineered lipid peroxidation nano-amplifier for ferroptosis-driven antitumor therapy - Xinxin Sun; Xiaohong Yang; Jing Wang; Yibo Shang; Pengfei Wang; Xia Sheng; Xiaohong Liu; Jin Sun; Zhonggui He; Shenwu Zhang; Cong Luo (Chemical Engineering Journal, 2023)

A chitosan derivative-crosslinked hydrogel with controllable release of polydeoxyribonucleotides for wound treatment - Yanzhen Sun; Xiaodong Jing; Yang Liu; Bing Yu; Hao Hu; Hailin Cong; Youqing Shen (Carbohydrate Polymers, 2023)

Have China’s drylands become wetting in the past 50 years? - Yu Zhang; Yangjian Zhang; Liang Cheng; Nan Cong; Zhoutao Zheng; Ke Huang; Jianshuang Zhang; Yixuan Zhu; Jie Gao; Yihan Sun (Journal of Geographical Sciences, 2023)

Multicolor colorimetric visual detection of Staphylococcus aureus based on Fe3O4–Ag–MnO2 composites nano-oxidative mimetic enzyme - Yushen Liu; Mengyue Sun; Wenteng Qiao; Shuang Cong; Yunqian Zhang; Luliang Wang; Zhenhua Hu; Fangjie Liu; Dacheng Wang; Ping Wang; Quanwen Liu (Analytica Chimica Acta, 2023)

Ecological distribution of modern diatom in peatlands in the northern Greater Khingan Mountains and its environmental implications - Dongxue Han; Yang Sun; Jinxin Cong; Chuanyu Gao; Guoping Wang (Environmental Science and Pollution Research, 2022)

Correction to: An analysis of the effects of human capital on green growth: effects and transmission channels - Daxu Liu; Guanzhuo Wang; Cong Sun; Muhammad Tariq Majeed; Zubaria Andlib (Environmental Science and Pollution Research, 2022)

Abrupt change of a thermal front in a high-biomass coastal zone during early spring - Jian Li; Peiliang Li; Peng Bai; Fangguo Zhai; Yanzhen Gu; Cong Liu; Ruili Sun; Wenfan Wu (Frontiers in Marine Science, 2022)
Coastal fronts play vital roles in local biogeochemical environment. An abrupt change of Zhejiang-Fujian coastal front (ZFCF) during early spring was well captured by multi-source satellite-retrieved sea surface temperature images. Here in this study, we investigated the mechanism of the abrupt decay with a combination of satellite observation and numerical simulation. Correlation analysis of long-term reanalysis data indicates that the variability of wind, heat flux and the Zhejiang-Fujian coastal current (ZFCC) have significant relationships with the variation of ZFCF in winter. Following heat budget analysis points out that net heat flux and horizontal advection are important in determining the net temperature tendency difference between two water masses of ZFCF during this process. To further explore the intrinsic physical roles of different dynamic factors, a comprehensive numerical investigation was conducted. Compared with the observations, the model reproduced the abrupt change process of the ZFCF satisfyingly. Sensitive experiments reveal that the weakening of the ZFCC, caused by the relaxation of the monsoon, contributes to the abrupt decay of ZFCF in the first half period, and heating effect of the Kuroshio Intrusion (KI) water gives rise to the following half period of the decay under the recovered monsoon. Further, with the impact of the KI water after the change, the ZFCF can be maintained even if the ZFCC is weak, whereas in January, the contribution of the KI water to the formation of the ZFCF seems to be limited under the prevailing monsoon. Besides, the riverine discharge and the tidal forcing can also modulate the spatiotemporal variation of ZFCF, the decrease of the river input also intensifies that decay, while tides fix the front at a specific depth.

Karst tiankeng shapes the differential composition and structure of bacterial and fungal communities in karst land - Cong Jiang; Xiang Sun; Yuanmeng Liu; Sufeng Zhu; Kexing Wu; Hui Li; Wei Shui (Environmental Science and Pollution Research, 2022)

Adventitial injection of HA/SA hydrogel loaded with PLGA rapamycin nanoparticle inhibits neointimal hyperplasia in a rat aortic wire injury model - Hualong Bai; Haoliang Wu; Liwei Zhang; Peng Sun; Yuanfeng Liu; Boao Xie; Cong Zhang; Shunbo Wei; Wang Wang; Jiangan Li (Drug Delivery and Translational Research, 2022)

Back-analysis of dynamic property of earth-rock dam considering parameter uncertainly - Hongyang Zhang; Ziyi Song; Yadong Sun; Zelin Ding; Xianqi Zhang; Pengju Han; Cong Ma (Arabian Journal of Geosciences, 2022)

Functional characterization of a Colchicum autumnale L. double-bond reductase (CaDBR1) in colchicine biosynthesis - Zhiqiang Xiong; Liang Wang; Jingyi Sun; Xuefei Jiang; Hanqing Cong; Huapeng Sun; Fei Qiao (Planta, 2022)

Sphingomicrobium nitratireducens sp. nov., isolated from a tidal flat in Guangxi - Hao You; Lin Xu; Yan-Hui Kong; Cong Sun; Peng Zhou; Xue-Wei Xu (Archives of Microbiology, 2022)

Cerebellar injury induced by cadmium via disrupting the heat-shock response - Shao-Shuai Bi; Milton Talukder; Xue-Tong Sun; Mei-Wei Lv; Jing Ge; Cong Zhang; Jin-Long Li (Environmental Science and Pollution Research, 2022)

Paracandidimonas lactea sp. nov., a urea-utilizing bacterium isolated from landfill - Chu Zhang; Qian Pu; Jun-jie Ying; Ying Chen; Cheng-ze Li; Hang-tao Wu; Bin-jie Wang; Yu-han Zhang; Guo-hong Zeng; Ou Li; Xiu-fang Hu; Cong Sun (Archives of Microbiology, 2022)

Essential role of ascO for virulence of Aeromonas veronii and inducing apoptosis - Tong Zhao; Bintong Yang; Hongjin Li; Aidong Qian; Wei Cong; Wuwen Sun; Yuanhuan Kang (Journal of Fish Diseases, 2022)
Aeromonas veronii is a significant pathogen that is capable of infecting humans, animals, and aquatic animals. The type III secretion system (T3SS) is intimately associated with bacterial pathogenicity. The ascO gene is an important core component of T3SS in A. veronii , but its function is still unclear. The ascO gene of A. veronii TH0426 was deleted by using the pRE112 suicide plasmid to study its function. The study results showed that the ability of ∆ ascO to adhere and invade EPC cells was significantly reduced by 1.28 times. The toxicity of the mutant strain Δ ascO to EPC cells was consistently significantly lower than wild‐type strain TH0426 at 1, 2, and 4 h. The LD50 values of ∆ ascO against zebrafish and Carassius auratus ( C. auratus ) were 53 and 15 times that of the wild‐type strain. In addition, the bacterial load of the mutant strain Δ ascO in blood, heart, liver, and spleen was lower than wild‐type strain TH0426. The Hoechst staining showed that the apoptotic degree of EPC cells induced by the mutant strain Δ ascO was lower than that of the wild‐type strain TH0426. Furthermore, real‐time quantitative PCR (RT‐qPCR) analysis revealed lower expression levels of pro‐apoptotic genes (including cytC , cas3 , cas9 , TNF‐α, and IL‐1β) in C. auratus tissues infected with the mutant strain Δ ascO compared to the wild‐type strain TH0426. The results of in vivo and in vitro experiments have shown that ascO gene mutation can reduce the adhesion and toxicity of A. veronii to EPC and reduce the level of apoptosis induced by A. veronii . As a result, these insights will help further elucidate the function of the ascO gene and thus contribute to understanding the pathogenesis of A. veronii .

An analysis of the effects of human capital on green growth: effects and transmission channels - Daxu Liu; Guanzhuo Wang; Cong Sun; Muhammad Tariq Majeed; Zubaria Andlib (Environmental Science and Pollution Research, 2022)

Complex carotid artery segmentation in multi-contrast MR sequences by improved optimal surface graph cuts based on flow line learning - Chenglu Zhu; Xiaoyan Wang; Shengyong Chen; Zhongzhao Teng; Cong Bai; Xiaojie Huang; Ming Xia; Zhanpeng Shao; Zheng Gu; Peiliang Sun (Medical & Biological Engineering & Computing, 2022)

Adipose Mesenchymal Stem Cell-Derived Exosomes Promote Wound Healing Through the WNT/β-catenin Signaling Pathway in Dermal Fibroblasts - Cong Li; Yu An; Yu Sun; Fan Yang; Quanchen Xu; Zhiguo Wang (Stem Cell Reviews and Reports, 2022)
The differentiation, migration, and proliferation of skin fibroblasts are identified as key factors in cutaneous wound healing. Adipose-derived mesenchymal stem cells (ADMSCs) and their exosomes (ADMSC-Exos) have been considered as potential therapeutic tools for tissue regeneration; however, the underlying mechanisms on cutaneous wound healing are still not well understood. In this study, we successfully obtained ADMSC-Exos and found ADMSC-Exos significantly promoted the migration and proliferation of fibroblasts in a dose-dependent manner in vitro. The expression levels of COL-I and COL-III in fibroblasts treated with ADMSC-Exos were significantly increased, while the expression level of α-SMA was decreased. In addition, the enhanced protein expression of WNT2b and β-catenin confirmed the activation of the WNT/β-catenin signaling pathway and the WNT/β-catenin inhibitor (XAV939) reversed the promoting effect of ADMSC-Exos on wound healing and the β-catenin expression. Taken together, our study partially elucidates the mechanism of ADMSC-Exos in wound healing, illustrating the potential of ADMSC-Exos as a new therapeutic approach to promote skin wound healing. Graphical Abstract

Hydrogels for the removal of the methylene blue dye from wastewater: a review - Yinchuan Yang; Qinlin Zhu; Xuwen Peng; Jingjing Sun; Cong Li; Xinmiao Zhang; Hao Zhang; Jiabin Chen; Xuefei Zhou; Hongbo Zeng; Yalei Zhang (Environmental Chemistry Letters, 2022)

Structural analysis and in vitro antitumor effect of polysaccharides from Pholiota adiposa - Jiao Zhou; Jinhua Gong; Yangyang Chai; Dehai Li; Cong Zhou; Changyan Sun; Joe M. Regenstein (Glycoconjugate Journal, 2022)

Hydrodynamic and Flow Field Characteristics of Water Jet Propulsion under Mooring Conditions - Dagang Zhao; Yang Zhang; Qian He; Cong Sun; Mingqi Bi (Journal of Marine Science and Engineering, 2022)
The acceleration characteristics of a water jet-propelled ship during startup are related to its performance under mooring conditions. Water jet propulsion cavitation during startup increases the vibration and noise of the whole ship. Therefore, accurately predicting and analyzing the performance, hydrodynamics and flow field characteristics of water jet-propelled ships under mooring conditions can help elucidate the startup characteristics of the ships and optimize their acceleration strategies. In this study, the hydrodynamic and flow field characteristics of water jet propulsion and water jet propulsion ships under mooring conditions were studied using three-dimensional numerical modeling. First, the hydrodynamic performance of the water jet propeller was analyzed, and the relevant flow field law was derived. Then, the hydrodynamic performance, internal and external flow field characteristics, pulsation pressure and flow rate at the nozzle, and pulsation pressure at the monitoring points around the impeller of the water jet propulsion ship model were analyzed under mooring conditions. We obtained the open-water law for the water jet propeller and the hydrodynamic force and flow field law for a two-pump water jet propulsion ship. The ship model developed in this study provides a good theoretical foundation for further research on water jet propulsion.

CHMP1A suppresses the growth of renal cell carcinoma cells via regulation of the PI3K/mTOR/p53 signaling pathway - Youping Wu; Yueguo Wu; Cong Xu; Wei Sun; Zhenqiang You; Yin Wang; Sheng Zhang (Genes & Genomics, 2022)

Research on the layout optimization and utilization of floor gas extraction roadway: a case study in Shoushan No.1 Coal Mine, China - Xiong Ding; Cheng Zhai; Jizhao Xu; Xu Yu; Yong Sun; Yuzhou Cong; Yangfeng Zheng; Wei Tang (Arabian Journal of Geosciences, 2022)

Identifying factors that affect environmental air quality using geographical detectors in the NKEFAs of China - Jie Xu; Haijiang Liu; Baolin Li; Xizhang Gao; Pingjing Nie; Cong Sun; Ziheng Jin; Dechao Zhai (Frontiers of Earth Science, 2022)

Mechanical properties distribution of lime-fly ash solidified oil contaminated soil in a coastal environment - Min Li; Cong Ma; Zhao Ming Sun; Xin Yu Yao (European Journal of Environmental and Civil Engineering, 2022)

Carbon sequestration and nutrients improvement meditated by biochar in a 3-year vegetable rotation system - Jining Zhang; Xianxian Zhang; Huifeng Sun; Cong Wang; Sheng Zhou (Journal of Soils and Sediments, 2022)

Using HYDRUS-2D model to simulate the water flow and nitrogen transport in a paddy field with traditional flooded irrigation - Xiaoying Sun; Juxiu Tong; Cong Liu; Yanbao Ma (Environmental Science and Pollution Research, 2022)

Unraveling the distribution patterns of near-surface temperature lapse rates in the Northwestern Kunlun Mountains - Cong-jian Sun; Wei Chen; Yan-jun Shen (Journal of Mountain Science, 2022)

Bacterial taxa have different responses to alterations in soil variables along a degradation gradient in the Napahai wetlands - Mei Lu; Cong Li; Yulian Ren; Xiangyang Sun; Jun Feng (Arabian Journal of Geosciences, 2022)

Application of ADSCs and their Exosomes in Scar Prevention - Cong Li; Shuqiang Wei; Quanchen Xu; Yu Sun; Xuchao Ning; Zhiguo Wang (Stem Cell Reviews and Reports, 2022)
Scar is a common way of healing after tissue injury. The poor scar healing will not only cause dysfunction of tissues and organs but also affect the appearance of the patients’ body surface, which causes the pressure of life and spirit to the patients. However, the formation of scar tissue is an extremely complex process and its mechanism is not fully understood. At present, there is no treatment method to eliminate scars completely. Fibroblasts are the most abundant cells in the dermis, which have the ability to synthesize and remodel extracellular matrix (ECM). Myofibroblasts actively participate in the wound healing process and influence the outcome. Therefore, both of them play important roles in wound healing and scar formation. Adipose tissue-derived stem cells (ADSCs) are pluripotent stem cells that can act on target cells by paracrine. Adipose tissue stem cell-derived exosomes (ADSC-Exos) are important secretory substances of ADSCs. They are nanomembrane vesicles that can transport a variety of cellular components and fuse with target cells. In this review, we will discuss the effects of ADSCs and ADSC-Exos on the behavior of fibroblasts and myofibroblasts during wound healing and scarring stage in combination with recent studies. Graphical Abstract

The adaptation mechanism based on an integrated vulnerability assessment of potato production to climate change in Inner Mongolia, China - Na Huang; Jialin Wang; Yu Song; Yuying Pan; Guolin Han; Ziyuan Zhang; Shangqian Ma; Guofeng Sun; Cong Liu; Zhihua Pan (Mitigation and Adaptation Strategies for Global Change, 2022)

The impact of Typhoon Lekima (2019) on East China: a postevent survey in Wenzhou City and Taizhou City - Cong Zhou; Peiyan Chen; Shifang Yang; Feng Zheng; Hui Yu; Jie Tang; Yi Lu; Guoming Chen; Xiaoqing Lu; Xiping Zhang; Jing Sun (Frontiers of Earth Science, 2022)

Damage and Failure of Hot Dry Rock under Cyclic Liquid Nitrogen Cold Shock Treatment: A Non-destructive Ultrasonic Test Method - Yong Sun; Cheng Zhai; Jizhao Xu; Xu Yu; Yuzhou Cong; Yangfeng Zheng; Wei Tang; Yujie Li (Natural Resources Research, 2022)

Research development and trends of benzene-induced leukemia from 1990 to 2019-A bibliometric analysis - Qianyu Sun; Boshen Wang; Shouxiang Xu; Xiaowei Cong; Yuepu Pu; Juan Zhang (Environmental Science and Pollution Research, 2022)

Reactive oxygen species mediate the relationship between mitochondrial function and delayed luminescence during senescence of strawberry (Fragaria ananassa) fruits - Cong Sun; Jiecai Liu; Huan Liu; Jinli Guo (Acta Physiologiae Plantarum, 2022)

Petrogenesis of the Late Triassic Mengsong strongly peraluminous granites in the southeastern Tibetan Plateau: highly fractionated from crystal mush - Feng Cong; Fu-Yuan Wu; Wen-Chang Li; De-Feng He; Zai-Bo Sun; Xiao-Ming Huang; Zhi-Zhong Hu; Han Zhao (International Geology Review, 2022)

Estimate greenhouse gas emissions from water-saving and drought-resistance rice paddies by deNitrification-deComposition model - Xianxian Zhang; Huifeng Sun; Junguo Bi; Bo Yang; Jining Zhang; Cong Wang; Sheng Zhou (Clean Technologies and Environmental Policy, 2022)

Halomonas populi sp. nov. isolated from Populus euphratica - Lin Xu; Jun-Jie Ying; Yuan-Chun Fang; Ran Zhang; Jia Hua; Min Wu; Bing-Nan Han; Cong Sun (Archives of Microbiology, 2022)

MEHP induces pyroptosis and autophagy alternation by cathepsin B activation in INS-1 cells - Lijie Jiang; Tianming Qiu; Xiaofeng Yao; Huangben Chen; Kun Yao; Xiance Sun; Guang Yang; Liping Jiang; Cong Zhang; Ningning Wang; Hongying Zhang; Xiaofang Liu (Environmental Science and Pollution Research, 2021)

Marinomonas vulgaris sp. nov., a marine bacterium isolated from seawater in a coastal intertidal zone of Zhoushan island - Jun-Jie Ying; Yuan-Chun Fang; Yong-Lian Ye; Zhi-Cheng Wu; Lin Xu; Bing-Nan Han; Cong Sun (Archives of Microbiology, 2021)

Dynamical influence of the Madden-Julian oscillation on the Northern Hemisphere mesosphere during the boreal winter - Cong Sun; Chengyun Yang; Tao Li (Science China Earth Sciences, 2021)

An overview of chitosan and its application in infectious diseases - Qingye Meng; Ying Sun; Hailin Cong; Hao Hu; Fu-Jian Xu (Drug Delivery and Translational Research, 2021)

Aestuariibaculum sediminum sp. nov., a marine bacterium isolated from a tidal flat in Zhoushan - Zhi-Cheng Wu; Xin-Yin Zhang; Cong Sun; Lin Xu; Ge-Yi Fu; Xue-Wei Xu (Archives of Microbiology, 2021)

Antibiotic usage and resistance in animal production in Vietnam: a review of existing literature - Khanh Nguyen Di; Duy Toan Pham; Tay Sun Tee; Quach An Binh; Thanh Cong Nguyen (Tropical Animal Health and Production, 2021)

Foetidibacter luteolus gen. nov., sp. nov., isolated from the rhizosphere of Salvia miltiorrhiza - Qian Pu; Guo-hong Zeng; Gui-wei Wang; Ling-er Lu; Ang Li; Xu-rui Cheng; Xue-ying Wang; Ou Li; Cong Sun; Xiu-fang Hu (Archives of Microbiology, 2021)

De novo hydroponics system efficiency for the cuttings of alfalfa (Medicago sativa L.) - Zhili Zhao; Wenyu Zhang; Yang Liu; Shuai Li; Wu Yao; Xiaohui Sun; Siyu Li; Lichao Ma; Juan Sun; Qingchuan Yang; Yongxiang Li; Guofeng Yang; et al. (Physiology and Molecular Biology of Plants, 2021)
The legume plant alfalfa ( Medicago sativa L.) is a widely cultivated perennial forage due to its high protein content, palatability, and strong adaptability to diverse agro-ecological zones. Alfalfa is a self-incompatible cross-pollinated autotetraploid species with tetrasomic inheritance. Therefore, maintaining excellent traits through seed reproduction is a prime challenge in alfalfa. However, the cutting propagation technology could enable consistent multiplication of quality plants that are genetically identical to the parent plant. The current study aimed to develop a simple, cost-effective, reproducible, and efficient hydroponic cutting method to preserve alfalfa plants and for molecular research. In this study, alfalfa landrace ‘Wudi’ was grown in hydroponics for 30 days and used as source material for cuttings. The top, middle and bottom sections of its stem were used as cuttings. The rooting rate, root length, and stem height of the different stem sections were compared to determine the best segment for alfalfa propagation in four nutrient treatments (H M , H M + 1/500H, H M + 1/1000H and d H M + 1/2000H). After 21 days of culture, the rooting rates of all the three stem types under four cutting nutrient solutions were above 78%. The rooting rate of the middle and bottom parts in H M + 1/1000 H and H M + 1/2000 H nutrient solutions reached more than 93%, with a higher health survey score (> 4.70). In conclusion, this study developed a de novo cutting propagation method that can be used to conserve and propagate germplasm in breeding programs and research. This method is a new report on the cutting propagation of alfalfa by hydroponics, which could supplement the existing cutting propagation methods.

Molecular cloning, characterization and expression analysis of three key starch synthesis-related genes from the bulb of a rare lily germplasm, Lilium brownii var. giganteum - Yun Wu; Minyi Sun; Shiqi Li; Ruihan Min; Cong Gao; Qundan Lyu; Ziming Ren; Yiping Xia (Journal of Zhejiang University-SCIENCE B, 2021)

Alterinioella nitratireducens gen. nov., sp. nov., Isolated from Seawater in the West Pacific Ocean - Yan-Hui Kong; Cong Sun; Li-Li Guo; Lin Xu; Yue-Hong Wu; Xue-Wei Xu (Current Microbiology, 2021)

Impacts of metallic nanoparticles and transformed products on soil health - Wenjie Sun; Fugen Dou; Cong Li; Xingmao Ma; Lena Q. Ma (Critical Reviews in Environmental Science and Technology, 2021)

Experimental Study on the Unsteady Natural Cloud Cavities: Influence of Cavitation Number on Cavity Evolution and Pressure Pulsations - Tiezhi Sun; Xiaoshi Zhang; Jianyu Zhang; Cong Wang (Journal of Marine Science and Engineering, 2021)
High-speed underwater vehicles are subjected to complex multiphase turbulent processes, such as the growth, development, shedding, and collapse of cavitation bubbles. To study the cavity evolution and pressure pulsation characteristics, in this paper, cloud cavitation over a conical axisymmetric test body with four pressure sensors is investigated. A multi-field simultaneous measurement experiment method for the natural cavitation of underwater vehicles is proposed to understand the relationship between cavity evolution and instantaneous pressure. The results show that the evolution of cloud cavitation can be mainly divided into three stages: (I) the growth process of the attached cavity, (II) the shedding process of the attached cavity, and (III) the collapse of detached cavities. The evolution of the attached cavity and collapse of the large-scale shedding cavity will cause strong pressure pulsations. It is found that the cavitation number plays an important role in cavitation evolution and pressure pulsation. Interestingly, as the cavitation number decreases, the fluctuation intensity of cavitation increases significantly and gradually presents obvious periodicity. Moreover, the unstable cavitating flow patterns are highly correlated with the time domain and frequency domain characteristics of pressure. Especially, as the cavitation number decreases, the main frequency becomes lower and the pressure band becomes more concentrated.

Experimental study on the formation and migration of submarine sandwaves under wave-only and combined wave-current conditions - Wang Cong; Sun Yongfu; Liu Zhenwen; Zhou Qikun; Zang Zhipeng (Marine Georesources & Geotechnology, 2021)

Marinobacter caseinilyticus sp. nov., Isolated from Saline Soil - Yanfang Nie; Xin Su; Dildar Wu; Ran Zhang; Ruijun Wang; Zhe Zhao; Maripat Xamxidin; Cong Sun; Min Wu (Current Microbiology, 2021)

The role of MYB proto-oncogene like 2 in tamoxifen resistance in breast cancer - Xia Li; Xi Zhang; Cong-Cong Wu; Ping-Ping Li; Yi-Mou Fu; Li-Hua Xie; Shuang-Shuang Sun; Ying-Ying Zhou; Bao-Ling Zhu (Journal of Molecular Histology, 2021)

Transcriptome landscapes of differentially expressed genes related to fat deposits in Nandan-Yao chicken - Cong Xiao; Tiantian Sun; Zhuliang Yang; Wenwen Xu; Juan Wang; Linghu Zeng; Jixian Deng; Xiurong Yang (Functional & Integrative Genomics, 2021)

LncRNA LEF1-AS1 promotes osteogenic differentiation of dental pulp stem cells via sponging miR-24-3p - Yuexia Wu; Keqian Lian; Cong Sun (Molecular and Cellular Biochemistry, 2020)

Numerical and Experimental Study of Flow Field between the Main Hull and Demi-Hull of a Trimaran - Cong Sun; Chunyu Guo; Chao Wang; Lianzhou Wang; Jianfeng Lin (Journal of Marine Science and Engineering, 2020)
The interactions between the main hull and demi-hull of trimarans have been arousing increasing attention, and detailed circumferential flow fields greatly influence trimaran research. In this research, the unsteady wake flow field of a trimaran was obtained by Reynolds-Averaged Navier-Stokes (RANS) equations on the basis of the viscous flow principles with consideration of the heaving and pitching of the trimaran. Then, we designed an experimental method based on particle-image velocimetry (PIV) and obtained a detailed flow field between the main hull and demi-hull of the trimaran. A trimaran model with one demi-hull made of polycarbonate material with 90% light transmission rate and a refractive index 1.58 (close to that of water 1.33) was manufactured as the experiment sample. Using polycarbonate material, the laser-sheet light-source transmission and high-speed camera recording problems were effectively rectified. Moreover, a nonstandard calibration was added into the PIV flow field measurement system. Then, we established an inverse three-dimensional (3D) distortion coordinate system and obtained the corresponding coordinates by using optics calculations. Further, the PIV system spatial mapping was corrected, and the real flow field was obtained. The simulation results were highly consistent with the experimental data, which showed the methods established in this study provided a strong reference for obtaining the detailed flow field information between the main hull and demi-hull of trimarans.

Sustaining Attention for a Prolonged Duration Affects Dynamic Organizations of Frequency-Specific Functional Connectivity - Jia Liu; Yongjie Zhu; Hongjin Sun; Tapani Ristaniemi; Fengyu Cong (Brain Topography, 2020)
Sustained attention encompasses a cascade of fundamental functions. The human ability to implement a sustained attention task is supported by brain networks that dynamically formed and dissolved through oscillatory synchronization. The decrement of vigilance induced by prolonged task engagement affects sustained attention. However, little is known about which stage or combinations are affected by vigilance decrement. Here, we applied an analysis framework composed of weighted phase lag index (wPLI) and tensor component analysis (TCA) to an EEG dataset collected during 80 min sustained attention task to examine the electrophysiological basis of such effect. We aimed to characterize the phase-coupling networks to untangle different phases involved in sustained attention and study how they are modulated by vigilance decrement. We computed the time–frequency domain wPLI from each block and subject and constructed a fourth-order tensor, containing the time, frequency, functional connectivity (FC), and blocks × subjects. This tensor was subjected to the TCA to identify the interacted and low-dimensional components representing the frequency-specific dynamic FC (fdFC). We extracted four types of neuromakers during a sustained attention task, namely the pre-stimulus alpha right-lateralized parieto-occipital FC, the post-stimulus theta fronto-parieto-occipital FC, delta fronto-parieto-occipital FC, and beta right/left sensorimotor FCs. All these fdFCs were impaired by vigilance decrement. These fdFCs, except for the beta left sensorimotor network, were restored by rewards, although the restoration by reward in the beta right sensorimotor network was transient. These findings provide implications for dissociable effects of vigilance decrement on sustained attention by utilizing the tensor-based framework.

Low Serum Uric Acid Levels Promote Hypertensive Intracerebral Hemorrhage by Disrupting the Smooth Muscle Cell-Elastin Contractile Unit and Upregulating the Erk1/2-MMP Axis - Ning Xiao; Tian-long Liu; Hao Li; Hao-chen Xu; Jing Ge; Hong-yan Wen; Cong-xia Bai; Li Song; Ying-ying Sun; Yin-hui Zhang; Ru-tai Hui; Wei-hua Song; et al. (Translational Stroke Research, 2020)

Overexpression of PREX1 in oral squamous cell carcinoma indicates poor prognosis - Shu-Cheng Wan; Hao Wu; Hao Li; Wei-Wei Deng; Yao Xiao; Cong-Cong Wu; Lei-Lei Yang; Wen-Feng Zhang; Zhi-Jun Sun (Journal of Molecular Histology, 2020)

Description of Erythrobacter mangrovi sp. nov., an aerobic bacterium from rhizosphere soil of mangrove plant (Kandelia candel) - Yang-Hui Ye; Nusratgul Anwar; Maripat Xamxidin; Ran Zhang; Cen Yan; Yan-Fang Nie; Zhe Zhao; Cong Sun; Min Wu (Antonie van Leeuwenhoek, 2020)

Prenatal di-(2-ethylhexyl) phthalate maternal exposure impairs the spatial memory of adult mouse offspring in a phase- and gender-dependent manner - Ling-Li Zhao; Ru Shen; Cong-Cong Sun; Shan-Yu Zhang; Bo Wang; Mei-Fang Sun; De-Xiang Xu (Environmental Science and Pollution Research, 2020)

Large Eddy Simulation of Microbubble Drag Reduction in Fully Developed Turbulent Boundary Layers - Tongsheng Wang; Tiezhi Sun; Cong Wang; Chang Xu; Yingjie Wei (Journal of Marine Science and Engineering, 2020)
Microbubble drag reduction has good application prospects. It operates by injecting a large number of bubbles with tiny diameters into a turbulent boundary layer. However, its mechanism is not yet fully understood. In this paper, the mechanisms of microbubble drag reduction in a fully developed turbulent boundary layer over a flat-plate is investigated using a two-way coupled Euler-Lagrange approach based on large eddy simulation. The results show good agreement with theoretical values in the velocity distribution and the distribution of fluctuation intensities. As the results show, the presence of bubbles reduces the frequency of bursts associated with the sweep events from 637.8 Hz to 611.2 Hz, indicating that the sweep events, namely the impacting of high-speed fluids on the wall surface, are suppressed and the streamwise velocity near the wall is decreased, hence reducing the velocity gradient at the wall and consequently lessening the skin friction. The suppression on burst frequency also, with the fluid fluctuation reduced in degree, decreases the intensity of vortices near the wall, leading to reduced production of turbulent kinetic energy.

Fine mapping QSc.VR4, an effective and stable scald resistance locus in barley (Hordeum vulgare L.), to a 0.38-Mb region enriched with LRR-RLK and GLP genes - Yonggang Wang; Yanhao Xu; Sanjiv Gupta; Yi Zhou; Hugh Wallwork; Gaofeng Zhou; Sue Broughton; Xiao-Qi Zhang; Cong Tan; Sharon Westcott; David Moody; Dongfa Sun; et al. (Theoretical and Applied Genetics, 2020)

EGF neutralization antibodies attenuate liver fibrosis by inhibiting myofibroblast proliferation in bile duct ligation mice - Hufeng Xu; Lin Liu; Min Cong; Tianhui Liu; Shujie Sun; Hong Ma; Hong You; Jidong Jia; Ping Wang (Histochemistry and Cell Biology, 2020)

A special symptom of olfactory dysfunction in coronavirus disease 2019: report of three cases - Chen Chen; Moxian Chen; Cong Cheng; Yun Chi; Zhiliang Hu; Yuan Liu; Shan Huang; Yanling Lv; Chongfeng Liang; Damin Jiao; Yongxiang Yi; Xia Zhang; et al. (Journal of NeuroVirology, 2020)

Year-to-year climate variability affects methane emission from paddy fields under irrigated conditions - Huifeng Sun; Sheng Zhou; Jining Zhang; Xianxian Zhang; Cong Wang (Environmental Science and Pollution Research, 2020)

The Complete Genome of Emcibacter congregatus ZYLT, a Marine Bacterium Encoding a CRISPR-Cas 9 Immune System - Zhe Zhao; Rui-an Zhang; Ge-yi Fu; Ran Zhang; Yan-fang Nie; Cong Sun; Min Wu (Current Microbiology, 2020)

Numerical Simulation on Vortex Shedding from a Hydrofoil in Steady Flow - Jian Hu; Zibin Wang; Wang Zhao; Shili Sun; Cong Sun; Chunyu Guo (Journal of Marine Science and Engineering, 2020)
This paper presents a numerical modeling procedure for the idealization of vortex shedding effects in the wake flow field of a NACA0009 hydrofoil. During the simulation, the lift and drag acting on the hydrofoil were monitored, and the vortex-shedding frequency of the hydrofoil was analyzed. The effects of inflow velocity, trailing-edge thickness, angle of attack, and maximum hydrofoil thickness on vortex shedding were investigated. The results indicate that an increase in the inflow velocity led to an increase in the vortex-shedding frequency and a negligible change in the Strouhal number. Furthermore, as the thickness of the trailing edge increased, the vortex-shedding frequency decreased gradually, whereas the Strouhal number first increased and then decreased. Vortex shedding and lift curve oscillations ceased altogether after the angle of attack of the hydrofoil increased beyond a certain threshold. When the maximum hydrofoil thickness was increased while keeping the thickness and chord length of the trailing edge constant, the vortex-shedding frequency decreased.

Atorvastatin ameliorates depressive behaviors and neuroinflammatory in streptozotocin-induced diabetic mice - Zhang Hai-Na; Yu Xu-Ben; Tang Cong-Rong; Cao Yan-Cheng; Yang Fan; Xu Lei-Mei; Sun Ruo-Lan; Ye-Zi; Wang Ye-Xuan; Liang Jing (Psychopharmacology, 2020)

ABA and sucrose co-regulate strawberry fruit ripening and show inhibition of glycolysis - Ya Luo; Cong Ge; Yajie Ling; Fan Mo; Min Yang; Leiyu Jiang; Qing Chen; Yuanxiu Lin; Bo Sun; Yong Zhang; Yan Wang; Mengyao Li; et al. (Molecular Genetics and Genomics, 2020)

Characterization of a novel echovirus 21 strain isolated from a healthy child in China in 2013 - Hongbo Liu; Shanri Cong; Danhan Xu; Keqin Lin; Xiaoqin Huang; Hao Sun; Zhaoqing Yang; Shaohui Ma (Archives of Virology, 2020)

Anaerophilus nitritogenes gen. nov., sp. nov., isolated from salt lake sediment in Xinjiang Province, China - Ran Zhang; Yan Zeng; Tian-Qi Wang; Xin-Mei Wang; Yi-Yu Shi; Jia-Tian Zou; Cong Sun; Gui-Shan Zhang; Wei-Yan Zhang; Min Wu (Antonie van Leeuwenhoek, 2020)

Unsupervised classification for PolSAR images based on multi-level feature extraction - Ping Han; Binbin Han; Xiaoguang Lu; Runmin Cong; Dandan Sun (International Journal of Remote Sensing, 2020)

Quantitative evaluation of rock brittleness based on crack initiation stress and complete stress–strain curves - Guoqing Chen; Wanzeng Jiang; Xiang Sun; Cong Zhao; Chang’An Qin (Bulletin of Engineering Geology and the Environment, 2019)

Algicoccus marinus gen. nov. sp. nov., a marine bacterium isolated from the surface of brown seaweed Laminaria japonica - Jun-Jie Ying; Shun-Li Zhang; Chao-Yu Huang; Lin Xu; Zhe Zhao; Min Wu; Cong Sun (Archives of Microbiology, 2019)

Slope stability analysis and protection measures in bridge and tunnel engineering: a practical case study from Southwestern China - Shangqu Sun; Shucai Li; Liping Li; Shaoshuai Shi; Jing Wang; Jie Hu; Cong Hu (Bulletin of Engineering Geology and the Environment, 2019)

Microstructure and strength features of warm and ice-rich frozen soil treated with high-performance cements - Gao-chen Sun; Jian-ming Zhang; Ying-sheng Dang; Cong Ding (Journal of Mountain Science, 2019)

Classical swine fever virus C-strain with eight mutation sites shows enhanced cell adaptation and protects pigs from lethal challenge - Tong Cao; Shengnan Zhang; Xiaoye Li; Yonghao Xu; Zuohuan Wang; Cong Chen; Narayan Paudyal; Xiaoliang Li; Jianhe Sun; Weihuan Fang (Archives of Virology, 2019)

Understanding Mercury Cycling in Tibetan Glacierized Mountain Environment: Recent Progress and Remaining Gaps - Qianggong Zhang; Xuejun Sun; Shiwei Sun; Xiufeng Yin; Jie Huang; Zhiyuan Cong; Shichang Kang (Bulletin of Environmental Contamination and Toxicology, 2019)

Genetic analysis of cob resistance to F. verticillioides: another step towards the protection of maize from ear rot - Cong Mu; Jingyang Gao; Zijian Zhou; Zhao Wang; Xiaodong Sun; Xuecai Zhang; Huafang Dong; Yanan Han; Xiaopeng Li; Yabin Wu; Yunxia Song; Peipei Ma; et al. (Theoretical and Applied Genetics, 2019)

Characteristic and Functional Properties of Gelatin from the Bones of Alaska Pollock ( Theragra chalcogramma ) and Yellowfin Sole ( Limanda aspera ) with Papain-Aided Process - Hongbo Mi; Cong Wang; Jingxin Chen; Yongxia Xu; Xuepeng Li; Jianrong Li; Xiaotao Sun; Linchun Mao; Yongjun Ma; Minjun Lao (Journal of Aquatic Food Product Technology, 2019)

Characteristics of salt contents in soils under greenhouse conditions in China - Huaiwei Sun; Cong Wei; Wensheng Xu; Jinzhong Yang; Xiugui Wang; Yuanfeng Qiu (Environmental Science and Pollution Research, 2019)

Nemertean taxonomy—Implementing changes in the higher ranks, dismissing Anopla and Enopla - Malin Strand; Jon Norenburg; José E. Alfaya; Fernando Ángel Fernández‐Álvarez; Håkan S Andersson; Sonia C. S. Andrade; Thomas Bartolomaeus; Patrick Beckers; Gregorio Bigatti; Irina Cherneva; Alexey Chernyshev; Brian M. Chung; et al. (Zoologica Scripta, 2019)

MiR-92a inhibits fibroblast-like synoviocyte proliferation and migration in rheumatoid arthritis by targeting AKT2 - Fang-Yuan Yu; Cong-Qin Xie; Chang-liang Jiang; Ji-Tong Sun; Hui-Cheng Feng; Chao Li; Xun-Wu Huang (Journal of Biosciences, 2018)

Confluentibacter flavum sp. nov., Isolated from the Saline Lake - Yu. Li; Xin-Jun Hou; Xia Shen; Shuai-Bo Han; Zhao Ju; Zhe Zhao; Xiao-Yun Yu; Min Wu; Cong Sun (Current Microbiology, 2018)

Origin of Early Cretaceous Guandian adakitic pluton in central eastern China: partial melting of delaminated lower continental crust triggered by ridge subduction - Ze-Bin Luo; Shuo Xue; Li-Peng Zhang; He Li; Cong-Ying Li; Hong Zhang; Yu-Long Liu; Ming-Xing Ling; Weidong Sun (International Geology Review, 2018)

Comparative pharmacokinetics study of five alkaloids in rat plasma and related compound–herb interactions mechanism after oral administration of Shuanghua Baihe tablets - Xinyu Zhao; Yan Wang; Lu Zheng; Chengpeng Sun; Chao Wang; Haijian Cong; Ting Xiang; Lin Zhang; Houli Zhang; Sa deng; Baojing Zhang; Bin Wu; et al. (Natural Product Research, 2018)

Anxiolytic potency of iridoid fraction extracted from Valeriana jatamansi Jones and its mechanism: a preliminary study - Xue-Mei Zhang; Jia-Li Zhu; Yong Sun; Yao-Lan Dai; Xiu Chen; Jia-Hong Cao; Ruo-Cong Yang; Chang Chen; Chao-Ying Ma; Tian-E Zhang; Yun-Hui Chen; Zhi-Yong Yan (Natural Product Research, 2018)

Over-expression of IQGAP1 indicates poor prognosis in head and neck squamous cell carcinoma - Cong-Cong Wu; Hao Li; Yao Xiao; Lei-Lei Yang; Lei Chen; Wei-Wei Deng; Lei Wu; Wen-Feng Zhang; Zhi-Jun Sun (Journal of Molecular Histology, 2018)

Altered Profiles of Gut Microbiota in Klebsiella pneumoniae-Induced Pyogenic Liver Abscess - Nan Chen; Zong-Xin Ling; Tong-Tong Jin; Ming Li; Sheng Zhao; Li-Shuang Zheng; Xin Xi; Lin-Lin Wang; Ying-Ying Chen; Yue-Liang Shen; Li-Ping Zhang; Shao-cong Sun (Current Microbiology, 2018)

Cell shape can be uncoupled from formononetin induction in a novel cell line from Callerya speciosa - Fei Qiao; Xue-fei Jiang; Han-qing Cong; Hua-peng Sun; Li Li; Peter Nick (Plant Cell Reports, 2018)

Polyphasic taxonomic characterisation of a novel strain as Pararhizobium haloflavum sp. nov., isolated from soil samples near a sewage treatment tank - Xia Shen; Yu Li; Zhe Zhao; Yi-Fan Han; Wen-Wu Zhang; Xiao-Yun Yu; Chong-Ya Zhang; Cong Sun; Min Wu (Antonie van Leeuwenhoek, 2018)

Large soil organic carbon increase due to improved agronomic management in the North China Plain from 1980s to 2010s - Daorui Han; Martin Wiesmeier; Richard T. Conant; Anna Kühnel; Zhigang Sun; Ingrid Kögel‐Knabner; Ruixing Hou; Peifei Cong; Rubiao Liang; Zhu Ouyang (Global Change Biology, 2018)
Agricultural soils are widely recognized to be capable of carbon sequestration that contributes to mitigating CO 2 emissions. To better understand soil organic carbon ( SOC ) stock dynamics and its driving and controlling factors corresponding with a period of rapid agronomic evolution from the 1980s to the 2010s in the North China Plain ( NCP ), we collected data from two region‐wide soil sampling campaigns (in the 1980s and 2010s) and conducted an analysis of the controlling factors using the random forest model. Between the 1980s and 2010s, environmental (i.e. soil salinity/fertility) and societal (i.e. policy/techniques) factors both contributed to adoption of new management practices (i.e. chemical fertilizer application/mechanization). Results of our work indicate that SOC stocks in the NCP croplands increased significantly, which also closely related to soil total nitrogen changes. Samples collected near the surface (0–20 cm) and deeper (20–40 cm) both increased by an average of 9.4 and 5.1 Mg C ha −1 , respectively, which are equivalent to increases of 73% and 56% compared with initial SOC stocks in the 1980s. The annual carbon sequestration amount in surface soils reached 10.9 Tg C year −1 , which contributed an estimated 43% of total carbon sequestration in all of China's cropland on just 27% of its area. Successful desalinization and the subsequent increases in carbon (C) inputs, induced by agricultural projects and policies intended to support crop production (i.e. reconstruction of low yield farmland, and agricultural subsidies), combined with improved cultivation practices (i.e. fertilization and straw return) since the early 1980s were the main drivers for the SOC stock increase. This study suggests that rehabilitation of NCP soils to reduce salinity and increase crop yields have also served as a pathway for substantial soil C sequestration.

Restoration of SMN expression in mesenchymal stem cells derived from gene-targeted patient-specific iPSCs - Mai Feng; Cong Liu; Yan Xia; Bo Liu; Miaojin Zhou; Zhuo Li; Qianru Sun; Zhiqing Hu; Yanchi Wang; Lingqian Wu; Xionghao Liu; Desheng Liang (Journal of Molecular Histology, 2018)

Regulating the alky chain length of fatty acid-didanosine prodrugs and evaluating its role in albumin binding - Hongxiang Chen; Gang Wang; Lanzhen Sun; Huicong Zhang; Mengchi Sun; Jin Sun; Lei Shang; Cong Luo (Drug Delivery and Translational Research, 2018)

Echinacoside, a phenylethanoid glycoside from Cistanche deserticola, extends lifespan of Caenorhabditis elegans and protects from Aβ-induced toxicity - Wei Chen; Hong-Ru Lin; Cong-Min Wei; Xiao-Hua Luo; Meng-Lu Sun; Zhen-Zhou Yang; Xin-Yan Chen; Hong-Bing Wang (Biogerontology, 2018)

Individual and Combined Toxicities of Benzo[a]pyrene and 2,2′,4,4′-Tetrabromodiphenyl Ether on Early Life Stages of the Pacific Oyster, Crassostrea gigas - Jia Xie; Dinglong Yang; Xiyan Sun; Ruiwen Cao; Lizhu Chen; Qing Wang; Fei Li; Huifeng Wu; Chenglong Ji; Ming Cong; Jianmin Zhao (Bulletin of Environmental Contamination and Toxicology, 2017)

A Novel miRNA Sponge Form Efficiently Inhibits the Activity of miR393 and Enhances the Salt Tolerance and ABA Insensitivity in Arabidopsis thaliana - Ruicai Long; Mingna Li; Xiao Li; Yanli Gao; Tiejun Zhang; Yan Sun; Junmei Kang; Tenghua Wang; Lili Cong; Qingchuan Yang (Plant Molecular Biology Reporter, 2017)

Position and Angular Misalignment Analysis for Implantable Wireless Power Transfer System Based on Magnetic Resonance - Fei-Xiang Gong; Zhiqiang Wei; Haokun Chi; Bo Yin; Ying Sun; Yanping Cong; Mingui Sun (Journal of Medical and Biological Engineering, 2017)

Rockfall Hazard Assessment on Wangxia Rock Mass in Wushan (Chongqing, China) - Shang-qu Sun; Li-ping Li; Shu-cai Li; Qian-qing Zhang; Cong Hu (Geotechnical and Geological Engineering, 2017)

Newcastle disease virus-like particles induce dendritic cell maturation and enhance viral-specific immune response - Jing Qian; Jiaxin Ding; Renfu Yin; Yixue Sun; Cong Xue; Xiaohong Xu; Jianzhong Wang; Chan Ding; Shengqing Yu; Xiufan Liu; Shunlin Hu; Yanlong Cong; et al. (Virus Genes, 2017)

CRISPR/Cas9-mediated somatic and germline gene correction to restore hemostasis in hemophilia B mice - Cong Huai; Chenqiang Jia; Ruilin Sun; Peipei Xu; Taishan Min; Qihan Wang; Chengde Zheng; Hongyan Chen; Daru Lu (Human Genetics, 2017)

Identification and genetic mapping of a novel incompletely dominant yellow leaf color gene, Y1718, on chromosome 2BS in wheat - Lingli Zhang; Cong Liu; Xuyao An; Huiyu Wu; Yi Feng; Hui Wang; Daojie Sun (Euphytica, 2017)

Evapotranspiration estimation considering anthropogenic heat based on remote sensing in urban area - ZhenTao Cong; QiNing Shen; Lin Zhou; Ting Sun; JiaHong Liu (Science China Earth Sciences, 2017)

Gelatin microspheres containing calcitonin gene-related peptide or substance P repair bone defects in osteoporotic rabbits - Jianghao Chen; Wei Liu; Jinxiu Zhao; Cong Sun; Jie Chen; Kaijin Hu; Linlin Zhang; Yuxiang Ding (Biotechnology Letters, 2017)

The formation of porphyry copper deposits - Weidong Sun; Jin-tuan Wang; Li-peng Zhang; Chan-chan Zhang; He Li; Ming-xing Ling; Xing Ding; Cong-ying Li; Hua-ying Liang (Acta Geochimica, 2017)

Weak electric fields detectability in a noisy neural network - Jia Zhao; Bin Deng; Yingmei Qin; Cong Men; Jiang Wang; Xile Wei; Jianbing Sun (Cognitive Neurodynamics, 2017)

Genetic diversity of the genotype VII Newcastle disease virus: identification of a novel VIIj sub-genotype - Cong Xue; Yanlong Cong; Renfu Yin; Yixue Sun; Chan Ding; Shengqing Yu; Xiufan Liu; Shunlin Hu; Jing Qian; Qianliang Yuan; Mingxi Yang; Chunfeng Wang; et al. (Virus Genes, 2017)

Mitochondrial aldehyde dehydrogenase 2 deficiency aggravates energy metabolism disturbance and diastolic dysfunction in diabetic mice - Cong Wang; Fan Fan; Quan Cao; Cheng Shen; Hong Zhu; Peng Wang; Xiaona Zhao; Xiaolei Sun; Zhen Dong; Xin Ma; Xiangwei liu; Shasha Han; et al. (Journal of Molecular Medicine, 2016)

TRI6 and TRI10 play different roles in the regulation of deoxynivalenol (DON) production by cAMP signalling in Fusarium graminearum - Cong Jiang; Chengkang Zhang; Chunlan Wu; Panpan Sun; Rui Hou; Huiquan Liu; Chenfang Wang; Jin‐Rong Xu (Environmental Microbiology, 2016)
Summary The biosynthesis of mycotoxin deoxynivalenol (DON) in Fusarium graminearum is regulated by two pathway‐specific transcription factors Tri6 and Tri10 and affected by various host and environmental factors. In this study, we showed that cyclic adenosine monophosphate (cAMP) treatment induced DON production by stimulating TRI gene expression and DON‐associated cellular differentiation in F. graminearum . Interestingly, exogenous cAMP had no effects on the tri6 mutant but partially recovered the defect of tri10 mutant in DON biosynthesis. Although the two cAMP phosphodiesterase genes PDE1 and PDE2 had overlapping functions in vegetative growth, conidiation, sexual reproduction and plant infection, deletion of PDE2 but not PDE1 activated intracellular PKA activities and increased DON production. Whereas the tri6 pde2 mutant failed to produce DON, the tri10 pde2 double mutant produced a significantly higher level of DON than the tri10 mutant. Cellular differentiation associated with DON production was stimulated by exogenous cAMP or deletion of PDE2 in both tri10 and tri6 mutants. These data indicate that TRI6 is essential for the regulation of DON biosynthesis by cAMP signalling but elevated PKA activities could partially bypass the requirement of TRI10 for TRI gene‐expression and DON production, and Pde2 is the major cAMP phosphodiesterase to negatively regulate DON biosynthesis in F. graminearum .

Metabolic engineering of Corynebacterium glutamicum for methionine production by removing feedback inhibition and increasing NADPH level - Ying Li; Hua Cong; Bingnan Liu; Jinzhu Song; Xueying Sun; Junzheng Zhang; Qian Yang (Antonie van Leeuwenhoek, 2016)

Erratum to: Initiation and evolution of the South China Sea: an overview - Wei-dong Sun; Chiou-ting Lin; Chan-chan Zhang; Yong-bin Hu; Ming-xing Ling; Xing Ding; Cong-ying Li; He Li; Kai Wu; Wei-ming Fan (Acta Geochimica, 2016)

Dietary Selenium Status Regulates the Transcriptions of Selenoproteome and Activities of Selenoenzymes in Chicken Kidney at Low or Super-nutritional Levels - Jing-Xiu Xu; Cong Zhang; Chang-Yu Cao; Shi-Yong Zhu; Hui Li; Yan-Chun Sun; Jin-Long Li (Biological Trace Element Research, 2016)

Morphology, sex steroid level and gene expression analysis in gonadal sex reversal of triploid female (XXX) rainbow trout (Oncorhynchus mykiss) - Gefeng Xu; Tianqing Huang; Xian Jin; Cunhe Cui; Depeng Li; Cong Sun; Ying Han; Zhenbo Mu (Fish Physiology and Biochemistry, 2016)

Preparation of Triacylglycerols Enriched in DHA from Single Cell Glycerides via Molecular Distillation and Enzymatic Glycerolysis - Zhaomin Sun; Lu Yang; Changhu Xue; Zhengxia Guo; Haihua Cong; Yuming Wang; Yong Xue; Jingfeng Wang (Journal of Aquatic Food Product Technology, 2015)

Multi-scale crown closure retrieval for moso bamboo forest using multi-source remotely sensed imagery based on geometric-optical and Erf-BP neural network models - Cong Wang; Huaqiang Du; Xiaojun Xu; Ning Han; Guomo Zhou; Shaobo Sun; Guolong Gao (International Journal of Remote Sensing, 2015)

Soil organic matter quantity and quality shape microbial community compositions of subtropical broadleaved forests - Junjun Ding; Yuguang Zhang; Mengmeng Wang; Xin Sun; Jing Cong; Ye Deng; Hui Lu; Tong Yuan; Joy D. Van Nostrand; Diqiang Li; Jizhong Zhou; Yunfeng Yang (Molecular Ecology, 2015)
As two major forest types in the subtropics, broadleaved evergreen and broadleaved deciduous forests have long interested ecologists. However, little is known about their belowground ecosystems despite their ecological importance in driving biogeochemical cycling. Here, we used Illumina MiSeq sequencing targeting 16S rRNA gene and a microarray named GeoChip targeting functional genes to analyse microbial communities in broadleaved evergreen and deciduous forest soils of Shennongjia Mountain of Central China, a region known as ‘The Oriental Botanic Garden’ for its extraordinarily rich biodiversity. We observed higher plant diversity and relatively richer nutrients in the broadleaved evergreen forest than the deciduous forest. In odds to our expectation that plant communities shaped soil microbial communities, we found that soil organic matter quantity and quality, but not plant community parameters, were the best predictors of microbial communities. Actinobacteria , a copiotrophic phylum, was more abundant in the broadleaved evergreen forest, while Verrucomicrobia , an oligotrophic phylum, was more abundant in the broadleaved deciduous forest. The density of the correlation network of microbial OTU s was higher in the broadleaved deciduous forest but its modularity was smaller, reflecting lower resistance to environment changes. In addition, keystone OTU s of the broadleaved deciduous forest were mainly oligotrophic. Microbial functional genes associated with recalcitrant carbon degradation were also more abundant in the broadleaved deciduous forests, resulting in low accumulation of organic matters. Collectively, these findings revealed the important role of soil organic matter in shaping microbial taxonomic and functional traits.

Pseudoroseovarius zhejiangensis gen. nov., sp. nov., a novel alpha-proteobacterium isolated from the chemical wastewater, and reclassification of Roseovarius crassostreae as Pseudoroseovarius crassostreae comb. nov., Roseovarius sediminilitoris as Pseudoroseovarius sediminilitoris comb. nov. and Roseovarius halocynthiae as Pseudoroseovarius halocynthiae comb. nov. - Cong Sun; Jie Pan; Xin-Qi Zhang; Yue Su; Min Wu (Antonie van Leeuwenhoek, 2015)

Isolation and functional characterization of salt-stress induced RCI2-like genes from Medicago sativa and Medicago truncatula - Ruicai Long; Fan Zhang; Zhenyi Li; Mingna Li; Lili Cong; Junmei Kang; Tiejun Zhang; Zhongxiang Zhao; Yan Sun; Qingchuan Yang (Journal of Plant Research, 2015)

Intercropping enhances soil carbon and nitrogen - Wen‐Feng Cong; Ellis Hoffland; Long Li; Johan Six; Jian‐Hao Sun; Xing‐Guo Bao; Fu‐Suo Zhang; Wopke Van Der Werf (Global Change Biology, 2015)
Intercropping, the simultaneous cultivation of multiple crop species in a single field, increases aboveground productivity due to species complementarity. We hypothesized that intercrops may have greater belowground productivity than sole crops, and sequester more soil carbon over time due to greater input of root litter. Here, we demonstrate a divergence in soil organic carbon (C) and nitrogen (N) content over 7 years in a field experiment that compared rotational strip intercrop systems and ordinary crop rotations. Soil organic C content in the top 20 cm was 4% ± 1% greater in intercrops than in sole crops, indicating a difference in C sequestration rate between intercrop and sole crop systems of 184 ± 86 kg C ha −1 yr −1 . Soil organic N content in the top 20 cm was 11% ± 1% greater in intercrops than in sole crops, indicating a difference in N sequestration rate between intercrop and sole crop systems of 45 ± 10 kg N ha −1 yr −1 . Total root biomass in intercrops was on average 23% greater than the average root biomass in sole crops, providing a possible mechanism for the observed divergence in soil C sequestration between sole crop and intercrop systems. A lowering of the soil δ 15 N signature suggested that increased biological N fixation and/or reduced gaseous N losses contributed to the increases in soil N in intercrop rotations with faba bean. Increases in soil N in wheat/maize intercrop pointed to contributions from a broader suite of mechanisms for N retention, e.g., complementary N uptake strategies of the intercropped plant species. Our results indicate that soil C sequestration potential of strip intercropping is similar in magnitude to that of currently recommended management practises to conserve organic matter in soil. Intercropping can contribute to multiple agroecosystem services by increased yield, better soil quality and soil C sequestration.

Phylogenetic analysis of 32 porcine circovirus type 2 isolates from Shandong, China - Jianli Shi; Shaojian Xu; Fang Fu; Xiaoyan Cong; Xiaoyuan Yuan; Zhe Peng; Jiaqiang Wu; Wenbo Sun; Yijun Du; Jun Li; Baohua Huang; Jinbao Wang (Archives of Virology, 2015)

Trace levels of mitomycin C disrupt genomic integrity and lead to DNA damage response defect in long-term-cultured human embryonic stem cells - Di Zhou; Ge Lin; Si-Cong Zeng; Bo Xiong; Ping-Yuan Xie; De-Hua Cheng; Qing Zheng; Qi Ouyang; Xiao-Ying Zhou; Wei-Ling Tang; Yi Sun; Guang-Ying Lu; et al. (Archives of Toxicology, 2015)

Application of 3D fine seismic interpretation technique in Dawangzhuang Area, Bohai Bay Basin, Northeast China - Shiqiang Xia; Quan Li; Xiande Wang; Cong Sun; Ye Wang; Zhen Hu; Xin Li; Qifang Zheng (Arabian Journal of Geosciences, 2015)

IL-2 Inhibited the Generation of CD4+ Memory T Cells - Hongjuan Lu; Jie Chen; Xuefeng Nie; Cong Liu; Weimin Sun (Cell Biochemistry and Biophysics, 2014)

Mammalian expression levels of cellulase and xylanase genes optimised by human codon usage are not necessarily higher than those optimised by the extremely biased approach - Zhiguo Liu; Yanxia Sun; Tao Feng; Qianqian Ji; Peiqing Cong; Yaosheng Chen; Zuyong He (Biotechnology Letters, 2014)

Seroprevalence investigation of bovine brucellosis in Macenta and Yomou, Guinea - Seydou Sylla; Youssouf Sidimé; Yixue Sun; Sayon Doumbouya; Yanlong Cong (Tropical Animal Health and Production, 2014)

The geometric factor of high energy protons detector on FY-3 satellite - ShenYi Zhang; XianGuo Zhang; ChuiQin Wang; GuoHong Shen; Tao Jin; BinQuan Zhang; YueQiang Sun; GuangWu Zhu; JinBao Liang; XiaoXin Zhang; JiaWei Li; Cong Huang; et al. (Science China Earth Sciences, 2014)

The Synthesis of l-dopa-l-Tyr and The Interaction of l-dopa-l-Tyr With ctDNA - Kui Lu; Jing Sun; Dong-Xin Zhao; Qi-Cong Zhu; Wei Lv (International Journal of Peptide Research and Therapeutics, 2014)

Myocardial Dysfunction in Early Diabetes Patients with Microalbuminuria: A 2-Dimensional Speckle Tracking Strain Study - Ran Guo; Ke Wang; Wei Song; Tao Cong; Zhi-Juan Shang; Ying-Hui Sun; Yi-Nong Jiang (Cell Biochemistry and Biophysics, 2014)

Erratum to: Genome-wide analysis of DNA methylation in an APP/PS1 mouse model of Alzheimer’s disease - Lin Cong; Jianping Jia; Wei Qin; Yan Ren; Yongxin Sun (Acta Neurologica Belgica, 2014)

Genome-wide analysis of DNA methylation in an APP/PS1 mouse model of Alzheimer’s disease - Lin Cong; Jianping Jia; Wei Qin; Yan Ren; Yongxin Sun (Acta Neurologica Belgica, 2014)

Origin area and migration route: Chloroplast DNA diversity in the arctic-alpine plant Koenigia islandica - Cong Long; YunJiang Min; XiuXia Zhao; ChunLei Yany; Hang Sun; HouYuan Lü; LingYu Tang; ZhongZe Zhou (Science China Earth Sciences, 2014)

Meta-discoveries from a synthesis of satellite-based land-cover mapping research - Le Yu; Lu Liang; Jie Wang; Yuanyuan Zhao; Qu Cheng; Luanyun Hu; Shuang Liu; Liang Yu; Xiaoyi Wang; Peng Zhu; Xueyan Li; Yue Xu; et al. (International Journal of Remote Sensing, 2014)

Identification of a new Mpl-interacting protein, Atp5d - Hongyan Liu; Zhenhu Zhao; Yuxu Zhong; Yajun Shan; Xiaohong Sun; Bingzhi Mao; Yuwen Cong (Molecular and Cellular Biochemistry, 2014)

Shapinggou: the largest Climax-type porphyry Mo deposit in China - Hong Zhang; Cong-Ying Li; Xiao-Yong Yang; Ya-Li Sun; Jiang-Hong Deng; Hua-Ying Liang; Rui-Long Wang; Bo-Hua Wang; Yu-Xian Wang; Wei-Dong Sun (International Geology Review, 2014)

Improvement of a gene targeting system for genetic manipulation in Penicillium digitatum - Qian Xu; Cong-yi Zhu; Ming-shang Wang; Xue-peng Sun; Hong-ye Li (Journal of Zhejiang University-SCIENCE B, 2014)

Induced pluripotent stem cells: origins, applications, and future perspectives - Jing Zhao; Wen-jie Jiang; Chen Sun; Cong-zhe Hou; Xiao-mei Yang; Jian-gang Gao (Journal of Zhejiang University-SCIENCE B, 2013)

Microbiota Regulates the TLR7 Signaling Pathway Against Respiratory Tract Influenza A Virus Infection - Sha Wu; Zhen-You Jiang; Yi-Fan Sun; Bin Yu; Jia Chen; Cong-Qi Dai; Xian-Lin Wu; Xiao-Long Tang; Xiao-Yin Chen (Current Microbiology, 2013)

Pestalotiopsis yunnanensis sp. nov., an endophyte from Podocarpus macrophyllus (Podocarpaceae) based on morphology and ITS sequence data - Ji-Guang Wei; Cong-Kien Phan; Lin Wang; Tong Xu; Ji-Tong Luo; Xiang Sun; Liang-Dong Guo (Mycological Progress, 2013)

Wet precipitation chemistry at a high-altitude site (3,326 m a.s.l.) in the southeastern Tibetan Plateau - Bin Liu; Shichang Kang; Jimin Sun; Yulan Zhang; Ri Xu; Yongjie Wang; Yongwen Liu; Zhiyuan Cong (Environmental Science and Pollution Research, 2013)

Evaluation of terrestrial carbon cycle models for their response to climate variability and to CO 2 trends - Shilong Piao; Stephen Sitch; Philippe Ciais; Pierre Friedlingstein; Philippe Peylin; Xuhui Wang; Anders Ahlström; Alessandro Anav; Josep G. Canadell; Nan Cong; Chris Huntingford; Martin Jung; et al. (Global Change Biology, 2013)
The purpose of this study was to evaluate 10 process‐based terrestrial biosphere models that were used for the IPCC fifth Assessment Report. The simulated gross primary productivity ( GPP ) is compared with flux‐tower‐based estimates by Jung et al . [ Journal of Geophysical Research 116 (2011) G00J07] ( JU 11). The net primary productivity ( NPP ) apparent sensitivity to climate variability and atmospheric CO 2 trends is diagnosed from each model output, using statistical functions. The temperature sensitivity is compared against ecosystem field warming experiments results. The CO 2 sensitivity of NPP is compared to the results from four Free‐Air CO 2 Enrichment ( FACE ) experiments. The simulated global net biome productivity ( NBP ) is compared with the residual land sink ( RLS ) of the global carbon budget from Friedlingstein et al . [ Nature Geoscience 3 (2010) 811] ( FR 10). We found that models produce a higher GPP (133 ± 15 Pg C yr −1 ) than JU 11 (118 ± 6 Pg C yr −1 ). In response to rising atmospheric CO 2 concentration, modeled NPP increases on average by 16% (5–20%) per 100 ppm, a slightly larger apparent sensitivity of NPP to CO 2 than that measured at the FACE experiment locations (13% per 100 ppm). Global NBP differs markedly among individual models, although the mean value of 2.0 ± 0.8 Pg C yr −1 is remarkably close to the mean value of RLS (2.1 ± 1.2 Pg C yr −1 ). The interannual variability in modeled NBP is significantly correlated with that of RLS for the period 1980–2009. Both model‐to‐model and interannual variation in model GPP is larger than that in model NBP due to the strong coupling causing a positive correlation between ecosystem respiration and GPP in the model. The average linear regression slope of global NBP vs. temperature across the 10 models is −3.0 ± 1.5 Pg C yr −1 °C −1 , within the uncertainty of what derived from RLS (−3.9 ± 1.1 Pg C yr −1 °C −1 ). However, 9 of 10 models overestimate the regression slope of NBP vs. precipitation, compared with the slope of the observed RLS vs. precipitation. With most models lacking processes that control GPP and NBP in addition to CO 2 and climate, the agreement between modeled and observation‐based GPP and NBP can be fortuitous. Carbon–nitrogen interactions (only separable in one model) significantly influence the simulated response of carbon cycle to temperature and atmospheric CO 2 concentration, suggesting that nutrients limitations should be included in the next generation of terrestrial biosphere models.

Evaluation of a DNA vaccine candidate co-expressing GP3 and GP5 of porcine reproductive and respiratory syndrome virus (PRRSV) with interferon α/γ in immediate and long-lasting protection against HP-PRRSV challenge - Yijun Du; Jing Qi; Yu Lu; Jiaqiang Wu; Dongwan Yoo; Xing Liu; Xiumei Zhang; Jun Li; Wenbo Sun; Xiaoyan Cong; Jianli Shi; Jinbao Wang (Virus Genes, 2012)

Formation of the world's largest molybdenum metallogenic belt: a plate-tectonic perspective on the Qinling molybdenum deposits - Cong-Ying Li; Fang-Yue Wang; Xi-Luo Hao; Xing Ding; Hong Zhang; Ming-Xing Ling; Ji-Bin Zhou; Yi-Liang Li; Wei-Ming Fan; Wei-Dong Sun (International Geology Review, 2012)

Characterization and expression pattern of KIFC1-like kinesin gene in the testis of the Macrobrachium nipponense with discussion of its relationship with structure lamellar complex (LCx) and acroframosome (AFS) - Yan-Ting Wang; Huan Mao; Cong-Cong Hou; Xiao Sun; Da-Hui Wang; Hong Zhou; Wan-Xi Yang (Molecular Biology Reports, 2012)

Poly(I:C) induce bone marrow precursor cells into myeloid-derived suppressor cells - Cong Liu; Chaoxiong Zhang; Hongjuan Lu; Jianming Cai; Zhigang Wang; Jie Chen; Fang Liu; Zhumei Wu; Xiaogang Liu; Weimin Sun (Molecular and Cellular Biochemistry, 2011)

Genetic analysis of avian paramyxovirus-1 (Newcastle disease virus) isolates obtained from swine populations in China related to commonly utilized commercial vaccine strains - Zhuang Ding; Yan-long Cong; Shuang Chang; Guang-mei Wang; Ze Wang; Quan-peng Zhang; Hao Wu; Yu-zhang Sun (Virus Genes, 2010)

Determination of Endocrine Disrupting Chemicals in Surface Water and Industrial Wastewater from Beijing, China - Jing Ge; Jian Cong; Ying Sun; Guoxue Li; Zhiqiang Zhou; Chuanfan Qian; Fengmao Liu (Bulletin of Environmental Contamination and Toxicology, 2010)

Effects of several immunostimulants on phenoloxidase and hemocytes of the crab Charybdis japonica - Tingjun Fan; Miaomiao Yu; Lingling Yang; Zhenping Shi; Wenjie Sun; Rishan Cong; Xiuxia Yang; Guojian Jiang (Journal of Ocean University of China, 2009)

Supplementary data: Assessment of genetic diversity ofLycoris longituba (Amaryllidaceae) detected by RAPDs - Chuan-Liang Deng; Jian Zhou; Wu-Jun Gao; Fu-Cong Sun; Rui-Yun Qin; Long-Dou Lu (Journal of Genetics, 2006)

Agrobacterium-mediated transformation of the apple rootstock Malus micromalus Makino with the RolC gene - Zhen Zhang; Aijun Sun; Yu Cong; Bingcheng Sheng; Quanhong Yao; Zong-Ming Cheng (In Vitro Cellular & Developmental Biology - Plant, 2006)

Zircon Ce4+/Ce3+ ratios and ages for Yulong ore-bearing porphyries in eastern Tibet - Hua-Ying Liang; Ian H. Campbell; Charlotte Allen; Wei-Dong Sun; Cong-Qiang Liu; Heng-Xiang Yu; Ying-Wen Xie; Yu-Qiang Zhang (Mineralium Deposita, 2006)

Purification and characterization of hatching enzyme from flounder Paralichthys olivaceus - Zhen-Ping Shi; Ting-Jun Fan; Ri-Shan Cong; Xiao-Feng Wang; Wen-Jie Sun; Ling-Ling Yang (Fish Physiology and Biochemistry, 2006)

Deregulation of NF-κB and its upstream kinases in cancer - Shao-Cong Sun; Gutian Xiao (Cancer and Metastasis Reviews, 2003)